Rational Design of Naringenin-Functionalized ZnO Nanoparticles for Wound Healing Applications with Cytocompatibility Assessment in L929 Fibroblast Cells - Ayusha O. Dondulkar; Mandar M. Muley; Raj Kiran; Siva Hemalatha; Prakash R. Itankar; Nikhil Y. Yenorkar; Raksha A. Purohit; Sadhana Soni; Arun Upadhyay; Beauty Behera; Natasha S. Akojwar; Satyendra K. Prasad (Journal of Pharmaceutical Innovation, 2027)

Identification and validation of QTLs associated with resistance to tomato leaf curl Bangalore virus disease using QTL-seq analysis in tomato (Solanum spp.) - Bhavya Chidambara; Dayanandhi Elangovan; Avverahally T. Sadashiva; S. Ramesh; Krishna Reddy M; Manoj Prasad; H. C. Prasanna; Kundapura V. Ravishankar (Molecular Biology Reports, 2026)

Beyond the dung heap: the reliability of spores of the ascomycete fungal genus Sporormiella (incl. Preussia) as a proxy indicator of dung and grazing animals - David L. Hawksworth; Patricia E.J. Wiltshire; K. Anupama; M.B. Govinda Rajulu; N. Thirunavukkarasu; S. Prasad; Kevin J. Edwards; T.S. Suryanarayanan (Review of Palaeobotany and Palynology, 2026)

Salmonella vaccines in poultry: An update on the current status - Lakshmi Prakasan; Sonu S. Nair; Santanu Pal; T.R. Arun; V. Athira; Mostafa Y. Abdel-Glil; Ayan Mukherjee; Abhishek; Bablu Kumar; Premanshu Dandapat; Prasad Thomas (Research in Veterinary Science, 2026)

Tunable rGO–ZnO/CuO nanocomposites for energy storage applications: Enhanced electrochemical, antibacterial and thermal performance - Shibi Krishnan; Pillai Aswathy Mohan; Arun S. Prasad (Next Research, 2026)

A Single Substitution of Valine to Glutamic Acid in the Omega-Like Loop Introduces a Penicillinase-Like Activity in MSMEG_6194 by Compromising its Role as DD-Carboxypeptidase - Aditya Prasad Panda; Debasmita Chatterjee; Anik Roy; Sarmistha Biswal; Anindya S. Ghosh (Current Microbiology, 2026)

Differential expression patterns of selective energy metabolism associated genes in fresh and freeze-thawed bubaline spermatozoa at uniform durations of in vitro capacitation - B.V.S. Sai Kiran; C.H. Srinivasa Prasad; B. Rambabu Naik; K. Aswani Kumar; S. Lavanya; Nikhil Kumar Tej; Iqbal Hyder (Cryobiology, 2026)

Defluoridation of Fluoride-Contaminated Wastewater Using ZnCl₂-Modified biochar: Kinetics and Isotherm Analysis - Hirpha Adugna Areti; Mani Jayakumar; Lata Deso Abo; B. S. Naveen Prasad; Suresh Krishnan; Nufbek Worku Salodi; Kenenesa Alemu Jima; Amansisa Aduna Waktola (Water, Air, & Soil Pollution, 2026)

Cross incompatibility restricting genome exchange and diversification of primary gene pool in plants: challenges and opportunities - Mahendar Thudi; Yogesh Dashrath Naik; Uday Chand Jha; M. S. Sai Reddy; Manish Kumar Pandey; Reyazul Rouf Mir; Muraleedhar S. Aski; Murukarthick Jayakodi; Venugopal Mendu; Naveen Puppala; P. V. Vara Prasad; Somashekhar M. Punnuri; et al. (Theoretical and Applied Genetics, 2026)
Key message Crop wild relatives provide essential genetic diversity for improving crop resilience; however, pre- and post-zygotic barriers often restrict interspecific hybridization. Recent approaches enable their effective use in crop improvement programs. Abstract Crop wild relatives (CWR), closely related wild taxa of cultivated crops, offer a wealth of genetic diversity essential for developing traits to help crops adapt to the challenges of biotic and abiotic stresses. This diversity is critical to meet the increasing global demand for food, especially under the looming threat of climate change. However, crossing between individuals from different species often results in maladapted or inviable offspring due to pre- and post-zygotic barriers. Pre-zygotic barriers prevent successful pollen–stigma interactions and pollen tube growth, while post-zygotic barriers include hybrid embryo or endosperm failure and chromosome pairing issues, contributing to cross incompatibility (CI). These barriers restrict genome exchange and hinder the diversification of the primary gene pool in plants. Overcoming these barriers is a significant challenge. This review explores the diverse pre- and post-zygotic barriers in interspecific hybridization, emphasizing genetic factors related to CI. Additionally, this review highlights biotechnological approaches such as somatic hybridization and embryo rescue techniques, which are used to overcome these barriers. Through continued research and innovation, these barriers can be overcome, unlocking the full potential of CWR to address the evolving demands of global agriculture. Recent advances in synthetic biology now offer the possibility to reprogram reproductive barriers, turning CI into a controllable trait for hybrid development.

Estimation of Soil Moisture Using Multi-Polarization SAR Data: A Kernel Based Approach - T. S. Prasad; B. Laxman; V. V. Ganesh; M. A. Fyzee; K. V. Ramana (Journal of the Indian Society of Remote Sensing, 2026)

Influence of GGBFS and alkali activator concentration on the geoengineering behavior of geopolymer-stabilized expansive soil - Murapaka Swamynaidu; S. Eswara Rao; Suresh Prasad Singh (Innovative Infrastructure Solutions, 2026)

Unravelling genetic variation in drought QTL pyramided lines to identify key traits for drought tolerance in rice - M. Gnana Akshaya; C. R. Anusha; G. Padmavathi; S. V. Sai Prasad; Mayank Rai; N. K. Singh; A. Sai Harini (Indian Journal of Genetics and Plant Breeding, 2026)

Status of insecticide resistance and detoxification enzymes activity in pink bollworm, Pectinophora gossypiella (Saunders) populations from India - K. Srilekha; A. G. Sreenivas; Jaba Jagdish; Pramod Katti; S. G. Hanchinal; Y. S. Amaresh; M. Lakshmikanth; Sujit Kumbhare; Pooja Verma; Vivek Shah; G. T. Behere; Y. G. Prasad; et al. (Ecotoxicology, 2026)

Black carbon as a compound agricultural stressor: impacts on plant physiology, crop productivity, and agricultural sustainability - Brindha Prasad; Jothimani Palanisamy; S. K. Rajkishore; P. Renukadevi; M. Kavitha; Muthamizh Selvan Annadurai (Plant Cell Reports, 2026)

Three new variants of Puccinia triticina causing wheat leaf rust in India - Subodh Kumar; O. P. Gangwar; P. Prasad; S. C. Bhardwaj; P. L. Kashyap; Hanif Khan; Sddanna Savadi; P. V. Patil; Ranjana Chakraborty (Indian Phytopathology, 2026)

Seasonal dynamics of trophic status in the coastal Bay of Bengal - D N Rao Darapu; Aneesh A Lotliker; Kiran Kumar Reddy; E Pattabhi Rama Rao; P S N Acharyulu; B S K Kumar; S Shiva Prasad; B J M Reddy; K Santhosh; P C Mohammed Munzil (Journal of Earth System Science, 2026)

Evaluation of biopolymer-enabled Trichoderma and compatible fungicides for the management of seed and soil-borne pathogens in oilseed crops - K. Vinod Kumar; M. Kavya; K. S. V. Poorna Chandrika; R. D. Prasad; S. K. Tripathi; V. Sowmya (Indian Phytopathology, 2026)

A Multi‐Model Ensemble Reveals a Diverging Hydrological Cycle in the Upper and Lower Transboundary Brahmaputra River Basin - Priyam Deka; Manabendra Saharia; Sharad Jain; Ved Prakash; Sujay Kumar; Augusto Getirana; Suneet Bansal; Kondapalli Niranjan Kumar; V. S. Prasad; Mrutyunjay Mohapatra (International Journal of Climatology, 2026)
The transboundary Brahmaputra basin is a significant component of the Asian Water Tower, housing approximately 66 million people in four countries and experiencing intense floods. However, this data‐scarce river has been subject to very few studies related to the long‐term assessment of its water budget. In this study, a multi‐model ensemble Indian Land Data Assimilation System (ILDAS) is set up to study the trends and variability in the water budget components from 1981 to 2020. The results indicate no significant long‐term trend in the annual basin‐averaged precipitation, evapotranspiration (ET), and runoff; however, spatial divergence in the hydrological cycle within the basin is observed, with the upper/Himalayan part showing an accelerating hydrologic cycle, contrasted by a decelerating hydrological cycle in the lower/plain part, which gets 70% of the basin rainfall. Our findings show that the winter precipitation in the basin has decreased by 5 mm per decade. The decreasing winter precipitation is confined to the lower part of the basin, which translates into a decrease in winter ET and runoff, whereas the upper part of the basin experienced an increase in precipitation in the pre‐monsoon and monsoon periods, resulting in increasing ET and runoff. It is observed that increasing runoff enhances streamflow in the upper basin; however, this signal is nullified by declining runoff towards the downstream region, leading to no significant trend in streamflow in the lower part of the basin. Further, it is observed that the TWSA variability in the basin is significantly dependent on groundwater storage variability and the amount of water stored in rivers and floodplains. These insights enhance our understanding of the complex variability of the hydrology of the Brahmaputra River basin.

Evaluation and Error Correction of Satellite Rainfall Using Dense Network of Rain Gauges Over Mumbai - Neha Rajput; Amarjyothi Kasimahanthi; Venkatrami Reddy; Hashmi Fatima; Preveen Kumar Devarajan; V. S. Prasad (Journal of the Indian Society of Remote Sensing, 2026)

Association studies of stem characteristics and cell wall polymers for genetic enhancement of lodging resistance in rice - Kavya Zoopally; Jyothi Badri; Radhika Kommineni; Sanjeeva Rao Durbha; Akshay Mamidi; Kamala Devi Datla; Padmashree Revadi; Harshavardhan Rayudu Jamedar; S. V. Sai Prasad; Raman Meenakshi Sundaram (Journal of Plant Biochemistry and Biotechnology, 2026)

Assessment of bakanae disease response, grain trait associations, and cgSSR based molecular diversity reveal significant variation among rice varieties and breeding lines - Debashis Moharana; Debasis Dash; Anilkumar C; Awadhesh Kumar; Debobrata Dey; Sasmita Behera; Soumya Priyadarsinee Mohanty; C. Mithun; Shyamaranjan Das Mohapatra; Lambodar Behera; Bishnu Charan Marndi; Jeevan B; et al. (Physiological and Molecular Plant Pathology, 2026)

Evaluation of soil moisture forecasts for landslide-prone areas in the Western Himalayas: A case study - Hashmi Fatima; M. N. Raghavendra Sreevathsa; John P. George; V. S. Prasad (Theoretical and Applied Climatology, 2026)

Application of machine learning tools for prediction of seed cotton yield in upland cotton (G. hirsutum L.) under irrigated ecosystem - Debashis Paul; Vinita Gotmare; M. Saravanan; Sandeep Bagri; Harish Kumbhalkar; Subhash Chandra; S. K. Verma; Rishi Kumar; Y. G. Prasad (Euphytica, 2026)

Hydrogeochemical characterization and integrated groundwater quality assessment using CCME-WQI, multivariate statistics, and irrigation indices in Ambedkar Nagar Region, India - Vijayendra Pratap Dheeraj; Abhishek Kumar; Amit Kumar Rai; Avaneesh Kumar Yadav; Manvendra Singh Chauhan; Ashwani Kumar Sonkar; C. S. Singh; Arjun Prasad (Environmental Geochemistry and Health, 2026)

Understanding DMG: current treatment options and prospective solutions using nanoparticles - Ahmed Mohamed; Aleksey Lyzlov; Rachna Prasad; Rex A. Moats; Mark D. Krieger; Virendra R. Desai; Ashley S. Margol; Peter A. Chiarelli; Meenakshi Upreti (Drug Delivery and Translational Research, 2026)

Comparative Analysis of Leaflet Materials, Stent Materials, and Stent Cell Density for Bileaflet Transcatheter Mitral Valve Design - Joseph Chibuike Nwokeafor; Joshua D. Hofmeister; Breandan B. Yeats; Lakshmi Prasad Dasi; Charanjit S. Rihal; Juan A. Crestanello; Leigh Griffiths; Mohamad A. Alkhouli; Hoda Hatoum (Annals of Biomedical Engineering, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A 5200-year record of vegetation dynamics and variations in the Indian Summer Monsoon from the Garhwal Himalaya, India - David F. Porinchu; Mohammad Firoze Quamar; Anoop K. Singh; Nagendra Prasad; Bahadur S. Kotlia (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Influence of regional rainfall biases on sub-seasonal variability during boreal summer over South Asia in NGFS reanalysis - Bibhuti S. Keshav; Mohan T. S; Smrutishree Lenka; Nagarjuna Rao D; Raghavendra Ashrit; V.S. Prasad (Dynamics of Atmospheres and Oceans, 2026)

Long-term Assessment of Integrated Nutrient Management Strategies on Soil Health and Yield Sustainability in a Rainfed Maize-based Cropping System - Bikram Borkotoki; P. K. Sarma; Palakshi Borah; Nikhita Kakati; Nupur Kalita; Nikhilesh Baruah; Prasanta Neog; Jayanta Kalita; Arunjyoti Sonowal; Budha Bora; Digambar Sarma; M. K. Sarma; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Development and Evaluation of Tofacitinib-Loaded Ethosomal Gel for Transdermal Management of Rheumatoid Arthritis - Pavani Chowdary; Vishnu Pulavarthy; V. V. S. Rajendra Prasad; Jyothi Golagana; V Balchander; Sadhana Noothi (Journal of Pharmaceutical Innovation, 2026)

Arsenic, selenium, cadmium and lead contamination in Garhwal Himalayan groundwater: an integrated geospatial, indexical and statistical framework for health risk evaluation and sustainable development - Mukesh Prasad; Manoj Wadhwa; Jaswinder Singh; Vikas Thada; Utpal Shrivastava; R. S. Aswal; Johnbosco C. Egbueri (Environmental Geochemistry and Health, 2026)

Multiple adoption of CSA practices and their determinants: a bundle wise analysis in climate vulnerable regions of Andhra Pradesh, India - Bhavani Prasad Thottadi; S. P. Singh (Mitigation and Adaptation Strategies for Global Change, 2026)

Aflatoxin B1 contamination and fungal diversity in oilseed cakes and formulated feeds from livestock feed markets in Addis Ababa and surrounding areas - Adey Melesse Yalew; Alemayehu Teressa Negawo; Tesfaye Alemu; Jean Hanson; Michael Blummel; Nebiyat Nigusie Woldeyohannis; Yilikal Assefa Teferi; Yonas Asmare; Prasad Kodukula V.S.V.; Chris S. Jones (Mycotoxin Research, 2026)
This study was conducted in Addis Ababa, surrounding peri-urban and urban feed markets to assess the prevalence of aflatoxin B 1 (AFB 1 ) and identify fungal diversity in livestock feeds. Two hundred and ninety samples of oil seed cakes and formulated feeds were collected from the randomly selected feed vendors. The samples were analysed for aflatoxin B 1 using a Helica ® Aflatoxin B 1 (low matrix) Enzyme-linked immunoassay (ELISA) kit. To validate the ELISA results, a subset of randomly selected samples was further analysed using High-performance liquid chromatography-fluorescence detection (HPLC-FLD). The results indicated that 92% of poultry ration, 72% of dairy ration, 66% of linseed cake, 64% of noug seed cake, 61% of cotton seed cake, and 36% of soybean cake were contaminated with AFB 1 exceeding the permissible level (20 µg/kg) in Ethiopia. To evaluate fungal diversity, genomic DNA was extracted, pooled by feed type, and sequenced. The findings revealed variations in the diversity indices of fungal phyla, families, genera and species. The Metabarcoding results revealed Ascomycota as the dominant phylum in all feeds, with Aspergillaceae , Nectriaceae , Botyosphaeriaceae , and Cladosporiaceae being the dominant families. Aspergillaceae accounts for 53%, 43%, 16%, 33%, 11%, and 28% of the total fungal contamination detected in cotton seed cake (S1), noug seed cake (S2), soybean cake (S3), linseed cake (S4), poultry ration (S5), and dairy ration (S6), respectively. The synergistic presence of multiple fungal species, some of which are known to be harmful, was identified in the feed samples. Among the species, the proportion of Aspergillus flavus found was 1.8%, 3.8%, 0%, 0.4%, 1.2%, and 1.2% in the feeds S1–S6, respectively. The findings highlight the critical need for enhanced feed management practices, improved education and training for feed handlers on feed safety, stricter regulatory measures, and more research on mycotoxins mitigation.

Long-term integrated nitrogen management: effects on crop productivity, soil properties, and carbon sequestration potential of a rainfed maize-wheat cropping system in Punjab, India - Mohammad Amin Bhat; MJ Singh; Abrar Yousuf; Anil Khokhar; Parminder Singh Sandhu; Kanwar Barjinder Singh; Balwinder Singh Dhillon; Randeep Singh; Priya P. Gurav; S. Kundu; Chary G. Ravindra; J. V. N. S. Prasad; et al. (Environmental Sustainability, 2026)

The dual role of autophagy in breast cancer stemness and treatment resistance - Anu Jayanthi Panicker; Kirti S. Prabhu; Ummu Habeeba; Zahwa Mariyam; Affan Asim; Sarada Prasad Dakua; Shahab Uddin (Tissue and Cell, 2026)

A new remote sensing-derived high resolution eco-physiological land use land cover (HR Eco-P LULC) product in support of regional climate modeling over the Indian landscape - Kshama Gupta; Bhoomika Ghale; Shailja Mamgain; Arijit Roy; Shweta Bhati; T.J. Anurose; A. Jayakumar; Abhishek Danodia; Harish Chandra Karnatak; Pramod Kumar; Raghavendra Pratap Singh; Murali Krishna Gumma; et al. (Remote Sensing Applications: Society and Environment, 2026)

Advancements in Spatio-temporal agricultural drought monitoring and modeling: a comprehensive review on multi-source remote sensing and machine learning techniques - Suresh Mondal; Kumar Arun Prasad; A. L. Achu; S. Kaliraj; K. Balasubramani (Theoretical and Applied Climatology, 2026)

Deciphering population ecology of Contarinia maculipennis Felt in tuberose: insights from age-stage, two-sex life table and below-ground soil environment - M. C. Keerthi; D. M. Firake; Y. S. Wagh; K. Ashok; K. V. Prasad; K. C. Naga; Sagar Pandit (Phytoparasitica, 2026)

Leveraging High-Throughput Phenomics and Morpho-Physiological Traits for Selecting Drought-Tolerant Pigeonpea [Cajanus cajan (L.) Millspaugh] Genotypes - Prasad; S. Muniswamy; P. S. Basavaraj; Anuja Gangurde; Rohit Babar; Shweta Shinde; K. M. Boraiah; C. B. Harisha; H. M. Halli; Dasari Sreekanth; Praveen Kumar; C. Laxuman; et al. (Journal of Plant Growth Regulation, 2026)

Seawater intrusion in a delta of southern India: Evidence from hydrogeochemistry and stable isotopes - Y. S. Prasad; R. V. Ramana; V. S. Jeyakanthan; Y. R. S. Rao (Acta Geochimica, 2026)

Predicting non-mixing river flow using data-driven approaches: A case study in the Menindee region in Australia - Leyde Briceno Medina; Duy Nguyen; Klaus Joehnk; Ravinesh C. Deo; Mumtaz Ali; Salvin S. Prasad; Nathan Downs (Science of The Total Environment, 2026)

Exploration of medicinal plants, their bioactive molecules and formulations from the Vidarbha region of Maharashtra, India in the treatment of inflammatory bowel disease - Nikhil Y. Yenorkar; Ayusha O. Dondulkar; Natasha S. Akojwar; Raksha A. Purohit; Prakash R. Itankar; Shashikant Singh; Satyendra K. Prasad (Next Research, 2026)

Evaluating various vegetation indices in triangle method to enhance high-resolution soil moisture estimation - Bharatkumar S. Prajapati; Sonu Kumar; Rajendra Prasad; Prashant Kumar Srivastava; Jyoti Sharma; Shubham Kumar Singh; Manika Gupta; Muskan Dua (Advances in Space Research, 2026)

Validation of the SeLECT and CAVE scores as clinical biomarkers and prediction models in an underserved community hospital - Stacey Kim; Yohan Ko; Aaron Fernandez; Alan Salim; Christel Benny; Dawn S. Eliashiv; Hari Prasad Kunhi Veedu (Next Research, 2026)

A TD-DFT Exploration and Artocarpus heterophyllus Plant Leaf Extract-Based Decolorization of Methylene Blue - C. M. Ugendar; A. S. Pani; K. Rambabu; Naina; P. Singh; K. Sivakumar; M. Rahaman; I. Bahadur; Ch. Prasad (Water, Air, & Soil Pollution, 2026)

Polyphenol-based therapeutics for glioblastoma: validation from In-vitro cell viability assay and integrated onco-omics computational analysis - Yogesh H S; Sadik Shaik; Sibghatullah Muhammad Ali Sangi; Krishna Swaroop; Sreeharsha Nagaraja; Anitha K N; Vipin Kumar Mishra; Santosh Prasad Chaudhary Kurmi; Subrata Nath; Shankar Thapa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Satellite-based estimation of potential evapotranspiration using the Thornthwaite–Mather model for sub-regional water resource assessment - G. M. Rajesh; S. Prasad; Dinesh Kumar Vishwakarma; Rohitashw Kumar; Sudhir Kumar Singh; A. Z. Dewidar; A. A. Al‑Othman; M. A. Mattar (International Journal of Environmental Science and Technology, 2026)

Pollen morphology and diversity in Rosa × hybrida cultivars with comparative insights across the Rosaceae family - A. J. Kulkarni; M. S. Nimbalkar; S. A. Patil; M. C. Pagariya; P. R. Jadhav; M. P. Mane; A. B. Magdum; K. V. Shinde; D. V. S. Raju; K. V. Prasad; G. B. Dixit; P. G. Kawar (Plant Biosystems, 2026)

Structure-based screening of marine carotenoids: fucoxanthin and its derivatives as potential inhibitors of the SARS-CoV-2 nucleocapsid phosphoprotein - Murali Krishna Paidi; Shivaleela Biradar; T. S. Keshava Prasad (In Silico Pharmacology, 2026)

State-of-the-art hydraulic modelling: a comprehensive review of HEC-RAS for 1D and 2D applications - Jyoti Prasad Gupta; Mukul Kumar Sahu; G. S. Dwarakish; H. R. Shwetha (Hydrological Sciences Journal, 2026)

Conservation agriculture for riverine agri-food systems under the climate crisis: enhancing soil health and mitigating erosion - Pazhanisamy S.; Devendra Singh; Rodda Chandana Devi; Vijay Singh Meena; Sunil Kumar; R.S. Singh; S.S. Prasad; R. Sushma Devi; Jogdande Sai Prasad; K. Damodar; Abhinandan Singh; V. Sridevi; et al. (Soil and Tillage Research, 2026)

Species transport modeling and tar analysis in palmyra palm fruit nutshell gasification: Performance evaluation and process optimization - Murugan Paradesi Chockalingam; Beno Wincy Winsly; Joseph Sekhar Santhappan; Boopathi M; Aruvi B; Suji Prasad S J (Fuel, 2026)

Near real-time quality-control of MESONET rain gauges: Generating high-resolution gridded rainfall by blending with GPM satellite observations - Upal Saha; V.S. Prasad; Ashis K. Mitra; Munmun Das Gupta; S. Indira Rani; John P. George; G. Pandithurai; Rajib Chattopadhyay (Atmospheric Research, 2026)

Coercive male genital structures expose concealed female genitalia in the water strider Chimarrhometra orientalis Distant, 1879 - Dong Yeop Yang; Min Suk Oh; Myeongdong Jo; Byeongho Lee; Jaehyun Choi; Suraj Basnet; Indra Prasad Subedi; Seunghwan Lee; Chang S. Han (Arthropod Structure & Development, 2026)

The ferroptosis-ncRNA-exosome triad: key orchestrators in cancer immunopathogenesis - Majid S. Jabir; Abdulrahman T. Ahmed; Ahmed Hussen; Ali G. Alkhathami; Rekha M. M.; Yash Sharma; Pooja Rani; G. V. Siva Prasad; Jawad Kadhim Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Hippocampal Bioenergetics and Metabolic Profiling Identifies Fatty Acid Oxidation as a Potential Therapeutic Target in Traumatic Brain Injury - Di Zhou; Mengxuan Shi; Mitchell D. Kilgore; Yuwen Xiu; Yingjie Wang; Danni Wang; Thin Yadanar Sein; Charles Vidoudez; Amin Iskender; Gaby A. Moyano; Lauren M. Dumont; Yinghua Jiang; et al. (Molecular Neurobiology, 2026)
Traumatic brain injury (TBI) causes lasting neurological impairments, particularly learning and memory deficits associated with hippocampal damage. Emerging evidence suggests that hippocampal vulnerability may be linked to bioenergetic dysfunction, though its role remains poorly defined. A deeper understanding of post-TBI metabolic disturbances and their association with pathological outcomes could reveal novel therapeutic targets. In this study, we conducted functional bioenergetic assessments and multi-omics analyses on hippocampal slices using a mouse controlled cortical impact model of TBI. Seahorse analysis revealed a significant reduction in mitochondrial oxidative phosphorylation in dentate gyrus (DG) slices at day 1 (acute phase), which recovered by day 7 (subacute phase) post-TBI. Metabolomic profiling revealed acute impairments in purine nucleotide, glucose, amino acid, and fatty acid metabolism, most of which normalized by day 7. Isotope tracing indicated enhanced octanoate-derived fatty acid oxidation (FAO) in DG slices at day 7 post-TBI. Proteomics confirmed suppressed purine metabolism at day 1 across hippocampal subregions, while FAO remained preserved at day 1 and became significantly elevated by day 7, suggesting a compensatory metabolic adaptation. Administration of sodium octanoate, a medium-chain fatty acid, at 1 h post-TBI enhanced mitochondrial respiration at 24 h, reduced microglial counts at 48 h, and attenuated neurodegeneration by day 3. These findings identify FAO enhancement as a promising metabolic strategy to restore hippocampal bioenergetics and promote neuroprotection following TBI.

Improving the skill of medium range ensemble rainfall and temperature forecasts over India using MoES grand ensemble (MGE)-Part-II - V. Abhijith; Anumeha Dube; Ashu Mamgain; Harvir Singh; Raghavendra Ashrit; Sunita Verma; J. P. George; V. S. Prasad (Meteorology and Atmospheric Physics, 2026)

Assessing the performance of a high-resolution regional ensemble prediction system in predicting intense precipitation events over India - S. Kiran Prasad; Ashish Routray; Gauri Shanker; V. S. Prasad (Meteorology and Atmospheric Physics, 2026)

Efficient in vitro regeneration through leaf-derived callus in Origanum majorana (L.): a multipurpose medicinal plant - Dulam Sandhya; Phanikanth Jogam; Gulab Khan Rohela; Syam Prasad Sura; Rajender Vadluri; Mahipal S. Shekhawat; Sadanandam Abbagani (Vegetos, 2025)

Characterization of mangrove sediment pollution with focus on microplastics in Kannur, South India - Rohini Pulikkal; Ayona Jayadev; Maha Madhu; S. Gayathri Nair; Reshma Shaji; Shilpa Sasidharan; Hazeena M. Ameen; Deepa Indira Nair; Geena Prasad (Regional Studies in Marine Science, 2025)

Structural characterization and metabolomic insights of biofunctional nanoparticles synthesized from Curcuma caesia Roxb - Lakshmi S; Vaibhavi J Godkhindi; Spoorthi S; Sudeep D; Aryaa N Murthy; Nagendra Prasad M N; Raj Niranjan S; Manju K; Syed Baker (Next Research, 2025)

The transforming thermal performance of residential buildings in the lower Himalayan cold climatic region - Neha Das; Rajasekar Elangovan; Prabhjot. S․ Chani; Satish Kumar; Prasad Vaidya (Building and Environment, 2025)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Co-infection with systemic candidiasis and diphtheritic aspergillosis in a Buffalo calf - Sumit S. Kamble; Veena R. Sutar; S. D. Vinay Kumar; Sonu S. Nair; V. Athira; J. Pranathi; Pawan Kumar; Prasad Thomas; Bablu Kumar; Premanshu Dandapat; Vidya Singh; Abhishek (Veterinary Research Communications, 2025)

Impact of heat stress on expression of nine major starch biosynthesis genes in two wheat genotypes differing for heat stress tolerance - Gautam Saripalli; Raju Bheemanahalli; S. V. Krishna Jagadish; P. V. Vara Prasad; Kulvinder S. Gill; Sachin Kumar; P. K. Sharma; H. S. Balyan; P. K. Gupta (Plant Physiology Reports, 2025)

Improvement of tropical cyclone prediction with vortex initialization in cyclic data assimilation using WRF model - Meenakshi Shenoy; V. S. Prasad; D. Srinivas; K. B. R. R. Hari Prasad; Suryakanti Dutta; P. V. S. Raju (Natural Hazards, 2025)

How well do multi-source ensemble rainfall products capture precipitation during monsoons in India? - K. Amarjyothi; D. Preveen Kumar; M. Venkatarami Reddy; Ashis. K. Mitra; M. N. Raghavendra Sreevathsa; M. Neha Rajput; V. S. Prasad (Meteorology and Atmospheric Physics, 2025)

Machine learning-driven flood susceptibility mapping: comparing model performances and feature influences in a coastal watershed of the Eastern mediterranean - Hazem Ghassan Abdo; Sahar Mohammed Richi; Ahmed Ali Bindajam; Bilel Zerouali; Okan Mert Katipoğlu; Pankaj Prasad; Maged Muteb Alharbi; Mona S. Ramadan; Javed Mallick; Mounir Ghribi (Journal of Coastal Conservation, 2025)

Utilization of doubled haploid breeding approach in introgression of QTL/gene(s) for parental line improvement of hybrid rice - Sudhansu Sekhar Bhuyan; Durga Prasad Barik; Byomkesh Dash; Prachitara Rout; Manjusha Chandravani; Swagatika Baral; Anindita Mishra; Ram Lakhan Verma; Jawahar Lal Katara; Parameswaran Chidambaranathan; B. N. Devanna; S. R. Prabhukarthikeyan; et al. (Journal of Applied Genetics, 2025)

Isolation of Brucella suis from cattle in India: whole genome analysis unravels potential for zoonotic transmission - M. Suman Kumar; S. S. R. Vakamalla; Haris Ayoub; C. Lalsangzuala; A. R. Chandni; Himani Dhanze; Valil Kunjukunju Vinod; S. Anbazhagan; Prasad Thomas (Brazilian Journal of Microbiology, 2025)

A new framework and classification scheme to indicate best-fit agroforestry systems: a locally adapted approach in the western coast of India - Harshavardhan Sarita Krishnarao Deshmukh; Minalkumar B. Tandel; Manmohan J. Dobriyal; Rajesh Gunaga; Ripu Kunwar; Narender Singh Thakur; Santoshkumar A. Huse; Ram Prasad Acharya; K. R. Ramesh; Shailesh S. Harne; Vishal B. Shambharkar; Ram J. Mevada; et al. (Agroforestry Systems, 2025)

Isolation and characterization of a potent anticancer fraction from Clinacanthus nutans targeting MCF-7 and A549 cells: an integrated in vitro and in silico study - Sushma Jahagirdar; Smitha S. Bhat; R. Sindhu; Sarana Rose Sommano; Rashmi Doddabassappa; Pradeep Matam; Nishanth Bhat; Shashanka K. Prasad (In Silico Pharmacology, 2025)

Do climate change and geopolitical risk influence volatility? Empirical evidence from leading economies - Saroj S. Prasad; Veerma Puri; Priti Bakhshi (Journal of Environmental Management, 2025)

Enhancing maize grain nutritional quality through combined application of Zn-enriched compost and rhizobacteria under natural arid conditions - Zafar Iqbal; Azhar Hussain; Maqshoof Ahmad; Abubakar Dar; Moazzam Jamil; Usman Zulfiqar; Hossam S. El-Beltagi; Muneera A. Saleh; P.V. Vara Prasad; Ivica Djalovic (Journal of Cereal Science, 2025)

Decadal analysis of black carbon aerosols over the central Indo-Gangetic Plain: trends, source regions, and policy impact - Bakhtawar Hameed Abdullah; Prayagraj Singh; Aditya Vaishya; Prabhunath Prasad; Shantanu Rastogi; Mukunda M. Gogoi; S. Suresh Babu (Atmospheric Research, 2025)

Heat stress analysis using RTMA over heatwave regions in India - Ch. Sridevi; M. V. S. Ramarao; Ashish Routray; B. Tarakesh Lakshman; K. B. R. R. Hari Prasad; Suryakanti Dutta; D. Srinivas; Edward Colón; Annette Gibbs; Manuel Pondeca; V. S. Prasad (Theoretical and Applied Climatology, 2025)

Comparative study on chemical characteristics of aromatic volatile organic compounds (VOCs) and gene expression in scented and non-scented Rosa Hybrida cultivars - P. R. Jadhav; T. P. Ahammed Shabeer; R. S. Yadav; A. Dhole; R. G. Kale; D. V. S. Raju; B. Ghosh; K. Banerjee; K. V. Prasad; P. G. Kawar (Physiology and Molecular Biology of Plants, 2025)

Improvements in Precipitation Product with Newer NASA/GPM IMERG Algorithm on TRMM/TMPA Data During Summer Monsoon Period over India - M. Venkatarami Reddy; K. Niranjan Kumar; Ashis. K. Mitra; K. Amarjyothi; Imranali M. Momin; Saji Mohandas; V. S. Prasad (Journal of the Indian Society of Remote Sensing, 2025)

Analysing the spatiotemporal dynamics of coastal aquaculture along the northern coastal plains of Tamil Nadu, India, using remote sensing time series data - S. Ravi Prasanth; T. K. Senthamizh; Sulochana Shekhar; L. Gnanappazham; Kumar Arun Prasad (Aquaculture International, 2025)

Correction: Evaluating high-resolution global NWP model day-1 precipitation forecasts for the Indian monsoon: Potential to use in real-time applications - Mannem Venkatarami Reddy; Ashis K Mitra; Kondapalli Niranjan Kumar; K Amarjyothi; I M Momin; Balaji Kumar Seela; P Mukhopadhyay; Raghavendra Ashrit; Saji Mohandas; V S Prasad (Journal of Earth System Science, 2025)

Behavior of interlocking compressed stabilized earth masonry under flexure and shear - H. G. Vivek Prasad; D. B. Nirmala; Mangala Keshava; K. S. Jagadish (Innovative Infrastructure Solutions, 2025)

Isolation and characterization of xyloglucan endotransglucosylase/hydrolase (XET/XTH) provide insights on the functional evolution of XET family proteins in ginger (Zingiber officinale Roscoe) - Arshya Devi; Divya P. Syamaladevi; B. Mekha; K. S. Nehamol; I. P. Vijesh Kumar; T. E. Sheeja; D. Prasad (Genetic Resources and Crop Evolution, 2025)

Fluoxetine HCl-Loaded Nanostructured Lipid Carriers for Nose-to-Brain Delivery: Optimization and Synergistic Role of Saffron Oil - Avinash R. Tekade; Prasad V. Kadam; Manoj K. Aswar; Anil B. Gaikwad; Rohit B. Shinde; Snehal S. Kharade (Journal of Molecular Neuroscience, 2025)

Evaluating high-resolution global NWP model day-1 precipitation forecasts for the Indian monsoon: Potential to use in real-time applications - Mannem Venkatarami Reddy; Ashis K Mitra; Kondapalli Niranjan Kumar; K Amarjyothi; I M Momin; Balaji Kumar Seela; P Mukhopadhyay; Raghavendra Ashrit; Saji Mohandas; V S Prasad (Journal of Earth System Science, 2025)

Seasonal dynamics of dissolved and particulate organic carbon in nearshore waters of the Andaman Islands - P. M. Mohan; R. Karuna Kumari; N. V. H. K. Chari; Sai Elangovan S.; J. Joyson Joe Jeevamani; Mamidala Harikrishna Prasad; Supriyo Chakraborty; V. Sachithanandam (Frontiers in Marine Science, 2025)
This study investigates the seasonal and spatial variability of hydrochemical parameters and organic carbon pools between the South Andaman Islands (SAI) and North Andaman Islands (NAI) under contrasting monsoonal regimes. Seawater temperature (26.1 – 33.5°C) was consistently higher in SAI due to reef-associated stratification, while NAI exhibited greater variability. Salinity (25.2 – 35.9) and pH were more stable in SAI, whereas NAI showed lower values and higher variability driven by freshwater inputs from the Bay of Bengal river systems. Turbidity and dissolved inorganic nutrients (DIN, DIP, DSi) were significantly higher in NAI, reflecting strong terrestrial and riverine influence. Dissolved organic carbon (DOC; 103 – 772 µM) and particulate organic carbon (POC; 22 – 168 µM) concentrations were consistently higher in NAI, particularly during the spring intermonsoon (SIM) and northeast monsoon (NEM), while SAI exhibited lower but more variable concentrations linked to reef metabolism. Seasonal drivers included freshwater and terrestrial inputs enhancing DOC during SIM and NEM, and monsoon-induced mixing reducing concentrations during the southwest monsoon (SWM). POC levels were enriched in NAI throughout, whereas SAI showed greater variability related to reef-derived particulate cycling. The POC: DOC ratio (0.04 – 0.83) highlighted contrasting biogeochemical regimes, with NAI dominated by particulate-rich terrestrial inputs and SAI characterized by variable phytoplankton- and reef-driven processes. These findings emphasize the role of monsoonal forcing in shaping carbon dynamics across the Andaman Islands and the contrasting influence of terrestrial inputs in NAI versus reef-associated processes in SAI, with implications for regional carbon cycling and ecosystem functioning.

Artificial intelligence in sustainable food design: Technological, ethical consideration, and future - S. Harikrishnan; Deepika Kaushik; Prasad Rasane; Ashwani Kumar; Narinder Kaur; Chagam Koteswara Reddy; Charalampos Proestos; Fatih Oz; Mukul Kumar (Trends in Food Science & Technology, 2025)

AI-enabled smart bioengineering for sustainability - Shayista H; Lakshmi Kalyani Chinthala; Kshithij G Raj; Akshatha P; Niranjan Raj S; Manju K; Ravi Kumara; Lakshmi S; Roopanjanli S; Vaibhavi J Godkhindi; Pratheeksha M C; Nagendra Prasad M N; et al. (Next Research, 2025)

Integrated computational approach revealed the potential inhibitory effect of xanthone derivatives against Marburg virus nucleocapsid - Sai Kiran; Saleem Javid; Somashekhar M Metri; Santosh Prasad Chaudhary Kurmi; S Hemavathi; Ashok Kumar Murav; Mahalakshmi Suresha Biradar; Shankar Thapa (VirusDisease, 2025)

Integrative taxonomy reveals discovery of new blossom midge species infesting jasmine (Jasminum sambac) flower buds in India - D. M. Firake; D. Vasanthakumar; K. C. Naga; Y. S. Wagh; K. V. Prasad; D. V. S. Raju; V. R. Ukarande; A. A. Chavan; S. S. Pandit (Phytoparasitica, 2025)

Assessing the Impact of Oceansat-3 Surface Winds on Monsoonal Low-Pressure Systems Using WRF ARW Model - Meenakshi Shenoy; Suryakanti Dutta; Srinivas Desamsetti; S. Indira Rani; V. S. Prasad (Journal of the Indian Society of Remote Sensing, 2025)

Harnessing inter-subspecific genetic variability for hybrid rice improvement: analysis of genetic diversity, heterosis, and combining ability - K. Sruthi; K. B. Eswari; Ch. Damodar Raju; M. Sheshu Madhav; A. Dhandapani; M. Bala Satya Sree; K. Srikrishna Latha; P. Koteswararao; M. Sadath Ali; Divya Balakrishnan; P. Senguttuvel; Revathi Ponnuswamy; et al. (Euphytica, 2025)

Deep learning-driven rainfall prediction leveraging hybrid child drawing development optimization and time series data - Nihar Ranjan; Mubin Tamboli; Jayashree R. Prasad; Rajesh S. Prasad; Amol V. Dhumane (Earth Science Informatics, 2025)

Interaction effect of lettuce (Lactuca sativa L.) varieties in aeroponics and geoponics system - Anand Sahil; S. R. Singh; Lalu Prasad Yadav; Sheetal Rawat; A. K. Singh (Vegetos, 2025)

Development of an enzyme immunoassay employing low molecular weight recombinant Ag1 and Ag1V1 proteins of cystic fluid for the serodiagnosis of porcine cysticercosis - Siju Susan Jacob; Pinaki Prasad Sengupta; Samer Shamshad; S. Sudhagar; A.G. S. Chandu; S.S. Patil; S.Madhaba Maharana (Veterinary Parasitology, 2025)

Complex developmental cardiovascular anomalies in a Sahiwal calf: a case study on patent ductus arteriosus, defective interatrial septum and arterial malformations - Ersavadla Rajaraviteja; Poovathikkal Suvaneeth; Paramadayalan S. Selvan; Ramaswamy V. Prasad (Journal of Comparative Pathology, 2025)

Dynamics of rice microbiome: insights into functional diversity, environmental influences, response to stress, and applications - Edna Mary Varghese; Jositta George; Anagha Hareendran; Athira Anilkumar; Adharsh A. Y. Narayanan; Jesmy James; Vyshakh Thykoottathil; Aswathi Prasad; Lakshmipriya Perincherry; Bony Cyriac; M. S. Jisha (World Journal of Microbiology and Biotechnology, 2025)

Estimation of outdoor thermal comfort by integrating landsat derived LULC to WRF-UCM model over a metropolitan city of India - P. S. Hari Prasad; A. N. V. Satyanarayana (Theoretical and Applied Climatology, 2025)

Synthesized Zinc and Iron Nanoparticles on Nutrient Fortification and Crop Productivity in Sugarcane Plant-Ratoon Sequences - Ch. S. Ramalakshmi; T. N. V. K. V. Prasad; A. Sireesha; T. Sreelatha; M. Bharathalakshmi (Sugar Tech, 2025)

Validation of markers linked to the double flower per peduncle trait in Indian chickpea cultivars and germplasm: genetic variation in SFL and other R2R3-MYB transcription factors - P. S. Shanmugavadivel; A K. Srivastava; M. Senthil Kumar; Aravind Kumar Konda; Anamika Kushwaha; Jyotirmay Dubey; Shivam Anand; Meenal Rathore; Girish Prasad Dixit (Genetic Resources and Crop Evolution, 2025)

From non-renewable waste to activated carbon: A smart move towards sustainable development and environmental protection in a circular economy - Sunaina S. Patil; Anna M. Kisiela-Czajka; Hari Prasad Dasari (Waste Management, 2025)

Improvement on Prediction of Tropical Cyclone ‘Fani’ by Assimilating Quality Controlled Indian DWR Radial Wind: A Case Study - Sujata Pattanayak; Amarjyothi Kasimahanthi; Ashish Routray; V. S. Prasad (Pure and Applied Geophysics, 2025)

Quantifying suitability of transit-oriented development in Indian cities - Lalitha Sree Chintakayala; C. S. R. K. Prasad (Innovative Infrastructure Solutions, 2025)

Whale shark residency and small-scale movements around oil and gas platforms in Qatar - Steffen S. Bach; David P. Robinson; Mohammed Y. Al Jaidah; Simon J. Pierce; Prasad Thoppil; Christoph A. Rohner (Frontiers in Marine Science, 2025)
Whale sharks seasonally aggregate near oil and gas platforms in Qatar to feed on fish spawn, creating one of the world’s largest aggregations of the species. We used passive acoustic telemetry to examine their fine-scale movements, residency, and seasonality and investigate whether the platforms influence their space use in this area. Tags had a mean retention of 161 ± 186 days (standard deviation, SD) and 32 of the 117 tags were recorded in multiple years in the acoustic array (21 stations). Most detections were recorded from May to September, confirming that this whale shark aggregation is seasonal. Whale sharks stayed up to 77 consecutive days in the array (mean = 16 ± 12.51 days) and had a mean residency index R max of 0.31. Although most detections (65%) were made at a single receiver located near a platform, here designated P1, an ‘open water’ receiver near this location also had a high proportion of total detections (8.5%). Receivers at other platforms, located away from this specific site, had relatively few detections. The distance from P1, identified as the center of the aggregation, was the main explanatory variable in a GAM. Whale shark aggregations were routinely observed feeding on tuna spawn at the surface at this location, with the eggs (and hence whale sharks) moving with the current through the day, and moving through the array as they did so. Whale sharks then swam against the current in the late afternoon and at night to relocate back to near the presumed tuna spawning site, close to P1, again in the early morning. Rather than being generally associated with platforms, whale sharks were clearly associated with a specific feeding location close to P1. Our results highlight the importance of this small feeding area for whale sharks, which face a high threat level in the region.

Object-based forecasting of heat waves over India: A novel approach - Harvir Singh; Anumeha Dube; Raghavendra Ashrit; Prashant Kumar Srivastava; V S Prasad (Journal of Earth System Science, 2025)

Efficacy of 6-nitrobenzo[d]thiazol-2 Amine Derivative (N3) in Mitigating PTZ-Induced Epileptic Conditions Via Modulation of Inflammatory and Neuroprotective Pathways in-vivo Zebrafish - Karthikeyan Ramamurthy; S. P. Ramya Ranjan Nayak; S. Madesh; Siva Prasad Panda; K. Manikandan; Rajakrishnan Rajagopal; Ahmed Alfarhan; Senthilkumar Palaniappan; Ajay Guru; M. K. Kathiravan; Jesu Arockiaraj (Journal of Neuroimmune Pharmacology, 2025)

Optimized framework for strategic electric vehicle charging station placement and scheduling in distribution systems with renewable energy integration - Jajna Prasad Sahoo; S. Sivasubramani; Parimi Sai Syama Srikar (Swarm and Evolutionary Computation, 2025)

Integrating molecular and phenotypic approaches to assess genetic diversity in Heliconia genotypes - A. Y. Jagtap; P. R. Jadhav; S. A. Safeena; A. U. Solanke; M. C. Pagariya; K. V. Prasad; P. G. Kawar (Genetic Resources and Crop Evolution, 2025)

Identification of novel QTL for bakanae disease resistance in non-basmati indica rice - Malabika Khan; S. Raghu; Rameswar Prasad Sah; T. P. Muhammed Azharudheen; Debashis Moharana; Sasmita Behera; P. Soumya Mohanty; B. Jeevan; Lambodar Behera; B.C. Marndi; Sanghamitra Samantaray; C. Anilkumar (Cereal Research Communications, 2025)

Quantitative Analysis on Expression of Insecticidal Crystal Proteins in Different Plant Parts of BG-II Cotton Hybrids at Various Phenological Stages - Debashis Paul; Rishi Kumar; G. Balasubhramani; Sandeep Bagri; Subhash Chandra; S. Manickam; Satpal Singh; A. H. Prakash; Y. G. Prasad (Agricultural Research, 2025)

Flood Risk Assessment of Bihar State in India Utilizing a Combination of Multi-criteria Analysis (MCA) and Analytical Hierarchy Process (AHP) Using Geospatial Techniques - S. V. Shiva Prasad Sharma; Rupal Budhbhatti; J. Srinivasulu; K. H. V. Durga Rao; Amanpreet Singh; Vipul Anand (Journal of the Indian Society of Remote Sensing, 2025)

Differential response of tolerant and susceptible cultivars of rice against sheath blight pathogen, Rhizoctonia solani Kühn - Puli Sasanka Roy; Vellaichamy Prakasam; Anil S. Kotasthane; Prasanth Pranathi; Chilumula Priyanka; Vadakkenchery Mohanan Manoj; Durbha Sanjeeva Rao; Gouri Sankar Laha; M Srinivas Prasad; Jyothi Badri; Satendra Kumar Mangrauthia; Raman Meenakshi Sundaram (European Journal of Plant Pathology, 2025)

Fidelity of coupled hindcast simulations in representing intraseasonal biases over South Asia - D. Nagarjuna Rao; T. S. Mohan; Ankur Gupta; Kondapalli Niranjan Kumar; Akhilesh Mishra; Imranali M. Momin; Saji Mohandas; Ashis K. Mitra; V. S. Prasad (Climate Dynamics, 2025)

Polyvinyl Chloride and Polypropylene Microplastics Impact Soil Total Antioxidant Capacity and Exoenzyme Secretions - Suryasikha Samal; Pratik Acharya; Rashmi Rekha Samal; Tanushree Moharana; C. S. K. Mishra; Priyadarshini Dash; Satyabrata Brahma; Binayak Prasad Behera; Pragyan Pallavini (Bulletin of Environmental Contamination and Toxicology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Impact of assimilation of DWR reflectivity and radial velocity on simulation of active monsoon precipitation over Indian region - Devajyoti Dutta; Kondapalli Niranjan Kumar; A. Routray; Sukhwinder Kaur; V. S. Prasad (International Journal of Remote Sensing, 2025)

Cultivation of Agardhiella subulata (C. Agardh) Kraft & M. J. Wynne, an unexplored red alga for carrageenan production in India - V. Veeragurunathan; P. Gwen Grace; U. Gurumoorthy; S. Gopala Krishnan; Monica Gajanan Kavale; Ramavatar Meena; Kamalesh Prasad (Aquaculture, 2025)

Intensification of pastoralism ∼ 8 ka: Non-pollen palynomorphs analyses from the Rawatsera palaeolake sediments profile, Central Himalaya, India - Mohammad Firoze Quamar; Nagendra Prasad; Maneesha M. ET; Paulramasamy Morthekai; Anoop K. Singh; Lalit M. Joshi; Bahadur S. Kotlia; Dhruv Sen Singh; Mohammad Javed (Review of Palaeobotany and Palynology, 2025)

Explainable deep learning hybrid modeling framework for total suspended particles concentrations prediction - Sujan Ghimire; Ravinesh C. Deo; Ningbo Jiang; A.A. Masrur Ahmed; Salvin S. Prasad; David Casillas-Pérez; Sancho Salcedo-Sanz; Zaher Mundher Yaseen (Atmospheric Environment, 2025)

Nitrogen ameliorates NaCl toxicity in eggplant seedlings: Role of hydrogen sulphide and sulphur metabolic signaling - Madhulika Singh; Pratibha Singh; S. Shweta; Utkarsha Singh; Sheo Mohan Prasad (Biocatalysis and Agricultural Biotechnology, 2025)

Ceria-based electrospun nanofibers and their widespread applications: A review - Hari Prasad Dasari; Sunaina S. Patil; Riya S. Kamath; Anna M. Kisiela-Czajka (Journal of Environmental Management, 2025)

Flood risk zone mapping and future projections for the Thamirabarani river basin, Southern India: insights from decadal rainfall trends and GIS-based analytical hierarchy process technique - S. Kaliraj; S. Shunmugapriya; C. Lakshumanan; D. Suresh; K. Arun Prasad; Reji Srinivas (Natural Hazards, 2025)

Exploration of piperazine-citral sulfonyl derivatives: antibacterial and in-silico studies against methicillin-resistant Staphylococcus aureus - K. Nirusha; H. S. Nagendra Prasad; T. N. Lohith; P. Saravanan; L. Mallesha; A. P. Anand (Archives of Microbiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Explainable hybrid deep learning framework for enhancing multi-step solar ultraviolet-B radiation predictions - Salvin S. Prasad; Lionel P. Joseph; Sujan Ghimire; Ravinesh C. Deo; Nathan J. Downs; Rajendra Acharya; Zaher M. Yaseen (Atmospheric Environment, 2025)

Construing the resilience to osmotic stress using endophytic fungus in maize (Zea mays L.) - Roopashree Byregowda; S. Rajendra Prasad; M. K. Prasannakumar (Plant Molecular Biology, 2025)

Tembotrione for weed management in kharif maize and its residual effect on succeeding wheat crop in western Indo-gangetic plain of India - Ajay Singh; Mehar Chand; Narender Singh; Govind Prasad; S. S. Punia; Samantha Weber (Phytoparasitica, 2025)

Differential Alterations in the Expression of AMPA Receptor and Its Trafficking Proteins in the Hippocampus Are Associated with Recognition Memory Impairment in the Rotenone-Parkinson’s Disease Mouse Model: Neuroprotective Role of Bacopa monnieri Extract CDRI 08 - Vartika Gupta; S. Prasad (Molecular Neurobiology, 2025)

Computational identification of potential bioactive compounds from Triphala against alcoholic liver injury by targeting alcohol dehydrogenase - Bhavya Banjan; Rajesh Raju; Thottethodi Subrahmanya Keshava Prasad; Chandran S. Abhinand (Molecular Diversity, 2025)

Delignification of Rosa hybrida cv. Rose Sherbet Seed Pericarp Using Deep Eutectic Solvents for Improved Seed Quality Parameters - Debshikha Dutta Roy; S. P. Jeevan Kumar; Ganesh B. Kadam; D. V. S. Raju; Uday Bhaskar Kethineni; K. V. Prasad; Samuel Jacob (Journal of Plant Growth Regulation, 2025)

Efficacy and Economic Viability of Biopolymer-Based Trichoderma as a Sustainable Alternative to Emerging Fungicides for Managing Safflower Soil-Borne Diseases - P. Surendra; Suma Moka; M. Kavya; R. D. Prasad; K. S. V. P. Chandrika; D. Murumkar; Reddy T. Rajeshwar; N. Prabhavathi; C. V. Ambadkar; L. Tandon Ashwarya (Journal of Crop Health, 2025)

Pink Bollworm, Pectinophora gossypiella (Saunders) Infestation Escalates from Incipient to Serious Proportions in North Cotton Zone of India - Rishi Kumar; Debashis Paul; S. K. Sain; Amarpreet Singh; Subhash Chandra; Satpal Singh; Rupinder Singh Cheema; Y. G. Prasad (Journal of Crop Health, 2025)

Development of multistage crop yield estimation model using machine learning and deep learning techniques - K. S. Aravind; Ananta Vashisth; P. Krishnan; Monika Kundu; Shiv Prasad; M. C. Meena; Achal Lama; Pankaj Das; Bappa Das (International Journal of Biometeorology, 2025)

Pollen morphology and variability among Indian cultivars of Chrysanthemum morifolium and comparative analysis with genera of the Asteraceae family - S. A. Patil; M. S. Nimbalkar; M. C. Pagariya; A. J. Kulkarni; P. R. Jadhav; M. P. Mane; A. B. Magdum; T. N. Saha; K. V. Shinde; K. V. Prasad; G. B. Dixit; P. G. Kawar (Genetic Resources and Crop Evolution, 2025)

Potential assessment of Chrysanthemum flowers from various cultivars as sources of natural antioxidants and bioactive compounds - S. A. Patil; A. J. Kulkarni; P. R. Jadhav; R. S. Yadav; M. C. Pagariya; T. N. Saha; T. P. Ahammed Shabeer; D. K. Sarode; A. K. Sharma; K. V. Prasad; P. G. Kawar (Genetic Resources and Crop Evolution, 2025)

Enhanced Red Luminescence in Dy3+/Eu3+ Co-doped Calcium Alumino Borosilicate Glasses for w-LED Applications - Videsh Kumar; Sheetal Kumari; Shristy Malik; Ravita; Tripti Sharma; Aman Prasad; A. S. Rao (Journal of Fluorescence, 2025)

Comparison of the flow characteristics and performance of low-GWP refrigerants in expansion capillary used in air conditioning units - S. H. Barbhuiya; K. Prasad; S. S. H. Kruthiventi (International Journal of Environmental Science and Technology, 2025)

Validation of OceanSat-3 sea surface winds for their utilization in the NCMRWF NWP assimilation systems - Dineshkumar K. Sankhala; S. Indira Rani; D. Srinivas; V.S. Prasad; John P. George (Advances in Space Research, 2025)

Energy Transfer Studies on Red Emitting CaGdSbWO8: Sm3+/Eu3+ Phosphor for w-LEDs and Indoor Plant Growth Lighting System - Jatin Parashar; Gaurank Yadav; Seema; Anu; Aman Prasad; A. S. Rao (Journal of Fluorescence, 2024)

Variability of sea ice concentration over Antarctica during recent decade - S K Sahoo; Imranali M Momin; John P George; V S Prasad (Journal of Earth System Science, 2024)

Comparative evaluation of machine learning algorithms for Coringa Mangroves mapping with satellite imagery and spectral indices - D S Sowjanya; P Rama Chandra Prasad (Journal of Earth System Science, 2024)

Contrasting influence of the 1997 and 2015 El Niño on the Indian Summer Monsoon Rainfall: Role of the Southern Hemisphere - Nimmakanti Mahendra; Nagaraju Chilukoti; Jasti S. Chowdary; Raju Attada; Ravi Kumar Kunchala; Prasad K. Bhaskaran (Global and Planetary Change, 2024)

Retraction notice to “Hydrolysis of biomass using a reusable solid carbon acid catalyst and fermentation of the catalytic hydrolysate to ethanol” [Bioresour. Technol. 188 (2015) 99–102] - Mandavi Goswami; S. Meena; S. Navatha; K.N. Prasanna Rani; Ashok Pandey; Rajeev Kumar Sukumaran; R.B.N. Prasad; B.L.A. Prabhavathi Devi (Bioresource Technology, 2024)

Ensemble versus deterministic lightning forecast performance at a convective scale over Indian region - S. Kiran Prasad; Kumarjit Saha; Gauri Shanker; Ashish Routray; Abhijit Sarkar; V.S. Prasad (Atmospheric Research, 2024)

Comparative assessment of univariate and multivariate spectral modelling techniques for non-destructive estimation of RWC in common beans - S. Kruthika; Apoorva Ashu; T. Basavaraja; Renu Pandey; P. V. Vara Prasad; Bhaskar B. Gaikwad; S. Gurumurthy (Plant Physiology Reports, 2024)

Understanding the nature of blast resistance in combined bacterial leaf blight and blast gene pyramided lines of rice variety tellahamsa - E. Ramprasad; Ch V Durga Rani; C. N. Neeraja; G. Padmavathi; R. Jagadeeshwar; C. Anjali; Priya Thakur; K. N. Yamini; G. S. Laha; M. Srinivas Prasad; Seham Sater Alhelaify; Ohud Muslat Aharthy; et al. (Molecular Biology Reports, 2024)

Unveiling the therapeutic potential of thymol from Nigella sativa L. seed: selective anticancer action against human breast cancer cells (MCF-7) through down-regulation of Cyclin D1 and proliferative cell nuclear antigen (PCNA) expressions - V. Vahitha; Growther Lali; Saradh Prasad; Ponmurugan Karuppiah; Gopalu Karunakaran; Mohamad S. AlSalhi (Molecular Biology Reports, 2024)

Comparative Metabolomics and Network Pharmacology Analysis Reveal Shared Neuroprotective Mechanisms of Bacopa monnieri (L.) Wettst and Centella asiatica (L.) Urb - Sakshi Sanjay Parate; Shubham Sukerndeo Upadhyay; Amrutha S.; Gayathree Karthikkeyan; Ravishankar Pervaje; Chandran S. Abhinand; Prashant Kumar Modi; Thottethodi Subrahmanya Keshava Prasad (Molecular Neurobiology, 2024)

Chromium Stress Induced Alterations in Leaf Physiology and Morphology in Mung Bean (Vigna radiata L.) - Gayatri Mishra; Navneet Yadav; Lekshmi S. Manasa; Durga Prasad Biswal; Gyana Ranjan Rout; Kishore Chandra Panigrahi (Journal of Crop Health, 2024)

Socioeconomic Changes Based Climate Training for Agricultural Application Using Deep Learning Model - M. Sunitha; M. Durairaj; A. Rajalingam; Siti Khalidah Mohd Yusoff; S. Hari Chandra Prasad; S. N. Lakshmi Malluvalasa; Ajmeera Kiran (Remote Sensing in Earth Systems Sciences, 2024)

Hydrochemical investigation and prediction of groundwater quality in a tropical semi-arid region of southern India using machine learning - Girish Gopinath; A.L. Achu; A.R. Sabitha; C.D. Aju; M. Pragath; Govind S. Prasad (Groundwater for Sustainable Development, 2024)

Performance prediction of emulsion treated base layer mixes using indirect tensile strength and resilient modulus test parameters - Jithin Kurian Andrews; Vishnu Radhakrishnan; Reebu Zachariah Koshy; C. S. R. K. Prasad (Innovative Infrastructure Solutions, 2024)

Ecological risk assessment of heavy metals contaminated mining sites of eastern india using soil and moss - Swayam Prakash Nanda; Bibhu Prasad Panda; Kishore C. S. Panigrahi; Abanti Pradhan (Environmental Monitoring and Assessment, 2024)

A GIS-coupled thermal response model for predicting the population growth potential of the red cotton bug, Dysdercus koenigii (Fabricius) (Hemiptera: Pyrrhocoridae) in India under climate change conditions - Vaishnavi A. Nankade; Babasaheb B. Fand; N.V. Lavhe; Shivaji H. Thube; Shailesh P. Gawande; D.T. Nagrale; S.L. Borkar; Tini S. Pillai; Akash Nikoshe; Y.G. Prasad (Journal of Thermal Biology, 2024)

Ellagic Acid Reverses Alterations in the Expression of AMPA Receptor and Its Scaffolding Proteins in the Cerebral Cortex and Memory Decline in STZ-sporadic Alzheimer’ s Disease Mouse Model - Nidhi Anand K. Singh; S. Prasad (Psychopharmacology, 2024)

Improving the skill of medium range ensemble rainfall forecasts over India using MoES grand ensemble (MGE)-part-I - Anumeha Dube; V. Abhijith; Ashu Mamgain; Snehlata Tirkey; Raghavendra Ashrit; V. S. Prasad (Meteorology and Atmospheric Physics, 2024)

Unveiling the Role of Root Exudates in Plant Adaptation to Drought and Heat Stress - S. Kruthika; Apoorva Ashu; Anjali Anand; Kotha Sammi Reddy; P. V. Vara Prasad; S. Gurumurthy (Journal of Crop Health, 2024)

Unveiling the unquestionable dominance of multilocularity in Brassica rapa var. yellow sarson: pioneering advancements in Brassica crop enhancement - Charu Bisht; Birendra Prasad; Usha Pant; S. K. Verma; Amit Kumar Gaur; Shubham Gupta; Neha Panwar; Sivendra Joshi; Yashpal Singh Bisht; Himanshu Prasad; Harsh deep (Genetic Resources and Crop Evolution, 2024)

Assimilation of horizontal line-of-sight winds in National Centre for Medium Range Weather Forecasting – Global Forecast System - Suryakanti Dutta; V S Prasad (Journal of Earth System Science, 2024)

Molecular characterization of begomovirus and DNA satellites associated with mosaic and leaf curl disease of Jamaica cherry (Muntingia calabura) in India: Uncovering a new host for chilli leaf curl India virus - K S Uday Durga Prasad; S S Kavya; Kopparthi Amrutha Valli Sindhura; Mantesh Muttappagol; R Kruthika; C. R. Jahir Basha; K. S. Shankarappa; V. Venkataravanappa; C. N. Lakshminarayana Reddy (VirusDisease, 2024)

Assessment of extreme rainfall events for iFLOWS Mumbai in NCUM regional forecasting system - Mohan S. T; Raghavendra Ashrit; Kondapalli Niranjan Kumar; Upal Saha; D. Nagarjuna Rao; A. Jayakumar; Saji Mohandas; V. S. Prasad (Natural Hazards, 2024)

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

Assessment of universal thermal climate index (UTCI) using the WRF-UCM model over a metropolitan city in India - P. S. Hari Prasad; A. N. V. Satyanarayana (International Journal of Biometeorology, 2024)

Comparing the Efficiency of Sunflower, Marigold and Spinach Plants for Their Phytoextraction Ability of Zinc and Copper in Contaminated Soil - Saubhagya Kumar Samal; Siba Prasad Datta; Debasis Golui; Md Basit Raza; Brahma Swaroop Dwivedi; Mahesh Chand Meena; Mahaveer Nogiya; Mahipal Choudhary; Punyavrat S. Pandey (Agricultural Research, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Developing a differential system for designating the pathotypes of Puccinia hordei causing barley leaf rust in India - Subodh Kumar; S. C. Bhardwaj; O. P. Gangwar; P. Prasad; Charu Lata; Ajit Singh; A. S. Manjul (Journal of Plant Pathology, 2024)

Accelerating vascular graft development: Adipose-derived stem cells and PODS® (Polyhedrin delivery system with tissue-specific growth factors) – Enhanced 3D bioprinting for functional blood vessels - Sushma Priya; Ashleigh S. Boyd; Abril Torres-Bautista; Prasad Sawadkar; Ash Mosahebi; Subha Narayan Rath; Deepak M. Kalaskar (Chemical Engineering Journal, 2024)

Interactive behavior of cadmium ions onto polyethylene microplastics in aquatic system - D. M. Reddy Prasad; B. S. Naveen Prasad; R. Senthilkumar; K. Saravana Kumar; S. Manickkam (International Journal of Environmental Science and Technology, 2024)

Soil Carbon Sequestration and Agronomic Productivity as Influenced by the Long-Term Organic and Inorganic Fertilisation Under the Upland Rice–Wheat System in Vertisols of Central India - Ch. Srinivasarao; Sumanta Kundu; D. P. Dubey; Rajiv Dubey; S. Rakesh; Rattan Lal; P. C. Abhilash; J. V. N. S. Prasad; G. Pratibha; Somasundaram Jayaraman; K. Mrunalini; K. A. Gopinath; et al. (Anthropocene Science, 2024)

Evaluating Short-Range Forecasts of a 12 km Global Ensemble Prediction System and a 4 km Convection-Permitting Regional Ensemble Prediction System - Ashu Mamgain; S. Kiran Prasad; Abhijit Sarkar; Gauri Shanker; Anumeha Dube; Ashis K. Mitra (Pure and Applied Geophysics, 2024)

A signaling network map of Lipoxin (LXA4): an anti-inflammatory molecule - G. P. Suchitha; Rex Devasahayam Arokia Balaya; T. S. Keshava Prasad; Shobha Dagamajalu (Inflammation Research, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Comparative analysis of commercially available kits for optimal DNA extraction from bovine fecal samples - P. S. Seethalakshmi; T. N. Kumaresan; R. U. Vishnu Prasad Nair; Ragothaman Prathiviraj; George Seghal Kiran; Joseph Selvin (Archives of Microbiology, 2024)

Metabolomic profiling of virulent and non-virulent Beauveria bassiana strains: insights into the pathogenicity of Tetranychus truncatus - M. Chaithra; T. Prameeladevi; L. Prasad; Aditi Kundu; S. N. Bhagyasree; Deeba Kamil (Archives of Microbiology, 2024)

Evaluating lightning forecasts of a convective scale ensemble prediction system over India - S. Kiran Prasad; Kumarjit Saha; Gauri Shanker; Abhijit Sarkar; John P. George; V. S. Prasad (Theoretical and Applied Climatology, 2024)

Differential drought responses in deep and shallow-rooted rice genotypes: enzymatic and non-enzymatic insights - Sadiah Shafi; Aaqif Zaffar; Ishrat Riyaz; Asif B. Shikari; S. Najeeb; Sajad Majeed Zargar; M. Djanaguiraman; S. Gurumurthy; P. V. V. Prasad; Parvaze A. Sofi (Plant Physiology Reports, 2024)

Root growth in Orchid Dendrobium cv. Sonia requires shade avoidance response of phytochromes along with regulation of auxin pathway genes - Durga Prasad Biswal; Brajabandhu Pradhan; Sulagna Subhasmita Jena; Sony Kumari; A. Soumya Rao; Nihar Ranjan Nayak; Madhusmita Panigrahy; Kishore C. S. Panigrahi (Plant Physiology Reports, 2024)
Orchid Dendrobium Sonia has wide demand in floral market throughout the world due to its vibrant coloured flowers, flowering recurrence and dense inflorescence. Effects of different monochromatic lights (red, far-red, blue, white) on different developmental and growth responses such as seed gemination, shoot and root growth, chlorophyll and carotenoid accumulation were studied in Dendrobium Sonia. Asymbiotic seed germination was highest under blue or white light (80%, p < 0.001) and least under far-red (55%, p < 0.001) suggesting that it could either be controlled by an exceptional novel function of Cryptochrome 1 or the blue wavelengths perceived by PHYA or PHYB in Dendrobium Sonia. All analyses were done in 6-months-old plants till 1 year of age. Shoot length increased significantly in white or red light (3.7-fold, 3.5-fold respectively) while was least under far-red (decreased by 1.6-fold) indicating the major regulatory role of PHYB for shoot growth. Root growth in red light in Dendrobium Sonia was more similar to hypocotyl adventitious root (HAR) formation considering the PHYB transcript expression. We suggest that the root growth (HAR) under red light in Dendrobium Sonia is partly attributed to PHYB , negatively regulated with HY5 and positively associated with auxin biosynthesis and accumulation gene BABY BOOM (BBM2) and efflux carriers such as LIKE AUXIN RESISTANT 2 and 3 ( LAX2, LAX3) . Highest chlorophyll content under far-red and blue might be a hyper-response of shade avoidance response under far-red light in Dendrobium Sonia . Taxonomic tree analysis finds Dendrobium Sonia closer to Phalaenopsis and Dendrobium catenatum . The three phytochromes and one cryptochrome sequences were similar to PHYA, PHYB, PHYC and CRY1 respectively. CRY1 was retrieved with one more isoform CRY1_X2, with all these sequences more similar to those of Oryza sativa . Further study can clarify the indicating reason of a probable gene loss which is evident from the absence of any sequence similar to CRY2 in root RNA isolates of Dendrobium Sonia.

Racial diversity in Uromyces appendiculatus causing French bean rust - Banita Devi; Gurvinder Singh; Satish K. Gupta; Pramod Prasad; S. C. Bhardwaj; Vinaykumar Rachappanavar (Indian Phytopathology, 2024)

Overcoming physiological dormancy in common buckwheat (Fagopyrum esculentum Moench) - Vishwanath Rohidas Yalamalle; Vijay Dunna; Gautam Chawla; Gyan Prakash Mishra; Vijayakumar H P.; Dilshad Ahmad; S. K. Lal; Dinesh Chandra Joshi; Rajendra Prasad Meena (Genetic Resources and Crop Evolution, 2024)

Depth averaged velocity and stage-discharge relationships in compound channels with composite roughness - Ebissa Gadissa Kedir; C. S. P. Ojha; K. S. Hari Prasad (Environmental Fluid Mechanics, 2024)

Variability of low-level jet over the Arabian Sea and its association with Indian summer monsoon rainfall - Archana Sagalgile; P. V. S. Raju; Akshay Kulkarni; Jagdish Prasad; V. B. Rao; Suvarna Fadnavis (Climate Dynamics, 2024)

Establishment of morphological markers to differentiate male and female plants in Ailanthus excelsa Roxb. using multiple logistic regression - Asmita Singh; Kumar Sambhav Verma; Mahesh Kumar Saini; Jagdish Prasad; Divyanshu Singh; S L Kothari; Aditi Kothari-Chhajer; Uttar Kumar Tomar; Vinod Singh Gour (Flora, 2024)

Retrieval of high-resolution aerosol optical depth (AOD) using Landsat 8 imageries over different LULC classes over a city along Indo-Gangetic Plain, India - Rohit Kumar Singh; A. N. V. Satyanarayana; P. S. Hari Prasad (Environmental Monitoring and Assessment, 2024)

Probing calmodulin–NO synthase interactions via site-specific infrared spectroscopy: an introductory investigation - Swapnil Singh; Yadav Prasad Gyawali; Ting Jiang; Gregory S. Bukowski; Huayu Zheng; Haikun Zhang; Rebecca Owopetu; Megan C. Thielges; Changjian Feng (JBIC Journal of Biological Inorganic Chemistry, 2024)

Augmenting abiotic stress tolerance and root architecture: The function of phytohormone-producing PGPR and their interaction with nanoparticles - Anuj Ranjan; Vishnu D. Rajput; Evgeniya V. Prazdnova; Manisha Gurnani; Shikha Sharma; Pallavi Bhardwaj; Sudhir S. Shende; Saglara S. Mandzhieva; Svetlana Sushkova; Tatiana Minkina; Abhishek Chauhan; Tanu Jindal; et al. (South African Journal of Botany, 2024)

Certified reference material (CRM) of tea powder (BARC - D3201) for K, Ca, P, Mg, Mn, Al, Fe, Ba, Zn, Cu, Sr, Pb, As, Cd, and Hg: Method validation and its production - Lori Rastogi; A. Durga Prasad; D. Sai Krishna; S. Yadlapalli; K. Dash (Food Control, 2024)

Identification of adult plant rust resistance genes in some pre and post-green revolution Indian bread-wheat varieties - Hanif Khan; S. C. Bhardwaj; O. P. Gangwar; Pramod Prasad; Subodh Kumar; G. P. Singh (Phytoparasitica, 2024)

Integrated Continuous Process Design for Crystallisation, Spherical Agglomeration, and Filtration of Lovastatin - Cameron J. Brown; John McGinty; Muhammad T. Islam; Nazer Rajoub; Omid Arjmandi-Tash; Sara Ottoboni; Muhid Shahid; Stephanie J. Urwin; Ye Seol Lee; Magdalene W. S. Chong; Foteini Papathanasiou; Aruna S. Prakash; et al. (Journal of Pharmaceutical Innovation, 2024)
Purpose This work seeks to improve the particle processability of needle-like lovastatin crystals and develop a small-footprint continuous MicroFactory for its production. Methods General conditions for optimal spherical agglomeration of lovastatin crystals and subsequent product isolation are developed, first as batch processes, and then transferred to continuous MicroFactory operation. Results Methyl isobutyl ketone is a suitable bridging liquid for the spherical agglomeration of lovastatin. Practical challenges including coupling unit operations and solvent systems; mismatched flow rates and inconsistent suspension solid loading were resolved. The successful continuous production of lovastatin spherical agglomerates (D 50 = 336 µm) was achieved. Spherical agglomeration increased the density of the bulk lovastatin powder and improved product flowability from poor to good, whilst maintaining lovastatin tablet performance. Conclusion A continuous, integrated MicroFactory for the crystallisation, spherical agglomeration, and filtration of lovastatin is presented with improved product particle processability. Up to 16,800 doses of lovastatin (60 mg) can be produced per day using a footprint of 23 m 2 .

Chalcone-based Turn-Off Chemosensor for Selective and Susceptible Detection of Fe2+ Ions: Spectroscopic and DFT Investigations - Bhavya Nelligere Revanna; Vinuta Kamat; Ananda Swamynayaka; Keshav Kumar Harish; Keerthikumara Venkatesha; Mahendra Madegowda; Boja Poojary; Sanjay S. Majani; Shiva Prasad Kollur (Journal of Fluorescence, 2024)

The Emerging Role of Toll-Like Receptor-Mediated Neuroinflammatory Signals in Psychiatric Disorders and Acquired Epilepsy - Anubha Chaudhary; Parul Mehra; Anand K Keshri; Suraj S Rawat; Amit Mishra; Amit Prasad (Molecular Neurobiology, 2024)

Assessment of genetic diversity in androgenic-based doubled haploid-derived improved restorer lines of indica rice - Sudhansu Sekhar Bhuyan; Durga Prasad Barik; Byomkesh Dash; Prachitara Rout; Snigdha Samir Pattnaik; Ramlakhan Verma; Jawahar Lal Katara; C. Parameswaran; B. N. Devanna; Raj Kishore Sahoo; Anindita Mishra; S. Sabarinathan; et al. (Journal of Crop Science and Biotechnology, 2024)

Salmonella enterica serovars linked with poultry in India: antibiotic resistance profiles and carriage of virulence genes - Dengam Geyi; Prasad Thomas; Lakshmi Prakasan; Yancy M. Issac; Arvinderpal Singh; Sonu S. Nair; Maninder Singh; Sophia Inbaraj; Suman Kumar; Asok K. Mariappan; Abhishek; Vinod K. Chaturvedi; et al. (Brazilian Journal of Microbiology, 2024)

Climate-smart agriculture (CSA) adaptation, adaptation determinants and extension services synergies: a systematic review - Bhavani Prasad Thottadi; S. P. Singh (Mitigation and Adaptation Strategies for Global Change, 2024)

Syngas and hydrogen production from co-gasification of rice husk biomass and plastic waste mixture using Aspen Plus - Roshan R. Bhurse; Prabuddha P. Gope; Himanshu Yadav; Kartik R. Prasad; Ashish S. Chaurasia (Environment, Development and Sustainability, 2024)

Meta-analysis of the serum/plasma proteome identifies significant associations between COVID-19 with Alzheimer’s/Parkinson’s diseases - Althaf Mahin; Sreelakshmi Pathappillil Soman; Prashant Kumar Modi; Rajesh Raju; Thottethodi Subrahmanya Keshava Prasad; Chandran S. Abhinand (Journal of NeuroVirology, 2024)

Development of Novel Sutureless Balloon Expandable Fetal Heart Valve Device Using Absorbable Polycaprolactone Leaflets - Sanchita S. Bhat; Hieu T. Bui; Anna Farnan; Katherine Vietmeyer; Aimee K. Armstrong; Christopher K. Breuer; Lakshmi Prasad Dasi (Annals of Biomedical Engineering, 2024)

Impact assessment of COSMIC-2 bending angle in the GSI 4D-EnVar analysis scheme operational at NCMRWF - Suryakanti Dutta; V. S. Prasad (International Journal of Remote Sensing, 2024)

Simple and Cost-effective Synthesis of a Rare-earth Free Long Afterglow Phosphor for Dark Visual Markings - K. A. K. Durga Prasad; S. Puranjay; M. Rakshita; Aachal A. Sharma; Payal P. Pradhan; K. Uday Kumar; R. Rakesh Kumar; D. Haranath (Journal of Fluorescence, 2024)

Development of a novel visual assay for ultrasensitive detection of Listeria monocytogenes in milk and chicken meat harnessing helix loop-mediated isothermal amplification (HAMP) - M.C.B. Prasad; A.A.P. Milton; V.K. Menon; K. Srinivas; D. Bhargavi; S. Das; S. Ghatak; S.L. Vineesha; B. Sunil; C. Latha; P.M. Priya; N. Thomas (Food Control, 2024)

In vitro virulotyping, antifungal susceptibility testing and DNA fingerprinting of Microsporum canis strains of canine and feline origin - Jitendra Kumar Bagra; Sonu S. Nair; V. Athira; M. Suman Kumar; Manish Kumar; Prasad Thomas; Bablu Kumar; V.K. Chaturvedi; Premanshu Dandapat; Abhishek (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Native bio-control agents from the rice fields of Telangana, India: characterization and unveiling the potential against stem rot and false smut diseases of rice - Sowmya Vanama; N. S. Raja Gopalan; Maruthi Pesari; M. Baskar; Uma Devi Gali; D. Ladha Lakshmi; P. Koteshwar; G. Jesudasu; Santosha Rathod; M. Srinivas Prasad; Rajanikanth Panuganti; R. M. Sundaram; et al. (World Journal of Microbiology and Biotechnology, 2024)

Simulations of North Indian Winter Climate Using Non-hydrostatic RegCM - M. M. Karadan; P. V. S. Raju; D. Hari Prasad (Pure and Applied Geophysics, 2024)

The MSMEG_1586 of M. smegmatis Is a Penicillin-Interactive Enzyme That Can Potentially Hydrolyse Aztreonam and Cephalosporins - Aditya Prasad Panda; Satya Deo Pandey; Diamond Jain; Anindya S. Ghosh (Current Microbiology, 2024)

Study pre- and post-monsoon storms over NIO region using high resolution IMDAA reanalysis dataset - A. Routray; Devajyoti Dutta; Srinivas Desamsetti; Shivaji Singh Patel; John P. George; V. S. Prasad (Climate Dynamics, 2024)

Transformation of brackish water Reverse Osmosis membranes to nanofiltration & ultrafiltration membranes by NaOCl treatment: Kinetic and characterization studies - Srija Madduri; Hemant S. Sodaye; A.K. Debnath; A.K. Adak; T.L. Prasad (Journal of Water Process Engineering, 2023)

Nutritional and pharmacological properties of palmyra palm - A.R. Basava Prasad; S. Vignesh; Arunkumar Elumalai; Arunkumar Anandharaj; D.V. Chidanand; N. Baskaran (Food and Humanity, 2023)

The amino acid region from 448-517 of CAMTA3 transcription factor containing a part of the TIG domain represses the N-terminal repression module function - Amira A. E. Abdel-Hameed; Kasavajhala V. S. K. Prasad; Anireddy S. N. Reddy (Physiology and Molecular Biology of Plants, 2023)

Improvement of floricultural traits in ornamental crops using genome editing tools - Pritam Ramesh Jadhav; Supriya Babasaheb Aglawe; D. Harish; Yogesh S. Wagh; Kalyani M. Barbadikar; P. Naveen Kumar; Prashant G. Kawar; K. V. Prasad; S. P. Jeevan Kumar (Journal of Plant Biochemistry and Biotechnology, 2023)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Phosphorus Solubilizing Microbes (PSM): Biological tool to combat salinity stress in crops - Meenu Thampi; N. D. Dhanraj; Aswathi Prasad; G. Ganga; M. S. Jisha (Symbiosis, 2023)

An Automatic Detection of Citrus Fruits and Leaves Diseases Using Enhanced Convolutional Neural Network - Rajveer Shastri; Abhay Chaturvedi; B. Mouleswararao; S. Varalakshmi; G. N. R. Prasad; Mylavarapu Kalyan Ram (Remote Sensing in Earth Systems Sciences, 2023)

First Seroepidemiological Investigation of Hepatitis E Virus Infection in Backyard Pigs from Northeastern India: Prevalence and Associated Risk Factors - A. A. P. Milton; Samir Das; S. Ghatak; K. Srinivas; M. Angappan; M. C. B. Prasad; L. Wahlang; G. Bhuvana Priya; Sabia Khan; Blessa Sailo; Lalhruaipuii; Mahak Singh; et al. (Food and Environmental Virology, 2023)

Export of particulate organic carbon and nitrogen to the northern Indian Ocean by the monsoonal rivers of India - M. S. Krishna; M. H. K. Prasad; S. A. Naidu; G. Srikanth; N. P. C. Reddy; N. S. Sarma (Environmental Science and Pollution Research, 2023)

Decoding the enigma of 100-year record-breaking rainfall over Tamil Nadu using wavelet analysis - Asok Raja S K; Durga Prasad Panday; Manish Kumar (Groundwater for Sustainable Development, 2023)

Measurement of radon concentration in soil gas and radon exhalation rate from soil samples along and across the Main Central Thrust of Garhwal Himalaya, India - Krishna Pal Singh; Subhash Chandra; Pooja Panwar; Abhishek Joshi; Ganesh Prasad; G. S. Gusain; R. C. Ramola (Environmental Geochemistry and Health, 2023)

The first record of calcitarchs from the Takche Formation (Ordovician–Silurian), Himalaya (India) - Olev Vinn; Ravi S. Chaubey; Birendra P. Singh; Om N. Bhargava; Subhay K. Prasad (Proceedings of the Geologists' Association, 2023)

Effect of cryopreservation and capacitation on expression patterns of ATP synthesis associated genes in bubaline spermatozoa - B.V.S. Sai Kiran; C.H. Srinivasa Prasad; B.R. Naik; K. Aswani Kumar; S. Lavanya; Tej Nikhil Kumar; Iqbal Hyder (Journal of Thermal Biology, 2023)

Assessment of Outdoor Thermal Comfort Using Landsat 8 Imageries with Machine Learning Tools over a Metropolitan City of India - P. S. Hari Prasad; A. N. V. Satyanarayana (Pure and Applied Geophysics, 2023)

Between versus within: Comparative analysis reveals significant differences among survival, regeneration and growth in explants of Gracilaria corticata var. cylindrica treated with two commercial Sargassum-derived extracts - Keval Joshi; Mukesh Baraiya; Kinjal Moradiya; Pankaj S. Dawange; Santlal Jaiswar; Kamalesh Prasad; Vaibhav A. Mantri (Journal of Applied Phycology, 2023)

Polyphenol-based targeted therapy for oral submucous fibrosis - Chetan Hasmukh Mehta; Shivangi Paliwal; Manjunatha S. Muttigi; Raviraja N. Seetharam; Alevoor Srinivas Bharath Prasad; Yogendra Nayak; Shruthi Acharya; Usha Yogendra Nayak (Inflammopharmacology, 2023)
Oral submucous fibrosis (OSF) is a chronic, progressive, and precancerous condition mainly caused by chewing areca nut. Currently, OSF therapy includes intralesional injection of corticosteroids with limited therapeutic success in disease management. Therefore, a combined approach of in silico , in vitro and in vivo drug development can be helpful. Polyphenols are relatively safer than other synthetic counterparts. We used selected polyphenols to shortlist the most suitable compound by in silico tools. Based on the in silico results, epigallocatechin-3-gallate (EGCG), quercetin (QUR), resveratrol, and curcumin had higher affinity and stability with the selected protein targets, transforming growth factor beta-1 (TGF-β1), and lysyl oxidase (LOX). The efficacy of selected polyphenols was studied in primary buccal mucosal fibroblasts followed by in vivo areca nut extract induced rat OSF model. In in vitro studies, the induced fibroblast cells were treated with EGCG and QUR. EGCG was safer at higher concentrations and more efficient in reducing TGF-β1, collagen type-1A2 and type-3A1 mRNA expression than QUR. In vivo studies confirmed that the EGCG hydrogel was efficient in improving the disease conditions compared to the standard treatment betamethasone injection with significant reduction in TGF-β1 and collagen concentrations with increase in mouth opening. EGCG can be considered as a potential, safer and efficient phytomolecule for OSF therapy and its mucoadhesive topical formulation help in the improvement of patient compliance without any side effects. Graphical abstract Highlights Potential polyphenols were shortlisted to treat oral submucous fibrosis (OSF) using in silico tools Epigallocatechin 3-gallate (EGCG) significantly reduced TGF-β1 and collagen both in vitro and in vivo EGCG hydrogel enhanced antioxidant defense, modulated inflammation by reducing TGF-β1 and improved mouth opening in OSF rat model.

Dryspells and Minimum Air Temperatures Influence Rice Yields and their Forecast Uncertainties in Rainfed Systems - Abhijeet Abhishek; Mantha S. Phanikumar; Alicia Sendrowski; Konstantinos M. Andreadis; Mahya G.Z. Hashemi; Susantha Jayasinghe; P.V. Vara Prasad; Roberts J. Brent; Narendra N. Das (Agricultural and Forest Meteorology, 2023)

The characterization of chitinolytic soil bacterial isolates for their antagonistic activity against root knot nematode Meloidogyne incognita: an effort towards developing ‘green’ nematicidal agents - Prasad Pawar; Jayraj Doshi; S. G. Patil; Prajakta Dandekar; K. Poornima (BioControl, 2023)

Gloriosa simplex L. (Colchicaceae): a new distributional record for India - S. P. Panda; Titir Saha; Sattom Dasgupta; R. D. Barman; S. K. Arjun; Ravi Prasad; Devendra Singh (Vegetos, 2023)

Unraveling the diversity and functions of sugar transporters for sustainable management of wheat rust - Charu Lata; Anshul Sharma Manjul; Pramod Prasad; O. P. Gangwar; Sneha Adhikari; Sonu; Subodh Kumar; S. C. Bhardwaj; Gyanendra Singh; Mahesh Kumar Samota; Mukesh Choudhary; Abhishek Bohra; et al. (Functional & Integrative Genomics, 2023)

Quantitative determination of heavy metal contaminants in edible soft tissue of clams, mussels, and oysters - Tibor Pasinszki; Shilvee S. Prasad; Melinda Krebsz (Environmental Monitoring and Assessment, 2023)

Glacier Volume Estimation Using Laminar-Flow and Volume–Area Scaling Techniques in the Chenab Basin - J. S. Gopika; Anil V. Kulkarni; Veena Prasad (Journal of the Indian Society of Remote Sensing, 2023)

Mito-TEMPO mitigates 5-fluorouracil-induced intestinal injury via attenuating mitochondrial oxidative stress, inflammation, and apoptosis: an in vivo study - Prasad Kisan Tambe; H. S. Qsee; Sanjay Bharati (Inflammopharmacology, 2023)
Background Recent evidences highlight role of mitochondria in the development of 5-fluorouracil (5-FU)-induced intestinal toxicity. Mitochondria-targeted antioxidants are well-known for their protective effects in mitochondrial oxidative stress- mediated diseases. In the present study, we investigated protective effect of Mito-TEMPO in 5-FU-induced intestinal toxicity. Methods Mito-TEMPO (0.1 mg/kg b.w.) was administered intraperitoneally to male BALB/c mice for 7 days, followed by co-administration of 5-FU for next 4 days (intraperitoneal 12 mg/kg b.w.). Protective effect of Mito-TEMPO on intestinal toxicity was assessed in terms of histopathological alterations, modulation in inflammatory markers, apoptotic cell death, expression of 8-OhDG, mitochondrial functional status and oxidative stress. Results 5-FU administered animals showed altered intestinal histoarchitecture wherein a shortening and atrophy of the villi was observed. The crypts were disorganized and inflammatory cell infiltration was noted. Mito-TEMPO pre-protected animals demonstrated improved histoarchitecture with normalization of villus height, better organized crypts and reduced inflammatory cell infiltration. The inflammatory markers and myeloperoxidase activity were normalized in mito-TEMPO protected group. A significant reduction in intestinal apoptotic cell death and expression of 8-OhDG was also observed in mito-TEMPO group as compared to 5-FU group. Further, mtROS, mtLPO and mitochondrial antioxidant defense status were improved by mito-TEMPO. Conclusion Mito-TEMPO exerted significant protective effect against 5-FU-induced intestinal toxicity. Therefore, it may be used as an adjuvant in 5-FU chemotherapy.

Can adoption of climate resilient management practices achieve carbon neutrality in traditional green revolution states of Punjab and Haryana? - J.V.N.S. Prasad; V. Girija Veni; Ch. Srinivasarao; Sumanta Kundu; B. Ramakrishna; K. Sammi Reddy; Rajbir Singh; S.K. Singh; Ashish Santosh Murai; P.P. Rohilla; Gurpreet Singh Makkar; Vipan Kumar Rampal; et al. (Journal of Environmental Management, 2023)

Assessing impact of land-use changes on land surface temperature and modelling future scenarios of Surat, India - S. R. S. Vasanthawada; H. Puppala; P. R. C. Prasad (International Journal of Environmental Science and Technology, 2023)

A systematic antidiarrhoeal evaluation of a vegetable root Begonia roxburghii and its marker flavonoids against nonpathogenic and pathogenic diarrhoea - Rupali S. Prasad; Nikhil Y. Yenorkar; Suhas R. Dhaswadikar; Saurabh K. Sinha; Nitish Rai; Pravesh Sharma; Onkar Kulkarni; Neeraj Kumar; Mahaveer Dhobi; Damiki Laloo; Shailendra S. Gurav; Prakash R. Itankar; et al. (Food Bioscience, 2023)

Electrochemical conversion of biomass-derived aldehydes into fine chemicals and hydrogen: A review - Jayaraman Theerthagiri; K. Karuppasamy; Juhyeon Park; Nihila Rahamathulla; M. L. Aruna Kumari; Marciélli K. R. Souza; Eduardo S. F. Cardoso; Arun Prasad Murthy; Gilberto Maia; Hyun-Seok Kim; Myong Yong Choi (Environmental Chemistry Letters, 2023)

Management of yellow stem borer in a paddy ecosystem using SPLAT mating disruption techniques - P. R. Badari Prasad; A. G. Sreenivas; G. S. Guruprasad; J. R. Divan; R. Harischandra Naik; M. Veeranagouda; J. Ashoka (Cereal Research Communications, 2023)

Evaluation of particle pollution influence on loss of solar power generation between commercial and background areas in Lucknow, India - Hari Om Prasad; S. S. Kalikinkar Mahanta; Sreekanth Bojjagani (Environment, Development and Sustainability, 2023)

Rise and fall of SARS-CoV-2 variants in Rotterdam: Comparison of wastewater and clinical surveillance - Ray W. Izquierdo-Lara; Leo Heijnen; Bas B. Oude Munnink; Claudia M.E. Schapendonk; Goffe Elsinga; Jeroen Langeveld; Johan Post; Divyae K. Prasad; Christian Carrizosa; Frederic Been; Janko van Beek; Remy Schilperoort; et al. (Science of The Total Environment, 2023)

Probable maximum precipitation analysis of high rainfall regions in India - Durga Prasad Panday; Akansha Singh; Siddhant; Aditya Ketu; Raja; Asok Raja S K; Manish Kumar (Groundwater for Sustainable Development, 2023)

Annual and seasonal trends in actual evapotranspiration over different meteorological sub-divisions in India using satellite-based data - Raghavendra Prasad K; Kantha Rao Bhimala; G. K. Patra; Himesh S; Sheshakumar Goroshi (Theoretical and Applied Climatology, 2023)

Yield, water, and carbon footprint of rainfed rice production under the lens of mid-century climate change: a case study in the eastern coastal agro-climatic zone, Odisha, India - Soumya Sucharita Behera; C. S. P. Ojha; K. S. Hari Prasad; Sonam Sandeep Dash (Environmental Monitoring and Assessment, 2023)

PGPR: the treasure of multifarious beneficial microorganisms for nutrient mobilization, pest biocontrol and plant growth promotion in field crops - D. T. Nagrale; A. Chaurasia; S. Kumar; S. P. Gawande; N. S. Hiremani; Raja Shankar; N. Gokte-Narkhedkar; Renu; Y. G. Prasad (World Journal of Microbiology and Biotechnology, 2023)

Microstructural and Cantabro loss studies on self-healing concrete with crushed stone sand, Bacillus subtilis bacteria and calcium lactate - C. Venkata Siva Rama Prasad; T. V. S. Vara Lakshmi; G. Sree Lakshmi Devi (Innovative Infrastructure Solutions, 2023)

Pharmacokinetics and tissue distribution of florfenicol and florfenicol amine in snubnose pompano (Trachinotus blochii) following oral administration - T. G. Sumithra; S. R. Krupesha Sharma; Vishnu Prasad; Ambarish P. Gop; Suja Gangadharan; S. Gayathri; Antony Ambrose; R. Rajisha; S. K. Panda; M. K. Anil; P. K. Patil (Fish Physiology and Biochemistry, 2023)

Extraction and mapping of shoreline changes along the Visakhapatnam–Kakinada coast using satellite imageries - B Gireesh; P S N Acharyulu; Venkateswarlu CH; B Sivaiah; K Venkateswararao; K V S R Prasad; C V Naidu (Journal of Earth System Science, 2023)

Management of rice blast with modern combination fungicides against Magnaporthe oryzae - Emani Rajeswari; M. Srinivas Prasad; B. VidyaSagar; M. S. Madhav; B. Teja Bhushan; Y. Roseswara Rao (Vegetos, 2023)

An eco-sustainable approach towards heavy metals remediation by mangroves from the coastal environment: A critical review - Krishna Kumar Yadav; Neha Gupta; Shiv Prasad; Lal Chand Malav; Javed Khan Bhutto; Akil Ahmad; Amel Gacem; Byong-Hun Jeon; Ahmed M. Fallatah; Basim H. Asghar; Marina M.S. Cabral-Pinto; Nasser S. Awwad; et al. (Marine Pollution Bulletin, 2023)

A mini review on plant-mediated zinc oxide nanoparticles and their antibacterial potency - A. Kavitha; A. Doss; R.P. Praveen Pole; T.P. Kumari Pushpa Rani; Ram Prasad; S. Satheesh (Biocatalysis and Agricultural Biotechnology, 2023)

Efficacy and physical modes of EBI and strobilurin fungicides in managing French bean rust (Uromyces appendiculatus) - Gurvinder Singh; Banita Devi; S. K. Gupta; Pramod Prasad (Indian Phytopathology, 2023)

Leaf rust responsive miRNA and their target genes in wheat - Neelu Jain; Aalok Shiv; Nivedita Sinha; Harikrishna; P. K. Singh; Pramod Prasad; H. S. Balyan; P. K. Gupta (Functional & Integrative Genomics, 2023)

Investigation of heavy metal contamination and associated health risks in groundwater sources of southwestern Punjab, India - Pargin Bangotra; Rajan Jakhu; Mukesh Prasad; R. S. Aswal; Ansumali Ashish; Zainab Mushtaq; Rohit Mehra (Environmental Monitoring and Assessment, 2023)

Swell wave propagation and its characteristics while approaching the Indian Coast - S. Sreelakshmi; Prasad K. Bhaskaran (Climate Dynamics, 2023)

Compendious Index for Drillability: a rapid tool to assess drill penetration rate and bit life for rock engineering applications - B. N. V. Siva Prasad; V. M. S. R. Murthy; Sripad R. Naik (Bulletin of Engineering Geology and the Environment, 2023)

Dermatophytosis caused by Nannizzia nana (Microsporum nanum): a comprehensive review on a novel pathogen - Sonu S. Nair; Abhishek; Shubham Saini; Chandana M.S.; Khan Sharun; Athira V.; Prasad Thomas; Bablu Kumar; V. K. Chaturvedi (Brazilian Journal of Microbiology, 2023)

Comparison of digestible and available phosphorus release values for a novel phytase determined with fecal phosphorus digestibility and bone mineralization in weaner pigs - H. Zhai; J. Zhang; Z. Wang; S. Wang; S. Prasad; K. Stamatopoulos; S. Duval (Animal Feed Science and Technology, 2023)

Saltatory rolling circle amplification assay for simple and visual detection of Listeria monocytogenes in milk and milk products - M.C.B. Prasad; A.A.P. Milton; V.K. Menon; S. Ghatak; K. Srinivas; K.M. Momin; S.L. Vineesha; S. Das; A. Sen; C. Latha; B. Sunil; D. Jolly (International Dairy Journal, 2023)

Impact of lighter alkanes on the formation and dissociation kinetics of methane hydrate in oil-in-water dispersions relevant for flow assurance - Siddhant Kumar Prasad; Jitendra S. Sangwai (Fuel, 2023)

Diffusion mechanism and electrochemical investigation of 1T phase Al–MoS2@rGO nano-composite as a high-performance anode for sodium-ion batteries - Manish Kr. Singh; Jayashree Pati; Deepak Seth; Jagdees Prasad; Manish Agarwal; M. Ali Haider; Jeng-Kuei Chang; Rajendra S. Dhaka (Chemical Engineering Journal, 2023)

Transcriptomic and physiological responses of Rhizobium sp. IRBG74 to Sesbania cannabina and rice (Oryza sativa L) rhizosphere - Laura M. Ketelboeter; Alex Gordon; Shashini U. Welmillage; Virinchipuram S. Sreevidya; Oleg Paliy; Prasad Gyaneshwar (Plant and Soil, 2023)

Improving blast resistance of maintainer line DRR 9B by transferring broad spectrum resistance gene Pi2 by marker assisted selection in rice - Arun Kumar Singh; Revathi Ponnuswamy; M. Srinivas Prasad; R. M. Sundaram; A. S. Hari Prasad; P. Senguttuvel; K. B. Kempa Raju; K. Sruthi (Physiology and Molecular Biology of Plants, 2023)

Identifying Rip Channels Along RK Beach, Visakhapatnam Using Video and Satellite Imagery Analysis - Sivaiah Borra; T. M. Balakrishnan Nair; Sudheer Jospeh; Surisetty V. V. Arun Kumar; T. Sridevi; R. Harikumar; K. Srinivas; G. Yatin; B. Gireesh; K. Venkateswararao; Ch. Venkateswarlu; A. Anjaneyulu; et al. (Journal of the Indian Society of Remote Sensing, 2023)

SAtellite-based Marine Process Understanding, Development, Research and Applications for Blue Economy (SAMUDRA): A Technology Demonstration Program in the Bay of Bengal - Rashmi Sharma; Neeraj Agarwal; Ratheesh R; Surisetty VVArun Kumar; A. D. Rao; KVSR Prasad; Jaya Kumar Seelam; R. Mani Murali; V. Suneel; Surendra Singh K; R. K. Sarangi; Soba J. Kizhakudan; et al. (Journal of the Indian Society of Remote Sensing, 2023)

Efficacy of novel insecticides and their combinations against pink bollworm, Pectinophora gossypiella (Saunders) (Lepidoptera: Gelechiidae) in cotton - V. Chinna Babu Naik; Mohan K. Narode; Sujit Kumbhare; Dilip Shriram Ghongade; T. N. Madhu; J. S. V. Murthy; Nandini Gokte-Narkhedkar; Y. G. Prasad (International Journal of Tropical Insect Science, 2023)

Prediction capability of the MCDA-AHP model in wildfire risk zonation of a protected area in the Southern Western Ghats - Salma; S. Nikhil; Jean Homian Danumah; Megha K. Prasad; Neha Nazar; Sunil Saha; Pratheesh C. Mammen; R. S. Ajin (Environmental Sustainability, 2023)

Discovery of Molecular Networks of Neuroprotection Conferred by Brahmi Extract in Aβ42-Induced Toxicity Model of Drosophila melanogaster Using a Quantitative Proteomic Approach - Sayali Chandrashekhar Deolankar; Mohd Altaf Najar; Poornima Ramesh; Anagha Kanichery; Avinash K. Kudva; Shamprasad Varija Raghu; T. S. Keshava Prasad (Molecular Neurobiology, 2023)

Modal shift by using ordinal regression model in terms of bus rapid transit system introduction - Khalil Ahmad Kakar; C. S. R. K Prasad (Innovative Infrastructure Solutions, 2023)

Comprehensive Proteomic Analysis of Brucella melitensis ATCC23457 Strain Reveals Metabolic Adaptations in Response to Nutrient Stress - Aliabbas A. Husain; Sneha M. Pinto; Nupur Agarwal; Santosh K. Behera; Payal R. Khulkhule; Nidhi M. Bhartiya; Yashwanth Subbannayya; T. S. Keshava Prasad; Lokendra R. Singh; Hatim F. Daginawala; Rajpal S. Kashyap (Current Microbiology, 2023)

Seasonal dynamics and polyphenism of butterfly communities in the coastal plains of central Western Ghats, India - Deepak Naik; R Shyama Prasad Rao; Krushnamegh Kunte; Mohammed S Mustak (Journal of Biosciences, 2022)

Probabilistic forecasting of Super Cyclone ‘Amphan’ using NCMRWF global and regional ensemble prediction systems - Abhijit Sarkar; S Kiran Prasad; Ashu Mamgain; Anumeha Dube; Paromita Chakraborty; Sushant Kumar; Sagili Karunasagar; Mohana S Thota; Gauri Shanker; Raghavendra Ashrit; A K Mitra (Journal of Earth System Science, 2022)

Occurrence of Banana bract mosaic virus on Musa ornata Roxb based hybrids in India - S. Madhavan; V. Balasubramanian; D. Ramajayam; D. V. S. Raju; K. V. Prasad; R. Selvarajan (VirusDisease, 2022)

Amyloid $$\upbeta$$ (1–42) peptide impairs mitochondrial respiration in primary human brain microvascular endothelial cells: impact of dysglycemia and pre-senescence - Siva S. V. P. Sakamuri; Venkata N. Sure; Xiaoying Wang; Gregory Bix; Vivian A. Fonseca; Ricardo Mostany; Prasad V. G. Katakam (GeroScience, 2022)

Multiplex PCR assay for the detection of Lr24 and Lr68 in salt tolerant wheat genotypes - Charu Lata; Arvind Kumar; O. P. Gangwar; Pramod Prasad; Sneha Adhikari; Subodh Kumar; Neeraj Kulshreshtha; S. C. Bhardwaj (Cereal Research Communications, 2022)

Synthesis of (+)-xestodecalactone A - G. Nagendra Reddy; Gudisela Mura Reddy; Gattu Sridhar; K. R. S Prasad (Natural Product Research, 2022)

Understanding the genesis of a dense fog event over Delhi using observations and high-resolution model experiments - Prafull Yadav; Avinash N. Parde; Narendra Gokul Dhangar; Gaurav Govardhan; Deen Mani Lal; Sandip Wagh; Dasari S. V. V. D. Prasad; Rizwan Ahmed; Sachin D. Ghude (Modeling Earth Systems and Environment, 2022)

Low-dose priming of gamma radiation enhanced cadmium tolerance in Chlamydomonas reinhardtii by modulating physio-biochemical pathways - Biswajita Pradhan; Srimanta Patra; Rabindra Nayak; Shasank S. Swain; Bimal Prasad Jit; Chhandashree Behera; Andrea Ragusa; Jang-Seu Ki; Mrutyunjay Jena (Environmental Science and Pollution Research, 2022)

Defatted silkworm pupae meal as an alternative protein source for cattle - K. M. Rashmi; M. Chandrasekharaiah; N. M. Soren; K. S. Prasad; C. G. David; Y. Thirupathaiah; V. Shivaprasad (Tropical Animal Health and Production, 2022)

A comprehensive review on current understanding of bradykinin in COVID-19 and inflammatory diseases - Devasahayam Arokiar Balaya Rex; Neelanchal Vaid; K. Deepak; Shobha Dagamajalu; T. S. Keshava Prasad (Molecular Biology Reports, 2022)

Effective batch and column remediation of zinc(II) from synthetic and electroplating effluents using biochar from brown alga - R. Senthilkumar; Krishnan Saravanakumar; D. M. Reddy Prasad; B. S. Naveen Prasad; Feroz Shaik (International Journal of Environmental Science and Technology, 2022)

Electrocatalytic conversion of nitrate waste into ammonia: a review - Jayaraman Theerthagiri; Juhyeon Park; Himadri Tanaya Das; Nihila Rahamathulla; Eduardo S. F. Cardoso; Arun Prasad Murthy; Gilberto Maia; Dai‑Viet N. Vo; Myong Yong Choi (Environmental Chemistry Letters, 2022)

ARIMAX—Artificial neural network hybrid model for predicting semilooper (Chrysodeixis acuta) incidence on soybean - Mathyam Prabhakar; Sengottaiyan Vennila; Yenumula Gerard Prasad; G. Srasvan Kumar; R. K. Paul; S. K. Yadav (International Journal of Tropical Insect Science, 2022)

Recent advancements in the applicability of SnO2-based photo-catalysts for hydrogen production: challenges and solutions - Anjali Prasad; Jyoti Verma; S. Suresh; S. Arisutha (Waste Disposal & Sustainable Energy, 2022)

Classification of COVID-19 from tuberculosis and pneumonia using deep learning techniques - Lokeswari Venkataramana; D. Venkata Vara Prasad; S. Saraswathi; C. M. Mithumary; R. Karthikeyan; N. Monika (Medical & Biological Engineering & Computing, 2022)

Analyzing influence of thermal and osmotic stress on native isolates of Fusarium oxysporum f.sp. cubense - S. Akhileswara Reddy; Chanda Kushwaha; Bishun Deo Prasad (Indian Phytopathology, 2022)

Effect of Different Postharvest Chemical Treatments on Ethylene Production, Respiration Rate and Vital Heat of Stored Broccoli Heads - B. V. G. Prasad; S. Chakravorty (Agricultural Research, 2022)

Quality control profiling, nutritional analysis and phytochemical standardization of a vegetable root Begonia roxburghii - Rupali S. Prasad; Suhas R. Dhaswadikar; Damiki Laloo; Mahaveer Dhobi; Prakash R. Itankar; Satyendra K. Prasad (Vegetos, 2022)

Sensitivity of physical schemes on simulation of severe cyclones over Bay of Bengal using WRF-ARW model - Meenakshi Shenoy; P. V. S. Raju; V. S. Prasad; K. B. R. R. Hari Prasad (Theoretical and Applied Climatology, 2022)

Evaluation of the Bioefficacy and Insecticide Compatibility of Entomopathogens for Management of Whitefly (Hemiptera: Aleyrodidae) on Upland Cotton Under Laboratory and Polyhouse Conditions - Satish Kumar Sain; Dilip Monga; Sandhya Kranthi; Neelakanth S. Hiremani; Dipak T. Nagrale; Rishi Kumar; Surender Kumar Verma; Yenumula G. Prasad (Neotropical Entomology, 2022)

Identifying Rip Channels Along RK Beach, Visakhapatnam Using Video and Satellite Imagery Analysis - Sivaiah Borra; T. M. Balakrishnan Nair; Sudheer Jospeh; Surisetty V. V. Arun Kumar; T. Sridevi; R. Harikumar; K. Srinivas; G. Yatin; B. Gireesh; K. Venkateswararao; Ch. Venkateswarlu; A. Anjaneyulu; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Glycolytic and Oxidative Phosphorylation Defects Precede the Development of Senescence in Primary Human Brain Microvascular Endothelial Cells - Siva S. V. P. Sakamuri; Venkata N. Sure; Lahari Kolli; Ning Liu; Wesley R. Evans; Jared A. Sperling; David W. Busija; Xiaoying Wang; Sarah H. Lindsey; Walter L. Murfee; Ricardo Mostany; Prasad V. G. Katakam (GeroScience, 2022)

Quantitative phosphoproteomics reveals diverse stimuli activate distinct signaling pathways during neutrophil activation - Pooja Yedehalli Thimmappa; Aswathy S. Nair; Mohd. Altaf Najar; Varshasnatha Mohanty; Shamee Shastry; Thottethodi Subrahmanya Keshava Prasad; Manjunath B. Joshi (Cell and Tissue Research, 2022)
Neutrophils display functional heterogeneity upon responding diversely to physiological and pathological stimulations. During type 2 diabetes (T2D), hyperglycemia constitutively activates neutrophils, leading to reduced response to infections and on the other hand, elevated metabolic intermediates such as homocysteine induce bidirectional activation of platelets and neutrophils leading to thrombosis. Hence, in the context of T2D-associated complications, we examined the influence of high glucose, homocysteine, and LPS representing effector molecules of hyperglycemia, thrombosis, and infection, respectively, on human neutrophil activation to identify distinct signaling pathways by quantitative phosphoproteomics approach. High glucose activated C-Jun-N-Terminal Kinase, NTRK1, SYK, and PRKACA kinases associated with Rho GTPase signaling and phagocytosis, whereas LPS induced AKT1, SRPK2, CSNK2A1, and TTN kinases involved in cytokine signaling and inflammatory response. Homocysteine treatment led to activatation of LRRK2, FGR, MAPK3, and PRKCD kinases which are associated with neutrophil degranulation and cytoskeletal remodeling. Diverse inducers differentially modulated phosphorylation of proteins associated with neutrophil functions such as oxidative burst, degranulation, extracellular traps, and phagocytosis. Further validation of phosphoproteomics data on selected kinases revealed neutrophils pre-cultured under high glucose showed impeded response to LPS to phosphorylate p-ERK1/2 Thr202/Tyr204 , p-AKT Ser473 , and C-Jun-N-Terminal Kinase Ser63 kinases. Our study provides novel phosphoproteome signatures that may be explored to understand neutrophil biology in T2D-associated complications.

Toxicity Assessment of Fluoride-Contaminated Soil and Wastewater in Solanum tuberosum - Gitika Devi; Anamika Kushwaha; Lalit Goswami; Sutapa Chakrabarty; Hardeep Kaur; Sandip S. Sathe; Kanchan Bahukhandi; Uday Bhan; Hari Prasad Sarma (Water, Air, & Soil Pollution, 2022)

Temperature Perturbations in the Troposphere and Lower Stratosphere Over a Semi-arid Region During the 2010 Solar Eclipse - Vinay Kumar; S. B. Surendra Prasad; K. Krishna Reddy; S. K. Dhaka; R. K. Choudhary; M. Venkatarami Reddy; Shu-Peng Ho (Pure and Applied Geophysics, 2022)

Tools and techniques in forensic entomology- A critical review - M. S. Siva Prasad; Embalil Mathachan Aneesh (International Journal of Tropical Insect Science, 2022)

Dissecting the dependence of total biomass on physiological traits through path analysis - S. Nadaradjan; S. M. Impa; P. Boominathan; S. Hukkeri; S. G. Parsi; M. S. Sheshshayee; M. Udayakumar; T. G. Prasad (Plant Physiology Reports, 2022)

Efficacy of Arbuscular Mycorrhizal Fungi and Bacterial Inoculants in Enhancing Yield of Phaseolus mungo L. and Vigna radiata (L.) R. Wilczek under Central Indian Conditions - Ashok Shukla; Anil Kumar; Rajendra Prasad; Naresh Kumar; S. K. Dhyani; O. P. Chaturvedi; Ayyanadar Arunachalam (Journal of Soil Science and Plant Nutrition, 2022)

Influence of river inflow and its impact on the salinity variations and flushing time in a networked system, northwest coast of India - Jubin Thomas; V S Naidu; P R Shanas; Prasad Bhaskaran; C V Naidu (Journal of Earth System Science, 2022)

Recycling of induction furnace steel slag in concrete for marine environmental applications towards ocean acidification studies - J. Baalamurugan; V. Ganesh Kumar; B. S. N. Naveen Prasad; R. Padmapriya; V. Karthick; K. Govindaraju (International Journal of Environmental Science and Technology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Development of an Android-Based Application System for Fish Farmers - D. Kiranmayi; Arpita Sharma; K. Pani Prasad; Rama Sharma; S. K. Sharma (Agricultural Research, 2022)

Annual and Inter-annual Variability Coupled with Comparison of MODIS-AERONET Retrieved Aerosol Optical Depth over a Rural Site in the Central Indo-Gangetic Basin - S. R. Varpe; A. R. Kolhe; P. Singh; C. M. Mahajan; G. C. Kutal; R. S. Patil; P. Prasad; G. R. Aher (Aerosol Science and Engineering, 2022)

Achieving higher production from low inputs using synergistic crop interactions under maize-based polyculture systems - S. D. Bamboriya; Ram Swaroop Bana; Bhola Ram Kuri; Vipin Kumar; Sumitra Devi Bamboriya; Rajendra Prasad Meena (Environmental Sustainability, 2022)

Back-propagation neural network: Box–Behnken design modelling for optimization of copper adsorption on orange zest biochar - S. Sivamani; B. S. Naveen Prasad; K. Nithya; N. Sivarajasekar; A. Hosseini-Bandegharaei (International Journal of Environmental Science and Technology, 2022)

Assessment of heterotic potential and combining ability of novel iso-cytoplasmic restorer lines derived from an elite rice hybrid, KRH-2, for the development of superior rice hybrids - Swapnil Ravindra Kulkarni; S M Balachandran; R A Fiyaz; Divya Balakrishnan; K Sruthi; K Ulaganathan; A S Hari Prasad; R M Sundaram (Euphytica, 2022)

Extreme swell wave energy and its directional characteristics in the Indian Ocean - S. Sreelakshmi; Prasad K. Bhaskaran (Climate Dynamics, 2022)

New Records of Six Fish Species from Reef Off Visakhapatnam Coastal Waters, Northeast Coast of India - K. Silambarasan; A. B. Kar; G. V. A. Prasad; S. K. Pattnayak; L. Ramalingam (Thalassas: An International Journal of Marine Sciences, 2022)

Analysis of functional traits in Gracilaria dura (Rhodophyta: Gracilariacae) reveals variation in wild and farmed populations - Kanchan Sambhwani; Gangotri Mathukiya; Pankaj S. Dawange; Rosy Alphons Sequeira; Kamalesh Prasad; Vaibhav A. Mantri (Journal of Applied Phycology, 2022)

Modelling of Moment Tensors and Source Parameters of the 25 July 2021 Rare Lower Crustal Hyderabad (India) Earthquake of Mw 3.9 - Prantik Mandal; Satish Saha; Sudesh Kumar; Sandeep Gupta; Rahul Biswas; Sanjay Kumar; K. Sivaram; B. N. V. Prasad; M. Saidixit; Raju Prathigadapa; Bhoopender Singh; S. Madhusudan (Pure and Applied Geophysics, 2022)

Detection of pre-cluster nano-tendency through multi-viewpoints cosine-based similarity approach - M. Suleman Basha; S. K. Mouleeswaran; K. Rajendra Prasad (Nanotechnology for Environmental Engineering, 2022)

Simulating the spatial and temporal distribution of oil spill over the coral reef environs along the southeast coast of Mauritius: A case study on MV Wakashio vessel wreckage, August 2020 - S J Prasad; T M Balakrishnan Nair; Sudheer Joseph; P C Mohanty (Journal of Earth System Science, 2022)

Prediction of rapid intensification for land-falling extremely severe cyclonic storms in the Bay of Bengal - Kuvar Satya Singh; Ambily Thankachan; K. Thatiparthi; M. S. Reshma; Jiya Albert; Subbareddy Bonthu; Prasad K. Bhaskaran (Theoretical and Applied Climatology, 2022)

Sustainable in-situ recycling and IoT-based monitoring system of water-soluble metal working fluids - H. V. Puneeth; M. S. Ganesha Prasad (Sustainable Water Resources Management, 2022)

Epigenetics of wheat–rust interaction: an update - Shilpa; Rajni Kant Thakur; Pramod Prasad; S. C. Bhardwaj; O. P. Gangwar; Subodh Kumar (Planta, 2022)

Ecological monitoring and indicator taxa: butterfly communities in heterogeneous landscapes of the Western Ghats and Malabar coast, India - Deepak Naik; R. Shyama Prasad Rao; Krushnamegh Kunte; Mohammed S. Mustak (Journal of Insect Conservation, 2022)

Landraces-potential treasure for sustainable wheat improvement - Sneha Adhikari; Jyoti Kumari; Sherry Rachel Jacob; Pramod Prasad; O. P. Gangwar; Charu Lata; Rajnikant Thakur; Amit Kumar Singh; Ruchi Bansal; Sundeep Kumar; S. C. Bhardwaj; Subodh Kumar (Genetic Resources and Crop Evolution, 2022)

An assessment of ITS rDNA PCR-based molecular identification, and characterization of fungal endophytes isolated from Hypericum japonicum - A. N. Anoopkumar; M. S. Siva Prasad; Sharrel Rebello; Sini Francis CF; Embalil Mathachan Aneesh (Plant Biosystems, 2022)

Role and influence of key atmospheric parameters in large-scale environmental flow associated with tropical cyclogenesis and ENSO in the North Indian Ocean basin - Jiya Albert; Athira Krishnan; Prasad K. Bhaskaran; Kuvar S. Singh (Climate Dynamics, 2022)

Loss of lock on GNSS signals and its association with ionospheric irregularities observed over Indian low latitudes - V. K. D. Srinivasu; Nirvikar Dashora; D. S. V. V. D. Prasad; K. Niranjan (GPS Solutions, 2022)

Age of diagnosis in familial Barrett’s associated neoplasia - Benita K. Glamour; Omar Alaber; Gino Cioffi; Apoorva K. Chandar; Jill Barnholtz-Sloan; Wendy Brock; Gary W. Falk; Marcia I. Canto; Jean S. Wang; Prasad G. Iyer; Nicholas J. Shaheen; William M. Grady; et al. (Familial Cancer, 2022)

Heat tolerance as a function of membrane lipid remodeling in the major US oilseed crops (soybean and peanut) - Sachin Rustgi; Jyoti Prasad Kakati; Zachary T. Jones; Zolian S. Zoong Lwe; Sruthi Narayanan (Journal of Plant Biochemistry and Biotechnology, 2021)

Landslide Susceptibility Zonation of Idukki District Using GIS in the Aftermath of 2018 Kerala Floods and Landslides: a Comparison of AHP and Frequency Ratio Methods - Anjana V. Thomas; Sunil Saha; Jean Homian Danumah; S. Raveendran; Megha K. Prasad; R. S. Ajin; Sekhar L. Kuriakose (Journal of Geovisualization and Spatial Analysis, 2021)

Multistage magmatic intrusion in Narmada–Tapti region, India: Insights from geopotential modelling - K N D Prasad; A P Singh; P Rama Rao; Om Prakash; S K Begum (Journal of Earth System Science, 2021)

Sensitivity to initial conditions on the simulation of extratropical cyclone ‘Gong’ formed over North Atlantic - P K Pradhan; Hari Prasad Dasari; Srinivas Desamsetti; S Vijaya Bhaskara Rao; Rambabu Guvvala (Journal of Earth System Science, 2021)

A comprehensive study on preparedness, impacts, response and recovery from tropical severe cyclonic storm ‘GAJA’: lessons for the future - S. Leo George; K. Balasubramani; Sulochana Shekhar; E. Venkatesham; K. Arun Prasad; Aakriti Grover; Dinabandhu Mahata; Ashish Kumar; V. V. Ashique; R. S. Libina; Divya Rajeswari Swaminathan; A. Balasundareshwaran; et al. (Journal of Coastal Conservation, 2021)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Numerical simulation of an extremely severe cyclonic storm over the Bay of Bengal using WRF modelling system: influence of model initial condition - K. S. Singh; Jiya Albert; Prasad K. Bhaskaran; Parvez Alam (Modeling Earth Systems and Environment, 2021)

A Dominant C150Y Mutation in FHL1 Induces Structural Alterations in LIM2 Domain Causing Protein Aggregation In Human and Drosophila Indirect Flight Muscles - Rashmi Santhoshkumar; Veeramani Preethish-Kumar; Kiran K. Mangalaparthi; Sruthi Unni; Balasundaram Padmanabhan; Keshava Prasad T. S.; Upendra Nongthomba; Nalini Atchayaram; Gayathri Narayanappa (Journal of Molecular Neuroscience, 2021)

Impact of Purkinje Cell Simple Spike Synchrony on Signal Transmission from Flocculus - John S. Stahl; Aaron Ketting-Olivier; Prasad A. Tendolkar; Tenesha L. Connor (The Cerebellum, 2021)

Spatial prediction of soil depth using environmental covariates by quantile regression forest model - M. Lalitha; S. Dharumarajan; Amar Suputhra; B. Kalaiselvi; Rajendra Hegde; RS. Reddy; CR. Shiva Prasad; CS. Harindranath; BS. Dwivedi (Environmental Monitoring and Assessment, 2021)

Prevalence of Y chromosome microdeletion in north Indian infertile males with spermatogenesis defect - HIMANSHU SHARMA; UJJAWAL SHARMA; SANTOSH KUMAR; SHRAWAN KUMAR SINGH; RAVI MOHAN S. MAVADURU; RAJENDRA PRASAD (Journal of Genetics, 2021)

On the Conditions for Onset and Development of Fog Over New Delhi: An Observational Study from the WiFEX - Narendra G. Dhangar; D. M. Lal; Sachin D. Ghude; Rachana Kulkarni; Avinash N. Parde; Prakash Pithani; K. Niranjan; Dasari S. V. V. D. Prasad; Chinmay Jena; Veeresh S. Sajjan; Thara Prabhakaran; A. K. Karipot; et al. (Pure and Applied Geophysics, 2021)

Morphological Descriptors and Heritability as Markers for Oil Yield in Balanites aegyptiaca (L.) Del.: A Potential Biodiesel Xerophyte - Mahesh Kumar Saini; Jagdish Prasad; P. V. S. Raju; S. L. Kothari; Harish; Jitendra Kumar Shukla; Vinod Singh Gour (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Reliability-based analysis of probability density function and failure rate of the shovel–dumper system in a surface coal mine - N. S. Harish Kumar; Ram Prasad Choudhary; Chivukula Suryanarayana Murthy (Modeling Earth Systems and Environment, 2021)

The bacterium Pseudomonas protegens antagonizes the microalga Chlamydomonas reinhardtii using a blend of toxins - Magdalena M. Rose; Daniel Scheer; Yu Hou; Vivien S. Hotter; Anna J. Komor; Prasad Aiyar; Kirstin Scherlach; Fredd Vergara; Qing Yan; Joyce E. Loper; Torsten Jakob; Nicole M. van Dam; et al. (Environmental Microbiology, 2021)
Summary The unicellular alga Chlamydomonas reinhardtii and the bacterium Pseudomonas protegens serve as a model to study the interactions between photosynthetic and heterotrophic microorganisms. P . protegens secretes the cyclic lipopeptide orfamide A that interferes with cytosolic Ca 2+ homeostasis in C . reinhardtii resulting in deflagellation of the algal cells. Here, we studied the roles of additional secondary metabolites secreted by P . protegens using individual compounds and co‐cultivation of algae with bacterial mutants. Rhizoxin S2, pyrrolnitrin, pyoluteorin, 2,4‐diacetylphloroglucinol (DAPG) and orfamide A all induce changes in cell morphology and inhibit the growth of C . reinhardtii . Rhizoxin S2 exerts the strongest growth inhibition, and its action depends on the spatial structure of the environment (agar versus liquid culture). Algal motility is unaffected by rhizoxin S2 and is most potently inhibited by orfamide A (IC 50 = 4.1 μM). Pyrrolnitrin and pyoluteorin both interfere with algal cytosolic Ca 2+ homeostasis and motility whereas high concentrations of DAPG immobilize C . reinhardtii without deflagellation or disturbance of Ca 2+ homeostasis. Co‐cultivation with a regulatory mutant of bacterial secondary metabolism (Δ gacA ) promotes algal growth under spatially structured conditions. Our results reveal how a single soil bacterium uses an arsenal of secreted antialgal compounds with complementary and partially overlapping activities.

EMS-Based In Vitro Mutagenesis and Mutant Screening for Smut Resistance with Agronomic Traits in Sugarcane - S. G. Dalvi; P. N. Tawar; P. Suprasanna; G. B. Dixit; D. Theertha Prasad (Sugar Tech, 2021)

Computational assessment of saikosaponins as adjuvant treatment for COVID-19: molecular docking, dynamics, and network pharmacology analysis - Rupesh Chikhale; Saurabh K. Sinha; Manish Wanjari; Nilambari S. Gurav; Muniappan Ayyanar; Satyendra Prasad; Pukar Khanal; Yadu Nandan Dey; Rajesh B. Patil; Shailendra S. Gurav (Molecular Diversity, 2021)

Are ocean-moored buoys redundant for prediction of Indian monsoon? - Maheswar Pradhan; Ankur Srivastava; Suryachandra A. Rao; Deep Sankar Banerjee; Abhisek Chatterjee; P. A. Francis; O. P. Sreejith; M. Das Gupta; V. S. Prasad (Meteorology and Atmospheric Physics, 2021)

Microplastic fibers influence Ag toxicity and bioaccumulation in Eisenia andrei but not in Enchytraeus crypticus - Paula S. Tourinho; Susana Loureiro; V. S. S. L. Prasad Talluri; Andraž Dolar; Rudo Verweij; Jiří Chvojka; Alena Michalcová; Vladimír Kočí; Cornelis A. M. van Gestel (Ecotoxicology, 2021)

Optimal Design of Barrage Profile on Anisotropic Soil Using Multi‐Objective Optimization Approach - Arjun Prasad; Raj Mohan Singh; S. K. Duggal (Water Resources Management, 2021)

Diabetes Mellitus/Poststroke Hyperglycemia: a Detrimental Factor for tPA Thrombolytic Stroke Therapy - Yinghua Jiang; Ning Liu; Jinrui Han; Yadan Li; Pierce Spencer; Samuel J. Vodovoz; Ming-Ming Ning; Gregory Bix; Prasad V. G. Katakam; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2021)

Reconstruction of Gap-Free OCM-2 Chlorophyll-a Concentration Using DINEOF - Chiranjivi Jayaram; J. Pavan Kumar; T. V. S. Udaya Bhaskar; I. V. G. Bhavani; T. D. V. Prasad Rao; P. V. Nagamani (Journal of the Indian Society of Remote Sensing, 2021)

The magnificent Dipterocarps: précis for an Epitaph? - P. S. Ashton; R. J. Morley; J. Heckenhauer; V. Prasad (Kew Bulletin, 2021)

Correction to: Application of GIS and AHP Method in Forest Fire Risk Zone Mapping: a Study of the Parambikulam Tiger Reserve, Kerala, India - S. Nikhil; Jean Homian Danumah; Sunil Saha; Megha K. Prasad; A. Rajaneesh; Pratheesh C. Mammen; R. S. Ajin; Sekhar L. Kuriakose (Journal of Geovisualization and Spatial Analysis, 2021)

Application of GIS and AHP Method in Forest Fire Risk Zone Mapping: a Study of the Parambikulam Tiger Reserve, Kerala, India - S. Nikhil; Jean Homian Danumah; Sunil Saha; Megha K. Prasad; A. Rajaneesh; Pratheesh C. Mammen; R. S. Ajin; Sekhar L. Kuriakose (Journal of Geovisualization and Spatial Analysis, 2021)

Influence of phytoplankton pigment composition and primary production on pCO2 levels in the Indian Ocean - V V S S Sarma; M H K Prasad; H B Dalabehera (Journal of Earth System Science, 2021)

Investigation of rip current processes along Visakhapatnam beaches, east coast of India: A study based on GNSS drifters and dye experiments - Surisetty V V Arun Kumar; B Sivaiah; Ch Venkateswarlu; B Gireesh; T Sridevi; K Venkateswara Rao; K V S R Prasad; Rashmi Sharma (Journal of Earth System Science, 2021)

Insights into the rust resistance base of common wheat (Triticum aestivum L.) in India - A. N. Mishra; K. N. Tiwari; Vaibhav K. Singh; M. Sivasamy; Dharam Pal; S. C. Bhardwaj; O. P. Gangwar; T. L. Prakasha; K. S. Solanki; Rahul M. Phuke; S. V. Sai Prasad; C. N. Mishra; et al. (Indian Phytopathology, 2021)

Immunity to rusts in wheat: theory, fact and practice - S. C. Bhardwaj; O. P. Gangwar; P. Prasad; Subodh Kumar; Dharam Pal (Indian Phytopathology, 2021)

Classification of Synthetic Aperture Radar-Ground Range Detected Image Using Advanced Convolution Neural Networks - Battula Balnarsaiah; T. S. Prasad; Parayitam Laxminarayana (Remote Sensing in Earth Systems Sciences, 2021)

A multidisciplinary review of Tetradesmus obliquus : a microalga suitable for large‐scale biomass production and emerging environmental applications - Carlos Yure B. Oliveira; Cicero Diogo L. Oliveira; Ravindra Prasad; Hwai C. Ong; Evando S. Araujo; Nisha Shabnam; Alfredo O. Gálvez (Reviews in Aquaculture, 2021)
Microalgae biomass is among one of the most promising sustainable raw materials for many industrial sectors especially biodiesel production. Although a great diversity of microalgae species has been described and isolated, few have been used for large‐scale cultivation. This review presents a multidisciplinary overview of studies on Tetradesmus obliquus – a freshwater microalga suitable for large‐scale production and emerging environmental applications. It reviews the taxonomic history of T. obliquus and its potential commercial applications, including cultivations techniques and environmental parameters, production systems, harvesting and drying of biomass, and its biochemical composition. In addition, a model refinery for T. obliquus is proposed that combines the main productive bioprocesses. Finally, a bibliometric analysis is presented and opportunities for future research with T. obliquus are identified.

Experimental studies on the performance and emission parameters of a direct injection diesel engine fueled with nanoparticle-dispersed biodiesel blend - S. Jaikumar; V. Srinivas; V. V. S. Prasad; G. Susmitha; P. Sravya; A. Sajala; L. Jaswitha (Nanotechnology for Environmental Engineering, 2021)

Metabolic changes in triple negative breast cancer-focus on aerobic glycolysis - J. R. Dev Arundhathi; Sandeep R Mathur; Ajay Gogia; S. V. S. Deo; Purusottam Mohapatra; Chandra Prakash Prasad (Molecular Biology Reports, 2021)

Mitigation strategies to enhance carbon sink potential in climate vulnerable districts of Eastern India - K. Sammi Reddy; Ch. Srinivasarao; V. Girija Veni; J.V.N.S. Prasad; K.L. Sharma; K. Sumanta; Ch. Chandrasekhar; Jha. Ratnesh Kumar; S.K. Choudhary; Deokaran; S.K. Mishra; Nityanand; et al. (Climate and Development, 2021)

Saddleback Syndrome in Wild Black Pomfret Parastromateus niger (Bloch, 1795), From Southeast Coast of India - K. Silambarasan; K. Govindaraj; A. B. Kar; G. V. A. Prasad; S. K. Pattnayak; L. Ramalingam (Thalassas: An International Journal of Marine Sciences, 2021)

Assessment of bollworm damage and yield loss in seed blends of Bollgard-II with corresponding Non-Bt hybrid as ‘built in refuge’ in cotton - Rishi Kumar; S. Kranthi; G. M. V. Prasad Rao; H. Desai; H. Bheemanna; B. Dharajothi; Alka Choudhary; K. R. Kranthi (Phytoparasitica, 2021)

Sensitivity analysis of artificial neural network for chlorophyll prediction using hyperspectral data - Prashant K. Srivastava; Manika Gupta; Ujjwal Singh; Rajendra Prasad; Prem Chandra Pandey; A. S. Raghubanshi; George P. Petropoulos (Environment, Development and Sustainability, 2021)

Lr80: A new and widely effective source of leaf rust resistance of wheat for enhancing diversity of resistance among modern cultivars - Subodh Kumar; Subhash C. Bhardwaj; Om P. Gangwar; Akanksha Sharma; Naeela Qureshi; Vikas V. Kumaran; Hanif Khan; Pramod Prasad; Hanif Miah; Gyanendra P. Singh; Kiran Sharma; Hemlata Verma; et al. (Theoretical and Applied Genetics, 2021)

Genome-wide comparative transcriptome analysis of the A4-CMS line ICPA 2043 and its maintainer ICPB 2043 during the floral bud development of pigeonpea - Abhishek Bohra; Abhishek Rathore; Prasad Gandham; Rachit K. Saxena; S. J. Satheesh Naik; Dibendu Dutta; Indra P. Singh; Farindra Singh; Meenal Rathore; Rajeev K. Varshney; Narendra P. Singh (Functional & Integrative Genomics, 2021)

Reduction of global warming potential vis-à-vis greenhouse gases through traditional agroforestry systems in Rajasthan, India - S. B. Chavan; Ram Newaj; R. H. Rizvi; Ajit; Rajendra Prasad; Badre Alam; A. K. Handa; S. K. Dhyani; Amit Jain; Dharmendra Tripathi (Environment, Development and Sustainability, 2021)

Assessment of extremely severe cyclonic storms over Bay of Bengal and performance evaluation of ARW model in the prediction of track and intensity - K. S. Singh; Jiya Albert; Prasad K. Bhaskaran; Parvez Alam (Theoretical and Applied Climatology, 2021)

Gain of one-month lead time in seasonal prediction of Indian summer monsoon prediction: comparison of initialization strategies - Ankur Srivastava; Suryachandra A. Rao; Maheswar Pradhan; Prasanth A. Pillai; V. S. Prasad (Theoretical and Applied Climatology, 2021)

Sugarcane Yield Forecasting Model Based on Weather Parameters - Amit Kumar Verma; Pradeep Kumar Garg; K. S. Hari Prasad; Vinay Kumar Dadhwal; Sunil Kumar Dubey; Arvind Kumar (Sugar Tech, 2021)

Identification of microRNAs and their gene targets in cytoplasmic male sterile and fertile maintainer lines of pigeonpea - Abhishek Bohra; Prasad Gandham; Abhishek Rathore; Vivek Thakur; Rachit K. Saxena; S. J. Satheesh Naik; Rajeev K. Varshney; Narendra P. Singh (Planta, 2021)

Effect of Sonic hedgehog pathway inhibition on PDX1 expression during pancreatic differentiation of human embryonic stem cells - Prasad S. Pethe; Niloufer P. Dumasia; Deepa Bhartiya (Molecular Biology Reports, 2021)

A comparative Study on the Effect of Seed Pre-sowing Treatments with Microwave Radiation and Salicylic Acid in Alleviating the Drought-Induced Damage in Wheat - Hanafey Farouk Maswada; V. S. John Sunoj; P. V. Vara Prasad (Journal of Plant Growth Regulation, 2021)

Spatial variations in dissolved inorganic nutrients in the groundwaters along the Indian coast and their export to adjacent coastal waters - B. S. K. Kumar; R. Viswanadham; V. R. Kumari; D. B. Rao; M. H. K. Prasad; N. Srinivas; V. V. S. S. Sarma (Environmental Science and Pollution Research, 2021)

Assessment of the Efficacy of Lightning Forecast Over India: A Diagnostic Study - A. Sandeep; A. Jayakumar; M. Sateesh; Saji Mohandas; V. S. Prasad; E. N. Rajagopal (Pure and Applied Geophysics, 2021)

Use of single seed descent versus pedigree selection for development of elite parental lines in castor (Ricinus communis L.) - C. Lavanya; B. Ushakiran; C. Sarada; T. Manjunatha; S. Senthilvel; K. T. Ramya; M. Santhalakshmi Prasad (Genetic Resources and Crop Evolution, 2021)

Variability of monsoon inversion over the Arabian Sea and its impact on rainfall - Sanjeev Dwivedi; Viswanadhapalli Yesubabu; M. Venkat Ratnam; Hari Prasad Dasari; Sabique Langodan; S. T. Akhil Raj; Ibrahim Hoteit (International Journal of Climatology, 2021)
This work investigates the spatial and temporal variability of the monsoon inversion (MI) over the Arabian Sea for the study of 37‐years period (1980–2016) using MERRA version2 (MERRA2) reanalysis and downscaled simulations generated with the Weather and Research Forecasting (WRF) model. After validating the downscaled products with the observations from four radiosonde stations (Salalah, Mumbai, Goa and Mangalore), we analysed the variability of MI from diurnal to seasonal scales. The diurnal evolution of the MI suggests that radiative cooling over the Arabian Peninsula at night, together with the onset of boundary layer jets along the coast of Oman, play an important role in amplifying the intensity and spatial extent of the MI during night and into the early morning hours. A seasonal analysis of the simulated winds and MI reveals that WRF reproduced the monsoon characteristics as observed in MERRA2 reanalysis, including the spatial and vertical orientations of the MI. The downscaled winds are slightly overestimated (by 1–2 m⋅s −1 ) over the Arabian Sea, which resulted in an increased simulated wind shear over the western Arabian Sea, ultimately manifested in the form of an enhanced MI. We further investigated the variability of the lower tropospheric wind speed and associated changes in MI over the 37‐year period. This reveals a significant decreasing trend during the summer monsoon over the western Arabian Sea. We argue that this led to a decreasing trend in the lower tropospheric wind shear and advection of temperature and hence, reduced the frequency of occurrence of the MI (shown in graphical abstract).

Numerical Simulation of an Extremely Severe Cyclonic Storm Hudhud over the North Indian Ocean in a Medium Range Scale: Influence of Cloud Microphysical Schemes - K. S. Singh; Parvez Alam; Jiya Albert; Prasad K. Bhaskaran (Pure and Applied Geophysics, 2020)

Seasonal variability of tropospheric CO2 over India based on model simulation, satellite retrieval and in-situ observation - M Krishnapriya; Rabindra K Nayak; Shaik Allahudeen; A Bhuvanachandra; V K Dadhwal; C S Jha; M V R Sheshasai; S K Sasmal; K V S R Prasad (Journal of Earth System Science, 2020)

Application of hind cast in identifying extreme events over India - C J Johny; V S Prasad (Journal of Earth System Science, 2020)

Understanding stable isotope systematics of salinity affected groundwater in Mewat, Haryana, India - Gopal Krishan; N C Ghosh; C P Kumar; Lalit Mohan Sharma; Brijesh Yadav; M L Kansal; Surjeet Singh; S K Verma; Gokul Prasad (Journal of Earth System Science, 2020)

Gondwana biostratigraphy and geology of West Bengal Basin, and its correlation with adjoining Gondwana basins of India and western Bangladesh - Bijai Prasad; B S Pundir (Journal of Earth System Science, 2020)

Inheritance of leaf rust resistance in four popular Indian durum wheat cultivars - A. Divya; T. L. Prakasha; A. N. Mishra; S. Chand; K. S. Solanki; Pramod Prasad; S. V. Sai Prasad (Indian Phytopathology, 2020)

Impacts of climate change on Fusarium species vis-à-vis adaptation strategies - Suseelendra Desai; S. C. Dubey; R. D. Prasad (Indian Phytopathology, 2020)

Safety of fluoxetine use in children and adolescents: a disproportionality analysis of the Food and Drug Administration Adverse Event Reporting System (FAERS) database - Iole N. Christodoulos; Te-yuan Chyou; Prasad S. Nishtala (European Journal of Clinical Pharmacology, 2020)

Impacts of hydrological model calibration on projected hydrological changes under climate change—a multi-model assessment in three large river basins - Shaochun Huang; Harsh Shah; Bibi S. Naz; Narayan Shrestha; Vimal Mishra; Prasad Daggupati; Uttam Ghimire; Tobias Vetter (Climatic Change, 2020)
This study aimed to investigate the influence of hydrological model calibration/validation on discharge projections for three large river basins (the Rhine, Upper Mississippi and Upper Yellow). Three hydrological models (HMs), which have been firstly calibrated against the monthly discharge at the outlet of each basin (simple calibration), were re-calibrated against the daily discharge at the outlet and intermediate gauges under contrast climate conditions simultaneously (enhanced calibration). In addition, the models were validated in terms of hydrological indicators of interest (median, low and high flows) as well as actual evapotranspiration in the historical period. The models calibrated using both calibration methods were then driven by the same bias corrected climate projections from five global circulation models (GCMs) under four Representative Concentration Pathway scenarios (RCPs). The hydrological changes of the indicators were represented by the ensemble median, ensemble mean and ensemble weighted means of all combinations of HMs and GCMs under each RCP. The results showed moderate (5–10%) to strong influence (> 10%) of the calibration methods on the ensemble medians/means for the Mississippi, minor to moderate (up to 10%) influence for the Yellow and minor (< 5%) influence for the Rhine. In addition, the enhanced calibration/validation method reduced the shares of uncertainty related to HMs for three indicators in all basins when the strict weighting method was used. It also showed that the successful enhanced calibration had the potential to reduce the uncertainty of hydrological projections, especially when the HM uncertainty was significant after the simple calibration.

Modeling of ionospheric characteristics based on canonical correlation analysis at Bangalore for the year 2017 - Ravi Kiran Pyla; J. R. K. Kumar Dabbakuti; S. G. Prasad Mutchakayala; Sairam Yashoda; Manikanta Alluri (Acta Geodaetica et Geophysica, 2020)

Assimilation of Radial Winds Over India Using a Community GSI Analysis System - Sujata Pattanayak; V. S. Prasad (Pure and Applied Geophysics, 2020)

Antimicrobial peptide polymers: no escape to ESKAPE pathogens—a review - Songhita Mukhopadhyay; A. S. Bharath Prasad; Chetan H. Mehta; Usha Y. Nayak (World Journal of Microbiology and Biotechnology, 2020)
Antimicrobial resistance (AMR) is one of the significant clinical challenges and also an emerging area of concern arising from nosocomial infections of ESKAPE pathogens, which has been on the rise in both the developed and developing countries alike . These pathogens/superbugs can undergo rapid mutagenesis, which helps them to generate resistance against antimicrobials in addition to the patient’s non-adherence to the antibiotic regimen. Sticking to the idea of a ‘one-size-fits-all’ approach has led to the inappropriate administration of antibiotics resulting in augmentation of antimicrobial resistance. Antimicrobial peptides (AMPs) are the natural host defense peptides that have gained attention in the field of AMR, and recently, synthetic AMPs are well studied to overcome the drawbacks of natural counterparts. This review deals with the novel techniques utilizing the bacteriolytic activity of natural AMPs. The effective localization of these peptides onto the negatively charged bacterial surface by using nanocarriers and structurally nanoengineered antimicrobial peptide polymers (SNAPPs) owing to its smaller size and better antimicrobial activity is also described here. Graphic abstract

Haemato-biochemical alterations and oxidative stress associated with naturally occurring porcine circovirus2 infection in pigs - J. B. Rajesh; S. Rajkhowa; U. Dimri; H. Prasad; N. H. Mohan; L. Hmar; K. Sarma; G. E. Chethan; P. Behera; G. Jaganmohanarao; S. Behera; Zosangpuii (Tropical Animal Health and Production, 2020)

Spatio-Temporal Distribution and Variability of High Threshold Wind Speed and Significant Wave Height for the Indian Ocean - S. Sreelakshmi; Prasad K. Bhaskaran (Pure and Applied Geophysics, 2020)

Variations in photosynthesis associated traits and grain yield of minor millets - K. S. Pavithra; A. Senthil; V. Babu Rajendra Prasad; R. Ravikesavan; M. Djanaguiraman (Plant Physiology Reports, 2020)

Genome-wide analysis of H3K4me3 and H3K27me3 modifications due to Lr28 for leaf rust resistance in bread wheat (Triticum aestivum) - Gautam Saripalli; Kalpana Singh; Tinku Gautam; Santosh Kumar; Saurabh Raghuvanshi; Pramod Prasad; Neelu Jain; P. K. Sharma; H. S. Balyan; P. K. Gupta (Plant Molecular Biology, 2020)

Efficacy of new generation fungicides against French bean rust caused by Uromyces appendiculatus - Banita Devi; S. K. Gupta; Gurvinder Singh; Pramod Prasad (Phytoparasitica, 2020)

Effect of ethanolic extract of Solanum virginianum Linn. on neuropathic pain using chronic constriction injury rat model and molecular docking studies - Sonia Verma; Anurag Kuhad; Ranjana Bhandari; Satyendra K. Prasad; Anshul Shakya; Rupali S. Prasad; Saurabh K. Sinha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Assessment of genetic diversity and development of core germplasm in durum wheat using agronomic and grain quality traits - Divya Ambati; Rahul M. Phuke; V. Vani; S. V. Sai Prasad; Jang Bahadur Singh; Chandra Prakash Patidar; Prakash Malviya; Amit Gautam; Vijay G. Dubey (Cereal Research Communications, 2020)

Correction to: Variation in stalk rot resistance and physiological traits of sorghum genotypes in the field under high temperature - Ramasamy Perumal; Sandeep S. Tomar; Ananda Bandara; Djanaguiraman Maduraimuthu; Tesfaye T. Tesso; P. V. Vara Prasad; Hari D. Upadhyaya; Christopher R. Little (Journal of General Plant Pathology, 2020)

Variation in stalk rot resistance and physiological traits of sorghum genotypes in the field under high temperature - Ramasamy Perumal; Sandeep S. Tomar; Ananda Bandara; Djanaguiraman Maduraimuthu; Tesfaye T. Tesso; P. V. Vara Prasad; Hari D. Upadhyaya; Christopher R. Little (Journal of General Plant Pathology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Evaluation of opportunity based urban road network accessibility using GIS - Kurre Sai Sahitya; C. S. R. K. Prasad (Spatial Information Research, 2020)

Thermodynamic Response of a High-Resolution Tropical Indian Ocean Model to TOGA COARE Bulk Air–Sea Flux Parameterization: Case Study for the Bay of Bengal (BoB) - Subrat Kumar Mallick; Neeraj Agarwal; Rashmi Sharma; K. V. S. R. Prasad; S. S. V. S. Ramakrishna (Pure and Applied Geophysics, 2020)

Population structure of Alternaria species causing leaf blight of sunflower (Helianthus annuus L.) in India - M. Santha Lakshmi Prasad; N. Naresh; K. Sujatha; D. Usha; M. Sujatha; C. Sarada; S. Chander Rao; P. Chowdappa (Phytoparasitica, 2020)

Modelling structural interdependent parameters of an urban road network using GIS - Kurre Sai Sahitya; C. S. R. K. Prasad (Spatial Information Research, 2020)

Evaluation of genetic diversity of parental lines for development of heterotic groups in hybrid rice (Oryza sativa L.) - K. Sruthi; B. Divya; P. Senguttuvel; P. Revathi; K. B. Kemparaju; P. Koteswararao; R. M. Sundaram; Vikram Jeet Singh; E. Ranjith Kumar; Prolay Kumar Bhowmick; K. K. Vinod; S. Gopala Krishnan; et al. (Journal of Plant Biochemistry and Biotechnology, 2020)

Detection of genetic variation among stripe rust (Puccinia striiformis f. sp. tritici) pathotypes of wheat with simple sequence repeat markers - Anurag Saharan; R. S. Chauhan; Archit Sood; Pramod Prasad; Subodh Kumar (Indian Phytopathology, 2020)

Regional wise characteristic study of significant wave height for the Indian Ocean - S. Sreelakshmi; Prasad K. Bhaskaran (Climate Dynamics, 2020)

Synthesis, anticancer evaluation, and molecular docking studies of benzoxazole linked combretastatin analogues - Vukoti Kiran Kumar; Venkat Swamy Puli; Ala Vasu Babu; Radhakrishnam Raju Ruddarraju; K. R. S. Prasad (Medicinal Chemistry Research, 2020)

Distribution pattern and sequential sampling plan for chilli thrips, Scirtothrips dorsalis Hood (Thripidae: Thysanoptera) - N. R. Prasannakumar; B. S. Rajendra Prasad; P. Shivarama Bhat (International Journal of Tropical Insect Science, 2020)

On the Variability of Cold Wave Episodes Over Northwest India Using an NGFS Retrospective Analysis - A. Sandeep; V. S. Prasad (Pure and Applied Geophysics, 2020)

Complex relationship between DNA methylation and gene expression due to Lr28 in wheat-leaf rust pathosystem - Gautam Saripalli; Chanchal Sharma; Tinku Gautam; Kalpana Singh; Neelu Jain; Pramod Prasad; J. K. Roy; J. B. Sharma; P. K. Sharma; K. V. Prabhu; H. S. Balyan; P. K. Gupta (Molecular Biology Reports, 2020)

Induction of growth cessation by acacetin via β-catenin pathway and apoptosis by apoptosis inducing factor activation in colorectal carcinoma cells - Nupoor Prasad; Jiten R. Sharma; Umesh C. S. Yadav (Molecular Biology Reports, 2020)

Analysis and Integration of Surface and Subsurface Information of Different Bridges - Sunni Kanta Prasad Kushwaha; S. Raghavendra; Hina Pande; S. Agrawal (Journal of the Indian Society of Remote Sensing, 2020)

Terminalia bellirica (Gaertn.) Roxb fruit exerts anti-inflammatory effect via regulating arachidonic acid pathway and pro-inflammatory cytokines in lipopolysaccharide-induced RAW 264.7 macrophages - Kuriakose Jayesh; Raj Karishma; A. Vysakh; Prasad Gopika; M. S. Latha (Inflammopharmacology, 2020)

Studies on the Solid Oxide Cell Perovskite Electrode Materials for Soot Oxidation Activity - Chaitra S. Shenoy; Sunaina S. Patil; P. Govardhan; Atmuri Shourya; Hari Prasad Dasari; M. B. Saidutta; Harshini Dasari (Emission Control Science and Technology, 2019)

Impact of Moisture Transport and Boundary Layer Processes on a Very Severe Cyclonic Storm Using the WRF Model - S. S. V. S. Ramakrishna; Nellipudi Nanaji Rao; B. Ravi Srinivasa Rao; P. Srinivasa Rao; C. V. Srinivas; Hari Prasad Dasari (Pure and Applied Geophysics, 2019)

Measuring Respiration in Isolated Murine Brain Mitochondria: Implications for Mechanistic Stroke Studies - Jared A. Sperling; Siva S. V. P. Sakamuri; Aaron L. Albuck; Venkata N. Sure; Wesley R. Evans; Nicholas R. Peterson; Ibolya Rutkai; Ricardo Mostany; Ryousuke Satou; Prasad V. G. Katakam (NeuroMolecular Medicine, 2019)

Wilt disease of castor: an overview - M. Santha Lakshmi Prasad; M. A. Raoof; B. Gayatri; K. Anjani; C. Lavanya; R. D. Prasad; S. Senthilvel (Indian Phytopathology, 2019)

Impact of differences in the decaying phase of El Niño on South and East Asia summer monsoon in CMIP5 models - Gangiredla Srinivas; Jasti S. Chowdary; Chellappan Gnanaseelan; Anant Parekh; Ramu Dandi; Koneru Venkata Siva Rama Prasad; Chennu Venkata Naidu (International Journal of Climatology, 2019)
The present study examined the ability of Coupled Model Intercomparison Project phase 5 (CMIP5) models in representing the differences in decaying phases of El Niño and their impact on south Asia and east Asia monsoon during June and July (JJ), the early summer monsoon months. El Niño decay is classified into three categories, based on the timing of decay with respect to the summer season after the peak phase of El Niño. Analysis suggests that many CMIP5 models are able to capture the differences in the decaying phase of El Niño. Observed rainfall anomalies are positive over most parts of south and east Asia regions during the early decay (ED) years mainly due to anomalous Tropical Indian Ocean (TIO) Sea Surface Temperature (SST) warming and La Niña like forcing from the eastern Pacific. Most models show significant skill in capturing the positive rainfall anomalies over south Asia and TIO SST warming in ED years. However, many models have failed to represent east Asian rainfall anomalies due to weak Western North Pacific (WNP) anticyclone and its association with El Niño‐Southern Oscillation. In case of mid‐decay (MD) years, observed rainfall anomalies over south Asia is negative especially in the monsoon trough region and positive over east Asian region. Low‐level divergence induced by anomalous WNP anticyclone extending to head Bay of Bengal and Gangetic Plain region in MD years caused low rainfall over south Asia. These features are however not well organized in many CMIP5 models. In no decay (ND) years, the rainfall anomalies over south and east Asia regions are negative in almost all the CMIP5 models, which is consistent with the observations. This study highlights the importance of proper representation of differences in the decaying phase of El Niño and associated teleconnections in CMIP5 models.

Managing nutrient flows in Indian urban and peri-urban livestock systems - Cadaba S. Prasad; Samireddypalle Anandan; Nisarani K. S. Gowda; Eva Schlecht; Andreas Buerkert (Nutrient Cycling in Agroecosystems, 2019)

Biological factors influencing the degradation of water-soluble metal working fluids - H. V. Puneeth; M. S. Ganesha Prasad (Sustainable Water Resources Management, 2019)

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

The Assimilation of Remote Sensing-Derived Soil Moisture Data into a Hydrological Model for the Mahanadi Basin, India - Soumya S. Behera; Bhaskar Ramchandra Nikam; Mukund S. Babel; Vaibhav Garg; Shiv Prasad Aggarwal (Journal of the Indian Society of Remote Sensing, 2019)

Performance of a very high-resolution global forecast system model (GFS T1534) at 12.5 km over the Indian region during the 2016–2017 monsoon seasons - P Mukhopadhyay; V S Prasad; R Phani Murali Krishna; Medha Deshpande; Malay Ganai; Snehlata Tirkey; Sahadat Sarkar; Tanmoy Goswami; C J Johny; Kumar Roy; M Mahakur; V R Durai; et al. (Journal of Earth System Science, 2019)

Suppressed biological production in the coastal waters off Visakhapatnam, India under the impact of the very severe cyclonic storm Hudhud - V V S S Sarma; T N R Srinivas; V R Kumari; M H K Prasad; H B Dalabehera; U Satyanarayana; G D Rao; D B Rao; Y S Paul; V S N Murty; M S Krishna; N P C Reddy (Journal of Earth System Science, 2019)

Perturbations in Earth’s Atmosphere over An Indian Region during the Total Solar Eclipse on 22 July 2009 - S. B. Surendra Prasad; Vinay Kumar; K. Krishna Reddy; S. K. Dhaka; Shristy Malik; M. Venkatarami Reddy; U. Murali Krishna (Journal of Meteorological Research, 2019)

Rust pathogen effectors: perspectives in resistance breeding - Pramod Prasad; Siddanna Savadi; S. C. Bhardwaj; O. P. Gangwar; Subodh Kumar (Planta, 2019)

Computational Predictability of Microsponge Properties Using Different Multivariate Models - Paresh R. Mahaparale; Bhavani Prasad Vinjamuri; Mayura S. Chavan; Mahavir B. Chougule; Rahul V. Haware (AAPS PharmSciTech, 2019)

Pro-inflammatory cytokine expression studies of subclinical and clinical endometritis in endometrial tissues of buffaloes - A. R. Bhadaniya; M. C. Prasad; H. H. Savsani; V. A. Kalaria; D. T. Fefar; B. S. Mathpati; B. B. Javia (Tropical Animal Health and Production, 2019)

Validation and Impact of SCATSAT-1 Scatterometer Winds - C. J. Johny; Sanjeev Kumar Singh; V. S. Prasad (Pure and Applied Geophysics, 2019)

Evaluation of precipitation forecasts from 3D-Var and hybrid GSI-based system during Indian summer monsoon 2015 - Sanjeev Kumar Singh; V. S. Prasad (Meteorology and Atmospheric Physics, 2019)

Ecology and Use of Lantana camara in India - Girish C. S. Negi; Subrat Sharma; Subash C.R. Vishvakarma; Sher S. Samant; Rakesh K. Maikhuri; Ram C. Prasad; Lok M. S. Palni (The Botanical Review, 2019)

Genetic Status and Endosymbionts Diversity of Bemisia tabaci (Gennadius) on Hosts Belonging to Family Malvaceae in India - T R Hashmi; S R Devi; A Ahmad; N M Meshram; R Prasad (Neotropical Entomology, 2019)

L-band scintillation and TEC variations on St. Patrick’s Day storm of 17 March 2015 over Indian longitudes using GPS and GLONASS observations - V K D Srinivasu; D S V V D Prasad; K Niranjan; Gopi K Seemala; K Venkatesh (Journal of Earth System Science, 2019)

Marker assisted introgression of a major bacterial blight resistance gene, Xa38 into a rice maintainer line, APMS 6B - A. Yugander; R. M. Sundaram; K. Singh; M. S. Prasad; A. S. Hari Prasad; M. S. Madhav; Gouri Sankar Laha (Indian Phytopathology, 2019)

Physiologic specialization and shift in Puccinia triticina pathotypes on wheat in Indian subcontinent during 2013–2016 - S. C. Bhardwaj; O. P. Gangwar; Pramod Prasad; Subodh Kumar; Hanif Khan; Neha Gupta (Indian Phytopathology, 2019)

Monitoring progression of the die back pathogen Phomopsis azadirachtae in neem seedlings - Prithvi S. Shirahatti; Ramith Ramu; S. Nanjunda Swamy; Joseph Jeyabalaji Kingston; M. N. Nagendra Prasad (Indian Phytopathology, 2019)

The role of the Indian Summer Monsoon variability on Arabian Peninsula summer climate - Raju Attada; Hari Prasad Dasari; Anant Parekh; Jasti S. Chowdary; Sabique Langodan; Omar Knio; Ibrahim Hoteit (Climate Dynamics, 2019)

Increased virulence in Pseudomonas aeruginosa at pathological glucose levels - Prathiksha Prabhakara Alva; Ravi Prasad; Thejaswini Venkatesh; Padmanaban S. Suresh; Ramya Premanath (Infectious Diseases, 2019)

Role of Planetary Boundary Layer Processes in the Simulation of Tropical Cyclones Over the Bay of Bengal - K. Vijaya Kumari; S. Karuna Sagar; Yesubabu Viswanadhapalli; Hari Prasad Dasari; S. Vijaya Bhaskara Rao (Pure and Applied Geophysics, 2019)

Impact of radiance data assimilation on the prediction performance of cyclonic storm SIDR using WRF-3DVAR modelling system - K. S. Singh; M. Mandal; Prasad K. Bhaskaran (Meteorology and Atmospheric Physics, 2019)

Numerical modeling of methane gas production from hydrate reservoir of Krishna Godhavari basin by depressurization - N. Vedachalam; S. Ramesh; V. B. N. Jyothi; N. Thulasi Prasad; D. Sathianarayanan; R. Ramesh; G. A. Ramadass (Marine Georesources & Geotechnology, 2019)

Studies on root anatomy, morphology and physiology of rice grown under aerobic and anaerobic conditions - Amol S. Phule; Kalyani M. Barbadikar; M. S. Madhav; D. Subrahmanyam; P. Senguttuvel; M. B. B. Prasad Babu; P. Ananda Kumar (Physiology and Molecular Biology of Plants, 2019)

Development of Regional Algorithm to Estimate Suspended Sediment Concentration (SSC) Based on the Remotely Sensed Reflectance and Field Observations for the Hooghly Estuary and West Bengal Coastal Waters - J. Selvin Pitchaikani; R. Ramakrishnan; Prasad K. Bhaskaran; D. Ilangovan; A. S. Rajawat (Journal of the Indian Society of Remote Sensing, 2019)

Surface air temperature variability over the Arabian Peninsula and its links to circulation patterns - Raju Attada; Hari Prasad Dasari; Jasti S. Chowdary; Ramesh Kumar Yadav; Omar Knio; Ibrahim Hoteit (International Journal of Climatology, 2019)
This study investigates the long‐term variability of surface air temperature (SAT) over the Arabian Peninsula (AP), using data from the Climate Research Unit (TS 3.22) for the 1960–2010 period. The long‐term climatology suggests that the warmest AP mean temperatures occur during summer, with the highest temperatures over the northern AP (NAP), due to the monsoon–desert mechanism. During winter, the NAP exhibits low SATs under the influence of western disturbances originating from the Mediterranean. The southwestern AP exhibits the lowest temperatures because of its proximity to the Arabian Sea cold waters, and also because of the orographic effects. The inter‐annual variability of the SAT is stronger during winters. A linear trend analysis reveals a significant increase in the SAT anomaly (0.10 °C/decade) across the AP, consistently with the global temperature anomalies. Besides the local convective heating, summer SAT variability is associated with the weakening of the Asian jet stream and a Rossby wave train from the Indian Ocean. This variability is also influenced by the anomalous low pressure over the North Atlantic and the Sahara, a high‐pressure system over Siberia and the northwest Pacific. Both in spring and autumn, sea surface temperature (SST) variations over the Indo‐western Pacific are highly influenced the AP SATs, whereas winter SATs are modulated by the subtropical jet stream and the Middle East jet stream. In all seasons, the AP SAT is strongly influenced by the SST variations over the tropical oceans. The temperature variability is closely associated with the El Niño–Southern Oscillation (ENSO), North Atlantic Oscillation (NAO) and Arctic Oscillation (AO). The warm phase of ENSO (i.e., El Niño) is one possible reason behind the inter‐annual increase in SAT over the southern AP. The negative phases of NAO and AO also play a role in increasing AP SAT.

Design, Development, and Assessment of Lake Water Purification System Through Solar Concentration Technique - Charan Nallode; Rakesh C; Ganesha Prasad M S; Adhvaith M; Ravi Kumar (Water Conservation Science and Engineering, 2018)

An assessment on oil spill trajectory prediction: Case study on oil spill off Ennore Port - S J Prasad; T M Balakrishnan Nair; Hasibur Rahaman; S S C Shenoi; T Vijayalakshmi (Journal of Earth System Science, 2018)

Correction to: A review on fisheries and conservation status of Asian horseshoe crabs - B. Akbar John; B. R. Nelson; Hassan I. Sheikh; S. G. Cheung; Yusli Wardiatno; Bisnu Prasad Dash; Keiji Tsuchiya; Yumiko Iwasaki; Siddhartha Pati (Biodiversity and Conservation, 2018)

A review on fisheries and conservation status of Asian horseshoe crabs - B. Akbar John; B. R. Nelson; Hassan I. Sheikh; S. G. Cheung; Yusli Wardiatno; Bisnu Prasad Dash; Keiji Tsuchiya; Yumiko Iwasaki; Siddhartha Pati (Biodiversity and Conservation, 2018)

Effect of Soil Amendments and Land Use Systems on Surface Cracks, Soil Properties and Crop Yield in a Vertisol - J. Somasundaram; R. K. Singh; S. N. Prasad; Ashok Kumar; Shakir Ali; N. K. Sinha; R. S. Chaudhary; M. Mohanty; B. L. Lakaria; M. Sankar; Rattan Lal (Agricultural Research, 2018)

An EMS-induced new sequence variant, TEMS5032, in the coding region of SRS3 gene leads to shorter grain length in rice (Oryza sativa L.) - Umakanta Ngangkham; Manoj Nath; Prasad Dokku; S. V. Amitha Mithra; Srinivasan Ramamurthy; Nagendra K. Singh; R. P. Sharma; Trilochan Mohapatra (Journal of Applied Genetics, 2018)

Improvement of blast resistance of the popular high-yielding, medium slender-grain type, bacterial blight resistant rice variety, Improved Samba Mahsuri by marker-assisted breeding - G. Rekha; V. Abhilash Kumar; B. C. Viraktamath; K. Pranathi; M. B. V. N. Kousik; B. Laxmi Prasanna; C. Backiyalakshmi; Pragya Sinha; R. K. Ravindra; S. Bhaskar; S. K. Hajira; C. H. Balachiranjeevi; et al. (Journal of Plant Biochemistry and Biotechnology, 2018)

Hepcidin and Ferritin: Important Mediators in Inflammation Associated Anemia in Systemic Lupus Erythematosus Patients - Neeraja Kunireddy; Rachel Jacob; Siraj Ahmed Khan; B. Yadagiri; K. S. S. Sai Baba; I. Rajendra Vara Prasad; Iyyapu Krishna Mohan (Indian Journal of Clinical Biochemistry, 2018)

Detection of Chromosomal AmpC, bla CTX-M in Extended Spectrum Beta Lactamase Producing Escherichia coli in Seafood Processing Effluent - G. K. Sivaraman; Deesha Vanik; M. M. Prasad; S. Visnuvinayagam; K. A. Basha; R. K. Nadella; A. K. Jha; Chandni Vaja (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Quantitative Analysis of Phyllanthus Species for Bioactive Molecules Using High-Pressure Liquid Chromatography and Liquid Chromatography–Mass Spectrometry - A. Muthusamy; E. R. Sanjay; H. N. Nagendra Prasad; M. Radhakrishna Rao; B. Manjunath Joshi; S. Padmalatha Rai; K. Satyamoorthy (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Temporal Transcriptional Changes in SAR and Sugar Transport-Related Genes During Wheat and Leaf Rust Pathogen Interactions - Siddanna Savadi; Pramod Prasad; S. C. Bhardwaj; Prem Lal Kashyap; O. P. Gangwar; Hanif Khan; Subodh Kumar (Journal of Plant Growth Regulation, 2018)

A novel high-throughput assay for respiration in isolated brain microvessels reveals impaired mitochondrial function in the aged mice - Venkata N. Sure; Siva S. V. P. Sakamuri; Jared A. Sperling; Wesley R. Evans; Ivan Merdzo; Ricardo Mostany; Walter L. Murfee; David W. Busija; Prasad V. G. Katakam (GeroScience, 2018)

Evaluation of site effects on ground motions based on equivalent linear site response analysis and liquefaction potential in Chennai, south India - Subhadra Nampally; Simanchal Padhy; S. Trupti; P. Prabhakar Prasad; T. Seshunarayana (Journal of Seismology, 2018)

Enhanced Exciplex Emission of Pyrene Thin Films Doped by Perylene: Structural, Photophysical and Morphological Investigation - Netaji K. Desai; Prasad G. Mahajan; Sawanta S. Mali; Govind B. Kolekar; Shivajirao R. Patil (Journal of Fluorescence, 2018)

Biological pest control using cannibalistic predators and with provision of additional food: a theoretical study - K. Durga Prasad; B. S. R. V. Prasad (Theoretical Ecology, 2018)

Implementation of RISAT-1 Hybrid Polarimetric Decomposition Techniques and Analysis Using Corner Reflector Data - P. V. Jayasri; K. Niharika; Manoj Joseph; H. S. V. Usha Sundari Ryali; C. V. Ramana Sarma; E. V. S. Sita Kumari; A. V. V. Prasad (Journal of the Indian Society of Remote Sensing, 2018)

Lupeol induces S-phase arrest and mitochondria-mediated apoptosis in cervical cancer cells - Nupoor Prasad; Akash Sabarwal; Umesh C S Yadav; Rana P Singh (Journal of Biosciences, 2018)

Measurement of respiratory function in isolated cardiac mitochondria using Seahorse XFe24 Analyzer: applications for aging research - Siva S. V. P. Sakamuri; Jared A. Sperling; Venkata N. Sure; Monica H. Dholakia; Nicholas R. Peterson; Ibolya Rutkai; Padmini S. Mahalingam; Ryosuke Satou; Prasad V. G. Katakam (GeroScience, 2018)

Solvent Dependence on Structure and Electronic Properties of 7-(Diethylamino) - 2H -1- Benzopyran-2- one (C-466) Laser Dye - C. G. Renuka; Y. F. Nadaf; G. Sriprakash; S. Rajendra Prasad (Journal of Fluorescence, 2018)

Potentially inappropriate medications in community-dwelling older adults undertaken as a comprehensive geriatric risk assessment - Sharmin S. Bala; Sujita W. Narayan; Prasad S. Nishtala (European Journal of Clinical Pharmacology, 2018)

Intra‐annual variability of heat wave episodes over the east coast of India - A. Sandeep; V. S. Prasad (International Journal of Climatology, 2018)
India is very prone to heat waves during April–June. The intra‐annual variability of heat wave episodes over the east coast of India has been studied using 16‐year NCMRWF global forecast system (NGFS) retrospective data. The objective of this study is threefold: (1) identification of heat wave episodes over the east coast of India, (2) intra‐annual variability of heat wave episodes, and (3) which physical mechanism(s) is responsible for its occurrence and long‐lasting? A total of ten heat wave episodes (100 hot days) were obtained for the period 2000–2015. The intensity of heat wave is found to be maximum (minimum) for 2015 (2007) episode. The average duration of heat wave episodes was 10 days, with the longest episode lasting for 20 days in the year 2003. Moreover, an average duration of severe heat wave is 3.5 days longer than that of a normal heat wave. The common feature observed in all heat wave cases is the presence of anticyclone in the upper troposphere and associated persistence high. This can cause sinking motion, which leads to surface warming due to adiabatic compression. The lack of soil moisture (SM) induces a positive feedback between the surface and the air above it, which amplifies the sensible heating and thereby increases surface temperature. The prevailed westerly anomalies over the study region which reduce the land–sea breeze result in heat wave. The heat wave episodes exhibit a significant intra‐annual variability. Intensity of heat waves averaged over the east coast of India has shown an increase of 0.06 °C per heat wave. The geopotential height anomaly, vertical velocity, and SM exhibit significant intra‐annual variability between the episodes and become decisive parameters for the maintenance and variability. The correlation coefficient between the maximum temperature and SM is found to be −0.56, indicating the importance of SM regulating the intensity of heat waves.

Impact of Aquarius Sea-Surface Salinity Assimilation in Improving the Ocean Analysis Over Indian Ocean - Vivek Seelanki; P. Sreenivas; K. V. S. R. Prasad (Marine Geodesy, 2018)

Thalassiosira mala (Bacillariophyta), a potentially harmful, marine diatom from Chilka Lake and other coastal localities of Odisha, India: Nomenclature, frustule morphology and global biogeography - Akshinthala K S K Prasad; James A Nienow; Eric Lochner (Journal of Biosciences, 2018)

Population behaviour of predominant and virulent pathotypes of Puccinia triticina causing wheat brown rust in India - Neha Gupta; S. C. Bhardwaj; T. R. Sharma; Pramod Prasad; O. P. Gangwar; Subodh Kumar (Indian Phytopathology, 2018)

A population-level study examining discontinuation of statins in older people with dementia - Sujita W. Narayan; Sarah N. Hilmer; Prasad S. Nishtala (European Journal of Clinical Pharmacology, 2018)

Association between mean and interannual equatorial Indian Ocean subsurface temperature bias in a coupled model - G. Srinivas; Jasti S. Chowdary; C. Gnanaseelan; K. V. S. R. Prasad; Ananya Karmakar; Anant Parekh (Climate Dynamics, 2018)

Reliability and validity of telephonic Barthel Index: an experience from multi-centric randomized control study - Kameshwar Prasad; Amit Kumar; Shubham Misra; Arun K. Yadav; Sarat Johri; R. S. Sarkar; S. P. Gorthi; K. M. Hassan; Sudesh Prabhakar; Usha Kant Misra; Pradeep Kumar (Acta Neurologica Belgica, 2018)

Terpenoid composition of essential oil from a new chemotype of Selinum wallichianum Raizada & Saxena - Deepshikha Joshi; Anand B. Melkani; Manoj K. Nailwal; Rajendra Prasad; Lalit S. Bisht (Natural Product Research, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Rotula aquatica Lour attenuates secretion of proinflammatory mediators and cytokines in lipopolysaccharide-induced inflammatory responses in murine RAW 264.7 macrophages - A. Vysakh; Prasad Gopika; Kuriakose Jayesh; Raj Karishma; M. S. Latha (Inflammopharmacology, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Curcumin Pretreatment Decreases Absorption of Phenacetin (Cytochrome P450 1A2 Substrate), Without Altering its Disposition Kinetics in Rats - V. G. N. V. Prasad; Ch. Vivek; M. Arjuna Rao; G. S. Rao (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

β-carotene at physiologically attainable concentration induces apoptosis and down-regulates cell survival and antioxidant markers in human breast cancer (MCF-7) cells - G. Sowmya Shree; K. Yogendra Prasad; H. S. Arpitha; U. R. Deepika; K. Nawneet Kumar; Priya Mondal; P. Ganesan (Molecular and Cellular Biochemistry, 2017)

IGF1 stimulates differentiation of primary follicles and their growth in ovarian explants of zebrafish (Danio rerio) cultured in vitro - Pancharatna A Katti; Sheetal S Narvekar; Basavaraj B Goundadkar; Prasad A Deshpande (Journal of Biosciences, 2017)

Antimicrobial Efficacy of Synthetic Pyranochromenones and (Coumarinyloxy)acetamides - Abhishek K. Singh; Suchita Prasad; Bipul Kumar; Shiv Kumar; Amitesh Anand; Shashank S. Kamble; Sunil K. Sharma; Hemant K. Gautam (Indian Journal of Microbiology, 2017)

Development and validation of a Medicines Comorbidity Index for older people - Sujita W. Narayan; Prasad S. Nishtala (European Journal of Clinical Pharmacology, 2017)

Identifying some additional rust resistance genes in Indian wheat varieties using robust markers - H. Khan; S.C. Bhardwaj; O.P. Gangwar; P. Prasad; P.L. Kashyap; S. Savadi; S. Kumar; R. Rathore (Cereal Research Communications, 2017)

Estimating carbon sequestration potential of existing agroforestry systems in India - Ajit; S. K. Dhyani; A. K. Handa; Ram Newaj; S. B. Chavan; Badre Alam; Rajendra Prasad; Asha Ram; R. H. Rizvi; Amit Kumar Jain; Uma; Dharmendra Tripathi; et al. (Agroforestry Systems, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Nanotechnology and its role in agro-ecosystem: a strategic perspective - A. Singh; S. M. Prasad (International Journal of Environmental Science and Technology, 2017)

Virulence profiling of Xanthomonas oryzae pv. oryzae isolates, causing bacterial blight of rice in India - A. Yugander; R. M. Sundaram; D. Ladhalakshmi; S. K. Hajira; V. Prakasam; M. S. Prasad; M. Sheshu Madhav; V. Ravindra Babu; G. S. Laha (European Journal of Plant Pathology, 2017)

Elasmobranch fauna from the upper most part of the Cretaceous Bagh Group, Narmada valley, India - Guntupalli V. R. Prasad; Vishal Verma; Ashok Sahni; Ranjit S. Lourembam; Priyadarshini Rajkumari (Island Arc, 2017)
In India, Cretaceous elasmobranchs are known from the uppermost Cretaceous Deccan intertrappean sedimentary sequences of peninsular India and the lower Upper Cretaceous (Cenomanian) Karai Formation of the Cauvery basin, South India. The intertrappean elasmobranchs are represented mainly by rays and skates, whereas the Karai fauna is known by hexanchiform, squaliform, and lamniform sharks. The latter assemblage is dominated by cool temperate water forms in addition to some cosmopolitan forms. Here new shark teeth recovered from the upper part of the marine Cretaceous Bagh Group, in the lower Narmada valley, Western India are described. This is the first detailed description of sharks from the Bagh Group and the first record of sharks from the youngest horizons (Coniacian to Late Maastrichtian) of this marine sedimentary sequence. The fauna, recovered from an oyster shell‐rich green sandstone at the top of the youngest geological unit (the Coralline Limestone) of the Bagh Group, is assigned to Ptychodus sp., Scapanorhynchus sp. aff. S. raphiodon (Agassiz, 1844), Cretodus sp. aff. C. crassidens (Dixon, 1850), Cretalamna sp., Squalicorax sp. aff. S. falcatus Agassiz, 1843, and Elasmobranchii indet. This assemblage, previously widely documented from the Cretaceous deposits of North and South Americas, Europe, North and West Africa, Far East and Near East, demonstrates that there is a clear change in elasmobranch faunal composition of India from cool temperate water forms in the early Late Cretaceous to essentially cosmopolitan forms in the Late Cretaceous.

Impact of Megha-Tropiques SAPHIR radiances in T574L64 global data assimilation and forecasting system at NCMRWF - Sanjeev Kumar Singh; V. S. Prasad (International Journal of Remote Sensing, 2017)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

Quality and Impact of Indian Doppler Weather Radar Wind Profiles: A Diagnostic Study - A. Sandeep; V. S. Prasad; C. J. Johny (Pure and Applied Geophysics, 2017)

A study of 2014 record drought in India with CFSv2 model: role of water vapor transport - S. S. V. S. Ramakrishna; V. Brahmananda Rao; B. R. Srinivasa Rao; D. Hari Prasad; N. Nanaji Rao; Roshmitha Panda (Climate Dynamics, 2017)

Evaluation of Abbreviated Impactor Measurements (AIM) and Efficient Data Analysis (EDA) for Dry Powder Inhalers (DPIs) Against the Full-Resolution Next Generation Impactor (NGI) - Megha Mohan; Sau Lee; Changning Guo; S. Prasad Peri; William H. Doub (AAPS PharmSciTech, 2017)

Water balance and water productivity of rice paddy in unpuddled sandy loam soil - Samuel Dagalo Hatiye; K. S. Hari Prasad; C. S. P. Ojha (Sustainable Water Resources Management, 2017)

In vitro propagation of Trichosanthus dioica Roxb. for nutritional security - Satyajit Saurabh; Dinesh Prasad; Ambarish S. Vidyarthi (Journal of Crop Science and Biotechnology, 2017)

The Appraisement of Antioxidant and Oxidant Status in Women Undergoing Surgical Menopause - Avneet Kaur; Pooja Negi; Veena Sarna; Rajendra Prasad; Bir S. Chavan; Anita Malhotra; Gurjit Kaur (Indian Journal of Clinical Biochemistry, 2017)

Cadmium toxicity-induced proline accumulation is coupled to iron depletion - P. Sharmila; P. Kusuma Kumari; Kavita Singh; N. V. S. R. K. Prasad; P. Pardha-Saradhi (Protoplasma, 2017)

Real-world risk of diabetes with antipsychotic use in older New Zealanders: a case-crossover study - Prasad S. Nishtala; Te-yuan Chyou (European Journal of Clinical Pharmacology, 2017)

Erratum to: Internal waves over the shelf in the western Bay of Bengal: a case study - Madhu Joshi; Ambarukhana Devendra Rao; Sachiko Mohanty; Himansu Kesari Pradhan; Vadlamani S. N. Murty; Koneru Venkata Siva Rama Prasad (Ocean Dynamics, 2017)

Internal waves over the shelf in the western Bay of Bengal: a case study - Madhu Joshi; Ambarukhana Devendra Rao; Sachiko Mohanty; Himansu Kesari Pradhan; Vadlamani S. N. Murty; Koneru Venkata Siva Rama Prasad (Ocean Dynamics, 2017)

Impact of 3D Var GSI-ENKF hybrid data assimilation system - V S Prasad; C J Johny; Jagdeep Singh Sodhi (Journal of Earth System Science, 2016)

Facility-based planning methodology for rural roads using spatial techniques - Anil Modinpuroju; C. S. R. K. Prasad; Mukesh Chandra (Innovative Infrastructure Solutions, 2016)
Provision of good rural roads to meet the public facilities changes the characteristics of rural transport. This paper aims at identifying the roads in a network for upgradation and maintenance based on the pavement and develop a methodology for prioritization of the roads using village facility indices. The study area is located in Warangal District, Telangana, India. Spatial analysis was carried out in the study area to identify the maximum coverage distance of the facility to design the village facility index using ArcGIS software. A priority list of the road links to upgradation works is prepared by calculating the link weight using gravity formula. A Geographic Information System (GIS)-based rural road database is developed, which will help the authorities in the road sector to expand the infrastructure facilities for current and future requirement. Practical applications of the model exhibit significant advantages over the general practices of rural road planning in India.

Marker-assisted improvement of the elite restorer line of rice, RPHR-1005 for resistance against bacterial blight and blast diseases - V. ABHILASH KUMAR; C. H. BALACHIRANJEEVI; S. BHASKAR NAIK; R. RAMBABU; G. REKHA; G. HARIKA; S. K. HAJIRA; K. PRANATHI; S. VIJAY; M. ANILA; H. K. MAHADEVASWAMY; M. KOUSIK; et al. (Journal of Genetics, 2016)

Performance evaluation of NCEP climate forecast system for the prediction of winter temperatures over India - M. M. Nageswararao; U. C. Mohanty; S. Kiran Prasad; Krishna K. Osuri; S. S. V. S. Ramakrishna (Theoretical and Applied Climatology, 2016)

Marker assisted introgression of blast (Pi-2 and Pi-54) genes in to the genetic background of elite, bacterial blight resistant indica rice variety, Improved Samba Mahsuri - K. Ratna Madhavi; R. Rambabu; V. Abhilash Kumar; S. Vijay Kumar; J. Aruna; S. Ramesh; R. M. Sundaram; G. S. Laha; M. Sheshu Madhav; V. Ravindra babu; M. Srinivas Prasad (Euphytica, 2016)

Isolated Archosaur teeth from the green sandstone capping the Coralline Limestone (Bagh Group) of the Narmada valley: Evidence for the presence of pre‐Late to Late Maastrichtian abelisaurids in India - Guntupalli V.R. Prasad; Vishal Verma; Pooja Grover; Rajkumari Priyadarshini; Ashok Sahni; Ranjit S. Lourembam (Island Arc, 2016)
Recent field prospecting in the Cretaceous sequences of the lower Narmada valley has led to the discovery of three isolated archosaur teeth from the upper part of marine Cretaceous rocks of the Bagh Group. The specimens were recovered by surface prospecting from an oyster‐bearing green sandstone bed occurring at the top of the Coralline Limestone (Coniacian) from a site near Phutibawri village, Dhar District, Madhya Pradesh , India . Of the three teeth recovered from this horizon, two are identified with abelisaurid dinosaurs and the third one with an indeterminate crocodile. The abelisaurid teeth conform to the premaxillary and maxillary tooth morphology of Majungasaurus and Indosuchus. Earlier reports of abelisaurid dinosaurs from India are from the Upper Cretaceous (Maastrichtian) Lameta Group of Jabalpur, Pisdura (Central India ) and Balasinor (Western India ) and Upper Cretaceous (Late Maastrichtian) Kallamedu Formation (South India ). As no associated age diagnostic fossils are found, the specimens described here are considered to represent pre‐Late to Late Maastrichtian age based on the known ages of the underlying and overlying formations. The new finds, therefore, document stratigraphically the oldest occurrence of abelisaurid dinosaurs known from the Indian subcontinent.

Marker-assisted introgression of the major bacterial blight resistance gene, Xa21 and blast resistance gene, Pi54 into RPHR-1005, the restorer line of the popular rice hybrid, DRRH3 - V. Abhilash Kumar; C. H. Balachiranjeevi; S. Bhaskar Naik; R. Rambabu; G. Rekha; K. R. Madhavi; G. Harika; S. Vijay; K. Pranathi; S. K. Hajira; A. Srivastava; H. K. Mahadevaswamy; et al. (Journal of Plant Biochemistry and Biotechnology, 2016)

Establishing a high throughput screening method for large scale phenotyping of castor genotypes for resistance to Fusarium wilt disease - Ranjan K. Shaw; Mobeen Shaik; Zubair Ahmed Mir; M. Santha Lakshmi Prasad; R. D. Prasad; S. Senthilvel (Phytoparasitica, 2016)

Genetic transformation and evaluation of two sweet sorghum genotypes for resistance to spotted stemborer, Chilo partellus (Swinhoe) - K. B. R. S. Visarada; G. Shyam Prasad; Monique. Royer (Plant Biotechnology Reports, 2016)

Bathymetric Mapping of Bhopal City Lower Lake Using IRS-P6: LISS-4 Imagery and Artificial Neural Network Technique - Arun Patel; S. K. Katiyar; Vishnu Prasad (Journal of the Indian Society of Remote Sensing, 2016)

Age-Dependent Alterations in the Interactions of NF-κB and N-myc with GLT-1/EAAT2 Promoter in the Pericontusional Cortex of Mice Subjected to Traumatic Brain Injury - Rajaneesh K. Gupta; S. Prasad (Molecular Neurobiology, 2016)

Identification and validation of novel alleles of rice blast resistant gene Pi54, and analysis of their nucleotide diversity in landraces and wild Oryza species - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; B. Umakanth; M. K. Pandey; M. S. Prasad; R. M. Sundaram; B. C. Viraktamath; V. Ravindra Babu (Euphytica, 2016)

Preparation and Photoluminescence of Sm 3+ Doped YAlO 3 Phosphor - Huma Nazli Baig; Jagjeet Kaur Saluja; D. Harnath; A. S. Sai Prasad; K. V. R. Murthy (Journal of Fluorescence, 2016)

Real-time prediction of movement, intensity and storm surge of very severe cyclonic storm Hudhud over Bay of Bengal using high-resolution dynamical model - Raghu Nadimpalli; Krishna K. Osuri; Sujata Pattanayak; U. C. Mohanty; M. M. Nageswararao; S. Kiran Prasad (Natural Hazards, 2016)

Impact of hybrid GSI analysis using ETR ensembles - V S Prasad; C J Johny (Journal of Earth System Science, 2016)

Potential Species Replacements for Black Ash (Fraxinus nigra) at the Confluence of Two Threats: Emerald Ash Borer and a Changing Climate - Louis Iverson; Kathleen S. Knight; Anantha Prasad; Daniel A. Herms; Stephen Matthews; Matthew Peters; Annemarie Smith; Diane M. Hartzler; Robert Long; John Almendinger (Ecosystems, 2016)

Further evidence for the genetic basis of qualitative traits and their linkage relationships in dolichos bean (Lablab purpureus L.) - C. M. KEERTHI; S. RAMESH; M. BYREGOWDA; A. MOHAN RAO; B. S. RAJENDRA PRASAD; P. V. VAIJAYANTHI (Journal of Genetics, 2016)

Thermal Processing of PVP- and HPMC-Based Amorphous Solid Dispersions - Justin S. LaFountaine; Leena Kumari Prasad; Chris Brough; Dave A. Miller; James W. McGinity; Robert O. Williams (AAPS PharmSciTech, 2016)

Uncertainty Analysis of Looped Water Distribution Networks Using Linked EPANET-GA Method - P . Sivakumar; R. K. Prasad; S. Chandramouli (Water Resources Management, 2016)

Assessing village-level carbon balance due to greenhouse gas mitigation interventions using EX-ACT model - Ch. Srinivasarao; Y. Sudha Rani; V. Girija Veni; K. L. Sharma; G. R. Maruthi Sankar; J. V. N. S. Prasad; Y. G. Prasad; K. L. Sahrawat (International Journal of Environmental Science and Technology, 2016)

Detection of Quorum Sensing Molecules and Biofilm Formation in Ralstonia solanacearum - J. Shiva Kumar; S. Umesha; K. Shiva Prasad; P. Niranjana (Current Microbiology, 2015)

Novel imaging findings in two cases of biotinidase deficiency-a treatable metabolic disorder - Maya Dattatraya Bhat; P. S. Bindu; Rita Christopher; Chandrajit Prasad; Abha Verma (Metabolic Brain Disease, 2015)

Isolation of Mycobacterium tuberculosis from Antelope cervicapra and Gazelle bennettii in India and confirmation by molecular tests - F. Mukherjee; V. S. Bahekar; A. Prasad; S. K. Rana; A. Kanani; G. K. Sharma; V. A. Srinivasan (European Journal of Wildlife Research, 2015)

Impact of SARAL/AltiKa-Derived Sea Level Anomaly in a Data Assimilative Ocean Prediction System for the Indian Ocean - Smitha Ratheesh; Rashmi Sharma; K. V. S. R. Prasad; Sujit Basu (Marine Geodesy, 2015)

Synthesis, anticancer and molecular docking studies of benzofuran derivatives - Purawarga Mathada Gurubasavaraja Swamy; Yejalla Rajendra Prasad; Hire Mathada Ashvini; D. Giles; Byrappa Venkataraju Shashidhar; Y. S. Agasimundin (Medicinal Chemistry Research, 2015)

Canopy Temperature as a Selection Parameter for Grain Yield and Its Components in Durum Wheat Under Terminal Heat Stress in Late Sown Conditions - Amit Gautam; S. V. Sai Prasad; Anjana Jajoo; Divya Ambati (Agricultural Research, 2015)

Inhibition of Alzheimer’s BACE-1 by 2,6-dialkyl-4-chromon-3-yl-1,4-dihydropyridine-3,5-dicarboxylates - Nima Razzaghi-Asl; Neha Aggarwal; Smriti Srivastava; Virinder S. Parmar; Ashok K. Prasad; Ramin Miri; Luciano Saso; Omidreza Firuzi (Medicinal Chemistry Research, 2015)

Variability in stratification and flushing times of the Gautami–Godavari estuary, India - B SRIDEVI; V V S S SARMA; T V R MURTY; Y SADHURAM; N P C REDDY; K VIJAYAKUMAR; N S N RAJU; CH JAWAHAR KUMAR; Y S N RAJU; R LUIS; M D KUMAR; K V S R PRASAD (Journal of Earth System Science, 2015)

Biodegradation of azo dye Direct Orange 16 by Micrococcus luteus strain SSN2 - S. Singh; S. Chatterji; P. T. Nandini; A. S. A. Prasad; K. V. B. Rao (International Journal of Environmental Science and Technology, 2015)

Assessment of possibility of saltwater intrusion in the central Godavari delta region, Southern India - Lagudu Surinaidu; Velidi V. S. Gurunadha Rao; Jampani Mahesh; Patury Rajendra Prasad; Gopu Tamma Rao; Vempati Subramanya Sarma (Regional Environmental Change, 2015)

Microbial Evaluation of Groundwater and its Implications on Redox Condition of a Multi-Layer Sedimentary Aquifer System - Tirumalesh Keesari; K. L. Ramakumar; M. Bala Krishna Prasad; S. Chidambaram; Petha Perumal; D. Prakash; N. Nawani (Environmental Processes, 2015)

Development- and age-related alterations in the expression of AMPA receptor subunit GluR2 and its trafficking proteins in the hippocampus of male mouse brain - Surya P. Pandey; Rakesh Rai; Pankaj Gaur; S. Prasad (Biogerontology, 2015)

Nucleotide variation and identification of novel blast resistance alleles of Pib by allele mining strategy - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; M. S. Prasad; V. Ravindra Babu (Physiology and Molecular Biology of Plants, 2015)

Latitudinal variation in the occurrence of GPS L-band scintillations associated with the day-to-day changes in TEC, h′F and the E×B drift velocity and their impact on GPS satellite signals - K Venkatesh; P V S Rama Rao; Gopi K Seemala; D S V V D Prasad (Journal of Earth System Science, 2015)

Development of a simple and reliable species-specific detection of Phomopsis azadirachtae, using the translation elongation factor 1-alpha gene - Prithvi S. Shirahatti; Ramith Ramu; C. R. Adkar Purushothama; M. N. Nagendra Prasad (European Journal of Plant Pathology, 2015)

Nanotherapeutic Approach for Opiate Addiction Using DARPP-32 Gene Silencing in an Animal Model of Opiate Addiction - T. A. Ignatowski; R. Aalinkeel; J. L. Reynolds; B. B. Nair; D. E. Sykes; C. P. K. Gleason; W. C. Law; M. J. Mammen; P. N. Prasad; S. A. Schwartz; Supriya D. Mahajan (Journal of Neuroimmune Pharmacology, 2015)

The pearl millet mitogen-activated protein kinase PgMPK4 is involved in responses to downy mildew infection and in jasmonic- and salicylic acid-mediated defense - Prasad Melvin; S. Ashok Prabhu; Mariswamy Veena; Sekhar Shailasree; Morten Petersen; John Mundy; Shekar H. Shetty; K. Ramachandra Kini (Plant Molecular Biology, 2015)

Synthesis and mosquito larvicidal activity of furanochalcones and furanoflavonoids analogous to karanjin - Susarla R. Satyavani; Sanjit Kanjilal; Muthineni S. Rao; Rachapudi B. N. Prasad; Upadyayula S. N. Murthy (Medicinal Chemistry Research, 2015)

Toxicological impacts of a botanical pesticide, azadirachtin on corpuscles of Stannius of stinging catfish, Heteropneustes fossilis - A. Kumar; M. Prasad; S. K. Srivastav; N. Suzuki; A. K. Srivastav (International Journal of Environmental Science and Technology, 2015)

Pharmacogenetic associations of the type-3 metabotropic glutamate receptor (GRM3) gene with working memory and clinical symptom response to antipsychotics in first-episode schizophrenia - Jeffrey R. Bishop; James L. Reilly; Margret S. H. Harris; Shitalben R. Patel; Rick Kittles; Judith A. Badner; Konasale M. Prasad; Vishwajit L. Nimgaonkar; Matcheri S. Keshavan; John A. Sweeney (Psychopharmacology, 2015)

Remediation of heavy metal contaminated ecosystem: an overview on technology advancement - A. Singh; S. M. Prasad (International Journal of Environmental Science and Technology, 2015)

A review on common vegetables and legumes as promising plant-based natural coagulants in water clarification - S. Y. Choy; K. M. N. Prasad; T. Y. Wu; R. N. Ramanan (International Journal of Environmental Science and Technology, 2015)

Impact of Doppler weather radar data on thunderstorm simulation during STORM pilot phase—2009 - S. Kiran Prasad; U. C. Mohanty; A. Routray; Krishna K. Osuri; S. S. V. S. Ramakrishna; Dev Niyogi (Natural Hazards, 2014)

Impact of period and timescale of FDDA analysis nudging on the numerical simulation of tropical cyclones in the Bay of Bengal - V. Yesubabu; C. V. Srinivas; S. S. V. S. Ramakrishna; K. B. R. R. Hari Prasad (Natural Hazards, 2014)

Synthesis, biological evaluation, and molecular docking studies of N-(α-acetamido cinnamoyl) aryl hydrazone derivatives as antiinflammatory and analgesic agents - Galla Rajitha; Koganti V. S. R. G. Prasad; Amineni Umamaheswari; Dibyabhaba Pradhan; Koganti Bharathi (Medicinal Chemistry Research, 2014)

Genetic characterization and pathogenicity assessment of Newcastle disease virus isolated from wild peacock - Sagar A. Khulape; Satish S. Gaikwad; Madhan Mohan Chellappa; Bishnu Prasad Mishra; Sohini Dey (Virus Genes, 2014)

Electrical resistivity imaging over natural (in situ) geological samples using physical model studies - Rajesh Rekapalli; Padmavathi Devi P; V. S. Sarma; P. Rajendra Prasad (Arabian Journal of Geosciences, 2014)

Alterations in the Sp1 binding and Fmr-1 gene expression in the cortex of the brain during maturation and aging of mouse - Pankaj Gaur; S. Prasad (Molecular Biology Reports, 2014)

The search for the primary tumor in metastasized gastroenteropancreatic neuroendocrine neoplasm - D. Kaemmerer; N. Posorski; F. von Eggeling; G. Ernst; D. Hörsch; R. P. Baum; V. Prasad; R. Langer; I. Esposito; G. Klöppel; S. Sehner; T. Knösel; et al. (Clinical & Experimental Metastasis, 2014)

Testosterone down regulates the expression of Fmr-1 gene in the cerebral cortex of gonadectomized old male mice - S. Prasad; Kanchan Singh (Biogerontology, 2014)

Understanding the spectacular failure of DNA barcoding in willows ( Salix ): Does this result from a trans‐specific selective sweep? - Diana M. Percy; George W. Argus; Quentin C. Cronk; Aron J. Fazekas; Prasad R. Kesanakurti; Kevin S. Burgess; Brian C. Husband; Steven G. Newmaster; Spencer C.H. Barrett; Sean W. Graham (Molecular Ecology, 2014)
Willows ( Salix : Salicaceae) form a major ecological component of Holarctic floras and consequently are an obvious target for a DNA ‐based identification system. We surveyed two to seven plastid genome regions (~3.8 kb; ~3% of the genome) from 71 Salix species across all five subgenera, to assess their performance as DNA barcode markers. Although Salix has a relatively high level of interspecific hybridization, this may not sufficiently explain the near complete failure of barcoding that we observed: only one species had a unique barcode. We recovered 39 unique haplotypes, from more than 500 specimens, that could be partitioned into six major haplotype groups. A unique variant of group I (haplotype 1*) was shared by 53 species in three of five Salix subgenera. This unusual pattern of haplotype sharing across infrageneric taxa is suggestive of either a massive nonrandom coalescence failure (incomplete lineage sorting), or of repeated plastid capture events, possibly including a historical selective sweep of haplotype 1* across taxonomic sections. The former is unlikely as molecular dating indicates that haplotype 1* originated recently and is nested in the oldest major haplotype group in the genus. Further, we detected significant non‐neutrality in the frequency spectrum of mutations in group I, but not outside group I, and demonstrated a striking absence of geographical (isolation by distance) effects in the haplotype distributions of this group. The most likely explanation for the patterns we observed involves recent repeated plastid capture events, aided by widespread hybridization and long‐range seed dispersal, but primarily propelled by one or more trans‐species selective sweeps.

Microbial Biomass Carbon Status in Agro-Ecological Sub Regions of Black Soils in India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Climate trends and impacts on crop production in the Koshi River basin of Nepal - Dinesh Bhatt; Shreedhar Maskey; Mukand S. Babel; Stefan Uhlenbrook; Krishna C. Prasad (Regional Environmental Change, 2014)

Synthesis and biological evaluation of fatty imidazolines - T. Satyavani; Y. Mohini; M. S. L. Karuna; R. B. N. Prasad; C. Ganesh Kumar; M. Poornima; P. Sujitha (Medicinal Chemistry Research, 2014)

Spread-F during the magnetic storm of 22 January 2004 at low latitudes: Effect of IMF-Bz in relation to local sunset time - R G Rastogi; H Chandra; P Janardhan; Thai Lan Hoang; Louis Condori; T K Pant; D S V V D Prasad; B Reinisch (Journal of Earth System Science, 2014)

Assessment of organochlorine pesticide residues in Indian flue-cured tobacco with gas chromatography-single quadrupole mass spectrometer - Rakesh Kumar Ghosh; Zareen S. Khan; C. V. N. Rao; Kaushik Banerjee; D. Damodar Reddy; T. G. K. Murthy; Nalli Johnson; Deb Prasad Ray (Environmental Monitoring and Assessment, 2014)

A substitution mutation in OsCCD7 cosegregates with dwarf and increased tillering phenotype in rice - KRISHNANAND P. KULKARNI; CHANDRAPAL VISHWAKARMA; SARADA P. SAHOO; JOHN M. LIMA; MANOJ NATH; PRASAD DOKKU; RAJESH N. GACCHE; TRILOCHAN MOHAPATRA; S. ROBIN; N. SARLA; M. SESHASHAYEE; ASHOK K. SINGH; et al. (Journal of Genetics, 2014)

Within-plant distribution of an invasive mealybug, Phenacoccus solenopsis, and associated losses in cotton - Rishi Kumar; V. S. Nagrare; Mukesh Nitharwal; Dinesh Swami; Y. G. Prasad (Phytoparasitica, 2014)

A Study on Detection of Pathogenic Listeria monocytogenes in Ovine’s of Kashmir Region Having Abortion or History of Abortion - Shabu Shoukat; S. V. S. Malik; D. B. Rawool; Ashok Kumar; Satish Kumar; Sameer Shrivastava; S. B. Barbuddhe; Durga Prasad Das; Sameer Das (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Calibration of a hysteretic model for glass fiber reinforced gypsum wall panels - Maganti Janardhana; P. Robin Davis; S. S. Ravichandran; A. M. Prasad; D. Menon (Earthquake Engineering and Engineering Vibration, 2014)

Natural variation in the regulation of leaf senescence and relation to N and root traits in wheat - K. B. Hebbar; J. Rane; S. Ramana; N. R. Panwar; S. Ajay; A. Subba Rao; P. V. V. Prasad (Plant and Soil, 2014)

Uptake of Indosol Dark-blue GL dye from aqueous solution by water hyacinth roots powder: adsorption and desorption study - Md. M. R. Khan; M. Z. B. Mukhlish; M. S. I. Mazumder; K. Ferdous; D. M. R. Prasad; Z. Hassan (International Journal of Environmental Science and Technology, 2014)

Evaluation of regional fracture properties for groundwater development using hydrolithostructural domain approach in variably fractured hard rocks of Purulia district, West Bengal, India - TAPAS ACHARYA; RAJESH PRASAD; S CHAKRABARTI (Journal of Earth System Science, 2014)

Genetics of growth habit and photoperiodic response to flowering time in dolichos bean (Lablab purpureus (L.) Sweet) - C. M. KEERTHI; S. RAMESH; M. BYREGOWDA; A. MOHAN RAO; B. S. RAJENDRA PRASAD; P. V. VAIJAYANTHI (Journal of Genetics, 2014)

RNA interference: concept to reality in crop improvement - Satyajit Saurabh; Ambarish S. Vidyarthi; Dinesh Prasad (Planta, 2014)

Retrieval and Validation of Chlorophyll-a Concentrations in the Coastal Waters Off Yanam and Kakinada (Godavari) Basin Along East Coast of India - T. Preethi Latha; P. V. Nagamani; K. H. Rao; S. K. Dash; S. B. Choudhury; Aziz Rehman; V. V. S. S. Sarma; M. Naveen Babu; P. Amarendra; B. Srinivasa Rao; T. D. V. Prasad (Journal of the Indian Society of Remote Sensing, 2014)

Improvements in medium range weather forecasting system of India - V S PRASAD; SAJI MOHANDAS; SURYA KANTI DUTTA; M DAS GUPTA; G R IYENGAR; E N RAJAGOPAL; SWATI BASU (Journal of Earth System Science, 2014)

Overexpression of AtNAC2 (ANAC092) in groundnut (Arachis hypogaea L.) improves abiotic stress tolerance - Mahesh Patil; S. V. Ramu; P. Jathish; Rohini Sreevathsa; P. Chandrashekar Reddy; T. G. Prasad; M. Udayakumar (Plant Biotechnology Reports, 2014)

Planetary-scale wave structures of the earth’s atmosphere revealed from the COSMIC observations - S. K. A. V. Prasad Rao Anisetty; P. S. Brahmanandam; G. Uma; A. Narendra Babu; Ching-Yuang Huang; G. Anil Kumar; S. Tulasi Ram; Hsiao-Lan Wang; Yen-Hsyang Chu (Journal of Meteorological Research, 2014)

Contrasting phytoplankton community structure and associated light absorption characteristics of the western Bay of Bengal - Sudarsana Rao Pandi; Rayaprolu Kiran; Nittala S. Sarma; A. S. Srikanth; V. V. S. S. Sarma; M. S. Krishna; D. Bandyopadhyay; V. R. Prasad; T. Acharyya; K. G. Reddy (Ocean Dynamics, 2014)

Impact of FORMOSAT-3/COSMIC radio occultation data on the prediction of super cyclone Gonu (2007): a case study - S. K. A. V. Prasad Rao Anisetty; Ching-Yuang Huang; Shu-Ya Chen (Natural Hazards, 2014)

Rip current-related fatalities in India: a new predictive risk scale for forecasting rip currents - S. V. V. Arun Kumar; K. V. S. R. Prasad (Natural Hazards, 2014)

Some substituted 1,3,4-thiadiazoles: a novel centrally acting agents - Rajesh Sharma; Yogendra Prasad; Ganesh Prasad Mishra; S. C. Chaturvedi (Medicinal Chemistry Research, 2014)

Improvement of Monsoon Depressions Forecast with Assimilation of Indian DWR Data Using WRF-3DVAR Analysis System - Ashish Routray; U. C. Mohanty; Krishna K. Osuri; S. Kiran Prasad (Pure and Applied Geophysics, 2013)

Urease Activity in Various Agro-ecological Sub-regions of Black Soil Regions of India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Diversity in Indian barley (Hordeum vulgare) cultivars and identification of genotype-specific fingerprints using microsatellite markers - S. K. Jaiswal; Shree P. Pandey; S. Sharma; R. Prasad; L. C. Prasad; R. P. S. Verma; Arun K. Joshi (Journal of Genetics, 2013)

Site classification of Pondicherry using shear-wave velocity and horizontal-to-vertical spectral ratio - S. Trupti; K. Goverdhan; K. N. S. S. S. Srinivas; P. Prabhakar Prasad; T. Seshunarayana (Natural Hazards, 2013)

An intensity database for earthquakes in South Africa from 1912 to 2011 - V. Midzi; J. J. Bommer; F. O. Strasser; P. Albini; B. S. Zulu; K. Prasad; N. S. Flint (Journal of Seismology, 2013)

Early down regulation of the glial Kir4.1 and GLT-1 expression in pericontusional cortex of the old male mice subjected to traumatic brain injury - R. K. Gupta; S. Prasad (Biogerontology, 2013)

Modeling analysis of potential carbon sequestration under existing agroforestry systems in three districts of Indo-gangetic plains in India - Ajit; S. K. Dhyani; Ramnewaj; A. K. Handa; Rajendra Prasad; Badre Alam; R. H. Rizvi; Garima Gupta; K. K. Pandey; Amit Jain; Uma (Agroforestry Systems, 2013)

Comparative Performance of Sweet Sorghum Hybrids and Open Pollinated Varieties for Millable Stalk Yield, Biomass, Sugar Quality Traits, Grain Yield and Bioethanol Production in Tropical Indian Condition - S. S. Rao; J. V. Patil; A. V. Umakanth; J. S. Mishra; C. V. Ratnavathi; G. Shyam Prasad; B. Dayakar Rao (Sugar Tech, 2013)

Cost assessment of losses due to recent reactivation of Kaliasaur landslide on National Highway 58 in Garhwal Himalaya - Indervir S. Negi; Kishor Kumar; Anil Kathait; P. S. Prasad (Natural Hazards, 2013)

Synthesis of fatty acid Schiff base esters as potential antimicrobial and chemotherapeutic agents - Y. Mohini; R. B. N. Prasad; M. S. L. Karuna; C. Ganesh Kumar; M. Poornima; P. Sujitha (Medicinal Chemistry Research, 2013)

Synthesis and pharmacological evaluation of some novel 4-isopropyl thiazole-based sulfonyl derivatives as potent antimicrobial and antitubercular agents - G. V. Suresh Kumar; Y. Rajendra Prasad; S. M. Chandrashekar (Medicinal Chemistry Research, 2013)

Incidence of Subclinical Mastitis and Prevalence of Major Mastitis Pathogens in Organized Farms and Unorganized Sectors - Raveendra Hegde; Shrikrishna Isloor; K. Nithin Prabhu; B. R. Shome; D. Rathnamma; V. V. S. Suryanarayana; S. Yatiraj; C. Renuka Prasad; N. Krishnaveni; S. Sundareshan; D. S. Akhila; A. R. Gomes; et al. (Indian Journal of Microbiology, 2013)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Study of morpho-physiological, phenological and reproductive behaviour in protogynous lines of Indian mustard [Brassica juncea (L.)] - U. S. Chandrashekar; Malavika Dadlani; K. Vishwanath; S. K. Chakrabarty; C. T. Manjunath Prasad (Euphytica, 2013)

Influence of salicylic acid and methyl jasmonate elicitation on anthocyanin production in callus cultures of Rosa hybrida L. - Mohan Ram; K. V. Prasad; S. K. Singh; B. S. Hada; Surendra Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Large-scale green synthesis of Cu nanoparticles - A. B. S. Sastry; R. B. Karthik Aamanchi; Ch. Sree Rama Linga Prasad; B. S. Murty (Environmental Chemistry Letters, 2013)

Simulation of Trajectories of Tar Ball Transport to the Goa Coast - V. Suneel; P. Vethamony; K. Vinod Kumar; M. T. Babu; K. V. S. R. Prasad (Water, Air, & Soil Pollution, 2013)

Intraspecific variability of pollen morphology as revealed by elliptic Fourier analysis - Vincent Bonhomme; S. Prasad; Cédric Gaucherel (Plant Systematics and Evolution, 2013)

Synthesis and biological evaluation of novel 4,5-dihydropyrazole derivatives as potent anticancer and antimicrobial agents - Y. Rajendra Prasad; G. V. Suresh Kumar; S. M. Chandrashekar (Medicinal Chemistry Research, 2013)

P alaeoenvironmental implications of evaporative gaylussite crystals from Lonar Lake, central India - A. ANOOP; S. PRASAD; B. PLESSEN; N. BASAVAIAH; B. GAYE; R. NAUMANN; P. MENZEL; S. WEISE; A. BRAUER (Journal of Quaternary Science, 2013)
We have undertaken petrographic, mineralogical, geochemical and isotopic investigations on carbonate minerals found within a 10‐m‐long core from Lonar Lake, central India, with the aim of evaluating their potential as palaeoenvironmental proxies. The core encompasses the entire Holocene and is the first well‐dated high‐resolution record from central India. While calcite and/or aragonite were found throughout the core, the mineral gaylussite was found only in two specific intervals (4630–3890 and 2040–560 cal a BP). Hydrochemical and isotope data from inflowing streams and lake waters indicate that evaporitic processes play a dominant role in the precipitation of carbonates within this lake. Isotopic (δ 18 O and δ 13 C) studies on the evaporative gaylussite crystals and residual bulk carbonates (calcite) from the long core show that evaporation is the major control on δ 18 O enrichment in both the minerals. However, in case of δ 13 C additional mechanisms, for example methanogenesis (gaylussite) and phytoplankton productivity (calcium carbonate), play an additional important role in some intervals. We also discuss the relevance of our investigation for palaeoclimate reconstruction and late Holocene monsoon variability. Copyright © 2013 John Wiley & Sons, Ltd.

Effect of micronutrient supplementation around calving on the plasma cortisol levels of Murrah buffaloes and Sahiwal and Karan Fries cows - Ajay Kumar Dang; Manu Jamwal; Mandheer Kaur; Shiv Prasad Kimothi; Shashi Pal; Kalyan De; Mohsin M. Pathan; Dilip K. Swain; Sushil K. Mohapatra; Suman Kapila; Rajeev Kapila; Harjit Kaur; et al. (Tropical Animal Health and Production, 2013)

Impact of atmospheric and physical forcings on biogeochemical cycling of dissolved oxygen and nutrients in the coastal Bay of Bengal - V. V. S. S. Sarma; B. Sridevi; K. Maneesha; T. Sridevi; S. A. Naidu; V. R. Prasad; V. Venkataramana; T. Acharya; M. D. Bharati; Ch. V. Subbaiah; B. S. Kiran; N. P. C. Reddy; et al. (Journal of Oceanography, 2013)

Studies on Mechanisation of Planting of Sugarcane Bud Chip Settlings Raised in Protrays - Ravindra Naik; S. J. K. Annamalai; N. Vijayan Nair; N. Rajendra Prasad (Sugar Tech, 2013)

Rhizospheric Flora and the Influence of Agronomic Practices on Them: A Review - Dinesh Kumar; Y. S. Shivay; Shiva Dhar; Chitranjan Kumar; Rajendra Prasad (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Synthesis and pharmacological evaluation of novel 4-isopropylthiazole-4-phenyl-1,2,4-triazole derivatives as potential antimicrobial and antitubercular agents - G. V. Suresh Kumar; Y. Rajendra Prasad; S. M. Chandrashekar (Medicinal Chemistry Research, 2013)

Evaluation of OSCAR ocean surface current product in the tropical Indian Ocean using in situ data - RAJESH SIKHAKOLLI; RASHMI SHARMA; SUJIT BASU; B S GOHIL; ABHIJIT SARKAR; K V S R PRASAD (Journal of Earth System Science, 2013)

Intensified oxygen minimum zone on the western shelf of Bay of Bengal during summer monsoon: influence of river discharge - V. V. S. S. Sarma; M. S. Krishna; R. Viswanadham; G. D. Rao; V. D. Rao; B. Sridevi; B. S. K. Kumar; V. R. Prasad; Ch. V. Subbaiah; T. Acharyya; D. Bandopadhyay (Journal of Oceanography, 2013)

A comparison of metallic contents in lichen Pyxine subcinerea, its substratum and soil - V. Shukla; D. K. Patel; D. K. Upreti; M. Yunus; S. Prasad (International Journal of Environmental Science and Technology, 2013)

Effect of dust load on the leaf attributes of the tree species growing along the roadside - R. K. Chaturvedi; Shikha Prasad; Savita Rana; S. M. Obaidullah; Vijay Pandey; Hema Singh (Environmental Monitoring and Assessment, 2013)

CytochromeP450 isoenzyme specificity in the metabolism of anti-malarial biguanides: molecular docking and molecular dynamics analyses - Dhilon S. Patel; M. Ramesh; Prasad V. Bharatam (Medicinal Chemistry Research, 2012)

Non-synonymous polymorphism (Gln261Arg) of 12-lipoxygenase in colorectal and thyroid cancers - Vidudala V. T. S. Prasad; Kolli Padma (Familial Cancer, 2012)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Development of multiple embryos in polyembryonic insertional mutant OsPE of rice - Priyanka Paul; Anjali Awasthi; Satish Kumar; Shailender Kumar Verma; Ramasare Prasad; H. S. Dhaliwal (Plant Cell Reports, 2012)

Abnormally large magnetospheric electric field on 9 November 2004 and its effect on equatorial ionosphere around the world - R G Rastogi; H Chandra; Louis Condori; M A Abdu; B Reinisch; R T Tsunoda; D S V V D Prasad; T K Pant; T Maruyama (Journal of Earth System Science, 2012)

Biomonitoring of Metals in Ganga Water at Different Ghats of Haridwar: Implications of Constructed Wetland for Sewage Detoxification - U. N. Rai; D. Prasad; S. Verma; A. K. Upadhyay; N. K. Singh (Bulletin of Environmental Contamination and Toxicology, 2012)

Numerical simulation of cyclonic storms FANOOS, NARGIS with assimilation of conventional and satellite observations using 3-DVAR - C. V. Srinivas; V. Yesubabu; K. B. R. R. Hari Prasad; B. Venkatraman; S. S. V. S. Ramakrishna (Natural Hazards, 2012)

Blighia unijugata and Luffa cylindrica Seed Oils: Renewable Sources of Energy for Sustainable Development in Rural Africa - Adewale Adewuyi; Rotimi A Oderinde; B. V. S. K. Rao; R. B. N. Prasad; B. Anjaneyulu (BioEnergy Research, 2012)

Correlation of partial env gene sequences with disease progression parameters in HIV-positive pregnant women from India - Supriya Singh; Shashi Khare; Sudha Prasad; R. L. Ichhpujani; S. S. Negi; Sachin Kumar; D. S. Rawat; L. S. Chauhan; Arvind Rai (Medical Microbiology and Immunology, 2012)

Genetic analysis of yield and quantitative traits in pigeonpea (Cajanus cajan L. Millsp.) - B. C. Ajay; B. N. Gnanesh; K. N. Ganapathy; M. Byre Gowda; P. S. Prasad; G. N. Veerakumar; S. C. Venkatesha; R. Abdul Fiyaz; K. T. Ramya (Euphytica, 2012)

Gene Expression Analysis to Identify Molecular Correlates of Pre- and Post-conditioning Derived Neuroprotection - Shiv S. Prasad; Marsha Russell; Margeryta Nowakowska; Andrew Williams; Carole Yauk (Journal of Molecular Neuroscience, 2012)

Reduced tillering in Basmati rice T-DNA insertional mutant OsTEF1 associates with differential expression of stress related genes and transcription factors - Priyanka Paul; Anjali Awasthi; Amit Kumar Rai; Santosh Kumar Gupta; R. Prasad; T. R. Sharma; H. S. Dhaliwal (Functional & Integrative Genomics, 2012)

Hydrochemical analysis to evaluate the seawater ingress in a small coral island of India - Pallavi Banerjee; V. S. Singh; Ajay Singh; R. K. Prasad; R. Rangarajan (Environmental Monitoring and Assessment, 2012)

Torulaspora indica a novel yeast species isolated from coal mine soils - Puja Saluja; R. K. Yelchuri; Satinder K. Sohal; Geetika Bhagat; Paramjit; G. S. Prasad (Antonie van Leeuwenhoek, 2012)

Simulation of tornado over Orissa (India) on March 31, 2009, using WRF–NMM model - A. J. Litta; U. C. Mohanty; S. Kiran Prasad; M. Mohapatra; Ajit Tyagi; S. C. Sahu (Natural Hazards, 2012)

Genetic characterization of bluetongue virus serotype 9 isolates from India - Pavuluri Panduranga Rao; Y. Vishnuvardhan Reddy; Keerti Meena; N. Karunasree; B. Susmitha; Madala Uma; P. U. V. S. Prasad; P. Chaitanya; Y. Narsimaha Reddy; Nagendra R. Hegde (Virus Genes, 2012)

Screening of Promising Sugarcane Somaclones for Agronomic Traits, and Smut Resistance Using PCR Amplification of Inter Transcribed Region (ITS) of Sporisorium scitaminae - S. G. Dalvi; V. C. Vasekar; Amit Yadav; P. N. Tawar; G. B. Dixit; D. Threetha Prasad; R. B. Deshmukh (Sugar Tech, 2012)

Microflora in fish digestive tract plays significant role in digestion and metabolism - S. Ganguly; A. Prasad (Reviews in Fish Biology and Fisheries, 2012)

A Study on Simulation of Heavy Rainfall Events Over Indian Region with ARW-3DVAR Modeling System - U. C. Mohanty; A. Routray; Krishna K. Osuri; S. Kiran Prasad (Pure and Applied Geophysics, 2012)

Estimation of structural vulnerability for flooding using geospatial tools in the rural area of Orissa, India - Praveen K. Thakur; Sreyasi Maiti; Nanette C. Kingma; V. Hari Prasad; S. P. Aggarwal; Ashutosh Bhardwaj (Natural Hazards, 2012)

Insight to Ecosystem Based Approach (EBA) at Landscape Level Using a Geospatial Medium - Nidhi Nagabhatla; Sonali S. Sellamuttu; A. Ghosh Bobba; Max Finlayson; Rohan Wickramasuriya; Martin Van Brakel; S. Narendra Prasad; Chiranjibi Pattanaik (Journal of the Indian Society of Remote Sensing, 2012)

Evaluation and identification of wheat- Aegilops addition lines controlling high grain iron and zinc concentration and mugineic acid production - K. Neelam; N. Rawat; V. Tiwari; R. Prasad; S. Tripathi; G. Randhawa; H. Dhaliwal (Cereal Research Communications, 2012)

Mean diffusivity in the amygdala correlates with anxiety in pediatric TBI - Jenifer Juranek; Chad P. Johnson; Mary R. Prasad; Larry A. Kramer; Ann Saunders; Pauline A. Filipek; Paul R. Swank; Charles S. Cox; Linda Ewing-Cobbs (Brain Imaging and Behavior, 2012)

Induction of carotenoid pigments in callus cultures of Calendula officinalis L. in response to nitrogen and sucrose levels - M. R. Legha; K. V. Prasad; S. K. Singh; C. Kaur; A. Arora; S. Kumar (In Vitro Cellular & Developmental Biology - Plant, 2012)

Tsunami and tropical island ecosystems: a meta-analysis of studies in Andaman and Nicobar Islands - P. Rama Chandra Prasad; P. Mamtha Lakshmi; K. S. Rajan; Vijaya Bhole; C. B. S. Dutt (Biodiversity and Conservation, 2012)

Assessment of the growth inhibiting effect of some plant essential oils on different Fusarium species isolated from sorghum and maize grains - Marikunte Y. Sreenivasa; Regina S. Dass; Adkar P. Charith Raj; Mysore N. Nagendra Prasad; Premila N. Achar; Gotravalli R. Janardhana (Journal of Plant Diseases and Protection, 2011)

Impact of gridpoint statistical interpolation scheme over Indian region - SURYA K DUTTA; V S PRASAD (Journal of Earth System Science, 2011)

Molecular identification of a new begomovirus associated with yellow mosaic disease of Jatropha gossypifolia in India - S. K. Snehi; S. K. Raj; M. S. Khan; V. Prasad (Archives of Virology, 2011)

Immune response in symptomatic and asymptomatic neurocysticercosis - Avantika Verma; Kashi N. Prasad; Satyanarayana S. Cheekatla; Kishan K. Nyati; Vimal K. Paliwal; Rakesh K. Gupta (Medical Microbiology and Immunology, 2011)

Synthesis, characterization, antioxidant, and anticancer studies of 6-[3-(4-chlorophenyl)-1H-pyrazol-4-yl]-3-[(2-naphthyloxy)methyl][1,2,4]triazolo[3,4-b][1,3,4]thiadiazole in HepG2 cell lines - Dhanya Sunil; Arun M. Isloor; Prakash Shetty; K. Satyamoorthy; A. S. Bharath Prasad (Medicinal Chemistry Research, 2011)

Prevention of benzene-induced genotoxicity in bone marrow and lung cells: superiority of polyphenolic acetates to polyphenols - Ajit Kumar; Anupam Sushama; Vishwajeet Rohil; Sushma Manral; Sukanya Gangopadhyay; Ashok K. Prasad; Hanumantharao G. Raj; Virender S. Parmar (Archives of Toxicology, 2011)

Animal models and molecular imaging tools to investigate lymph node metastases - Elliot L. Servais; Christos Colovos; Adam J. Bograd; Julie White; Michel Sadelain; Prasad S. Adusumilli (Journal of Molecular Medicine, 2011)

Identification of Fruity Aroma-Producing Compounds from Chryseobacterium sp. Isolated from the Western Ghats, India - P. Anil Kumar; T. N. R. Srinivas; A. R. Prasad; S. Shivaji (Current Microbiology, 2011)

Complete nucleotide sequence of Croton yellow vein mosaic virus and DNA-β associated with yellow vein mosaic disease of Jatropha gossypifolia in India - S. K. Snehi; M. S. Khan; S. K. Raj; V. Prasad (Virus Genes, 2011)

A new hybrid spectral similarity measure for discrimination among Vigna species - M. Naresh Kumar; M. V. R. Seshasai; K. S. Vara Prasad; V. Kamala; K. V. Ramana; R. S. Dwivedi; P. S. Roy (International Journal of Remote Sensing, 2011)

On-farm evaluation of two fast growing trees for biomass production for industrial use in Andhra Pradesh, Southern India - J. V. N. S. Prasad; G. R. Korwar; K. V. Rao; K. Srinivas; Ch. Srinivasarao; B. Pedababu; B. Venkateswarlu; S. N. Rao; H. D. Kulkarni (New Forests, 2011)

Changes in agricultural cropland areas between a water-surplus year and a water-deficit year impacting food security, determined using MODIS 250 m time-series data and spectral matching techniques, in the Krishna River basin (India) - Murali Krishna Gumma; Prasad S. Thenkabail; I. V. Muralikrishna; Manohar N. Velpuri; Parthasarathi T. Gangadhararao; Venkateswarlu Dheeravath; Chandrasekhar M. Biradar; Sreedhar Acharya Nalan; Anju Gaur (International Journal of Remote Sensing, 2011)

Space borne SAR observations of oceanic internal waves in North Bay of Bengal - K. V. S. R. Prasad; M. Rajasekhar (Natural Hazards, 2011)

Reply to: do marathon runners face an “ominous” risk of myocardial fibrosis? - M. G. Wilson; R. O’Hanlon; S. K. Prasad; S. Sharma; K. George; G. Whyte (European Journal of Applied Physiology, 2011)

Lignolytic enzyme activities of wood decaying fungi from Andhra Pradesh - J. Vinay Sagar Goud; N. S. V. S. S. S. L. Hima Bindu; B. Samatha; M. Ram Prasad; M. A. Singara Charya (Journal of the Indian Academy of Wood Science, 2011)

Application of drastic model and GIS: for assessing vulnerability in hard rock granitic aquifer - Ranjeet Kumar Prasad; V. S. Singh; S. K. G. Krishnamacharyulu; Pallavi Banerjee (Environmental Monitoring and Assessment, 2011)

Factors affecting in vitro propagation of Momordica balsamina: a medicinal and nutritional climber - Gulab Singh Thakur; Mukeshwar Pandey; Rohit Sharma; Bhagwan Singh Sanodiya; G. B. K. S. Prasad; Prakash Singh Bisen (Physiology and Molecular Biology of Plants, 2011)

Inhibitory effect of caffeic acid on cancer cell proliferation by oxidative mechanism in human HT-1080 fibrosarcoma cell line - N. Rajendra Prasad; A. Karthikeyan; S. Karthikeyan; Bandugula Venkata Reddy (Molecular and Cellular Biochemistry, 2011)

Neuroprotection Induced In Vitro by Ischemic Preconditioning and Postconditioning: Modulation of Apoptosis and PI3K–Akt Pathways - Shiv S. Prasad; Marsha Russell; Margeryta Nowakowska (Journal of Molecular Neuroscience, 2011)

Spatial patterns of plant diversity below‐ground as revealed by DNA barcoding - PRASAD R. KESANAKURTI; ARON J. FAZEKAS; KEVIN S. BURGESS; DIANA M. PERCY; STEVEN G. NEWMASTER; SEAN W. GRAHAM; SPENCER C. H. BARRETT; MEHRDAD HAJIBABAEI; BRIAN C. HUSBAND (Molecular Ecology, 2011)
Our understanding of the spatial organization of root diversity in plant communities and of the mechanisms of community assembly has been limited by our ability to identify plants based on root tissue, especially in diverse communities. Here, we test the effectiveness of the plastid gene rbcL , a core plant DNA barcoding marker, for investigating spatial patterns of root diversity, and relate observed patterns to above‐ground community structure. We collected 3800 root fragments from four randomly positioned, 1‐m‐deep soil profiles (two vertical transects per plot), located in an old‐field community in southern Ontario, Canada, and extracted and sequenced DNA from 1531 subsampled fragments. We identified species by comparing sequences with a DNA barcode reference library developed previously for the local flora. Nearly 85% of sampled root fragments were successfully sequenced and identified as belonging to 29 plant species or species groups. Root abundance and species richness varied in horizontal space and were negatively correlated with soil depth. The relative abundance of taxa below‐ground was correlated with their frequency above‐ground ( r = 0.73, P = 0.0001), but several species detected in root tissue were not observed in above‐ground quadrats. Multivariate analyses indicated that diversity was highly structured below‐ground, and associated with depth, root morphology, soil chemistry and soil texture, whereas little structure was evident above‐ground. Furthermore, analyses of species co‐occurrence indicates strong species segregation overall but random co‐occurrence among confamilials. Our results provide insights into the role of environmental filtering and competitive interactions in the organization of plant diversity below‐ground, and also demonstrate the utility of barcoding for the identification of plant roots.

Induction of anthocyanin pigments in callus cultures of Rosa hybrida L. in response to sucrose and ammonical nitrogen levels - Mohan Ram; K. V. Prasad; Charanjit Kaur; S. K. Singh; Ajay Arora; Surendra Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Application of GIS for Evaluation and Design of Watershed Guidelines - R. S. Bhalla; Neil W. Pelkey; K. V. Devi Prasad (Water Resources Management, 2011)

Biotransformation of Meloxicam by Cunninghamella blakesleeana: Significance of Carbon and Nitrogen Source - Gurram Shyam Prasad; Kollu Narasimha Rao; Rama Preethi; Sivasri Girisham; S. M. Reddy (Indian Journal of Microbiology, 2011)

Rapid gains in food security from new maize varieties for complex hillside environments through farmer participation - Thakur Prasad Tiwari; Guillermo Ortiz-Ferrara; Dil B. Gurung; Ramesh Dhakal; Ram B. Katuwal; Birendra B. Hamal; Nirmal Gadal; Daljit S. Virk (Food Security, 2010)

Hydrogeochemical characterization of fluoride rich groundwater of Wailpalli watershed, Nalgonda District, Andhra Pradesh, India - A. G. S. Reddy; D. V. Reddy; P. N. Rao; K. Maruthy Prasad (Environmental Monitoring and Assessment, 2010)

Cardiovascular function and the veteran athlete - M. Wilson; R. O’Hanlon; S. Basavarajaiah; K. George; D. Green; P. Ainslie; S. Sharma; S. Prasad; C. Murrell; D. Thijssen; A. Nevill; G. Whyte (European Journal of Applied Physiology, 2010)

Vitamin and mineral use and risk of prostate cancer: misleading? - Ananda S. Prasad; Harold H. Sandstead; Chris Frederickson (Cancer Causes & Control, 2010)

A conceptual framework to analyse the land-use/land-cover changes and its impact on phytodiversity: a case study of North Andaman Islands, India - P. Rama Chandra Prasad; K. S. Rajan; C. B. S. Dutt; P. S. Roy (Biodiversity and Conservation, 2010)

Synthesis, chemical characterization of novel 1,3-dimethyl acridones as cytotoxic agents, and their DNA-binding studies - N. K. Sathish; P. GopKumar; V. V. S. Rajendra Prasad; S. M. Shanta Kumar; Y. C. Mayur (Medicinal Chemistry Research, 2010)

Bioconversion of acrylonitrile to acrylamide using polyacrylamide entrapped cells of Rhodococcus rhodochrous PA-34 - J. Raj; S. Prasad; N. N. Sharma; T. C. Bhalla (Folia Microbiologica, 2010)

Alteration in hematology of Labeo rohita under stress of pollution from Lakes of Bangalore, Karnataka, India - Bela Zutshi; S. G. Raghu Prasad; R. Nagaraja (Environmental Monitoring and Assessment, 2010)

Correlation of the oldest Toba Tuff to sediments in the central Indian Ocean Basin - J. N. Pattan; M. Shyam Prasad; E. V. S. S. K. Babu (Journal of Earth System Science, 2010)

Antioxidant, antinociceptive and anti-inflammatory activities of atorvastatin and rosuvastatin in various experimental models - Mahesh M. Ghaisas; Prasad R. Dandawate; Suyash A. Zawar; Yogesh S. Ahire; Santosh P. Gandhi (Inflammopharmacology, 2010)

Biodiesel production with special emphasis on lipase-catalyzed transesterification - Prakash S. Bisen; Bhagwan S. Sanodiya; Gulab S. Thakur; Rakesh K. Baghel; G. B. K. S. Prasad (Biotechnology Letters, 2010)

A logistic regression approach for monthly rainfall forecasts in meteorological subdivisions of India based on DEMETER retrospective forecasts - K. Prasad; S. K. Dash; U. C. Mohanty (International Journal of Climatology, 2010)
A multi‐predictor logistic regression model has been developed for probabilistic forecasts of domain average rainfall on monthly timescale for three study regions namely, India as a whole, and two homogeneous meteorological subdivisions of India, i.e. Orissa on the east coast and Gujarat on the west coast. The time series of the monthly total observed rainfall as the predictand variable was constructed from the gridded (1° × 1°) daily rainfall produced by India Meteorological Department, and those of the predictor data sets from 1‐month lead forecasts of several atmospheric and oceanic variables produced by the ‘Development of a European Multi‐model Ensemble system for seasonal to inTERannual prediction (DEMETER)’ project of European Centre for Medium‐Range Weather Forecasts (ECMWF). Multi‐model ensembles of nine‐member retrospective forecasts for the month of August generated by three constituent models of the DEMETER system, viz., ECMWF, United Kingdom Meteorological Office (UKMO) and Meteo France are used. The predictor variables (totally 36 in number) include direct model‐predicted total precipitation and its inter‐member standard deviation. A two‐stage procedure has been designed, where logistic regression is first computed for each individual variable and then for the variables ranked on the basis of Brier scores. The top‐ranked variables (up to four) are used for fitting the multiple logistic regression model in a stepwise manner. The fitted model provides estimates of probability of the value of an observation exceeding a specified quantile (such as median) of the statistical distribution of the predictand variable. The model shows good performance in capturing the extreme rainfall years and appears to perform better than the direct model forecasts of total precipitation in respect of such years. Copyright © 2009 Royal Meteorological Society

Fire risk evaluation using multicriteria analysis—a case study - Krishna Prasad Vadrevu; Anuradha Eaturu; K. V. S. Badarinath (Environmental Monitoring and Assessment, 2010)

Nitrogen deposition in tropical forests from savanna and deforestation fires - YANG CHEN; JAMES T. RANDERSON; GUIDO R. VAN DER WERF; DOUGLAS C. MORTON; MINGQUAN MU; PRASAD S. KASIBHATLA (Global Change Biology, 2010)
We used satellite‐derived estimates of global fire emissions and a chemical transport model to estimate atmospheric nitrogen (N) fluxes from savanna and deforestation fires in tropical ecosystems. N emissions and reactive N deposition led to a net transport of N equatorward, from savannas and areas undergoing deforestation to tropical forests. Deposition of fire‐emitted N in savannas was only 26% of emissions – indicating a net export from this biome. On average, net N loss from fires (the sum of emissions and deposition) was equivalent to approximately 22% of biological N fixation (BNF) in savannas (4.0 kg N ha −1 yr −1 ) and 38% of BNF in ecosystems at the deforestation frontier (9.3 kg N ha −1 yr −1 ). Net N gains from fires occurred in interior tropical forests at a rate equivalent to 3% of their BNF (0.8 kg N ha −1 yr −1 ). This percentage was highest for African tropical forests in the Congo Basin (15%; 3.4 kg N ha −1 yr −1 ) owing to equatorward transport from frequently burning savannas north and south of the basin. These results provide evidence for cross‐biome atmospheric fluxes of N that may help to sustain productivity in some tropical forest ecosystems on millennial timescales. Anthropogenic fires associated with slash and burn agriculture and deforestation in the southern part of the Amazon Basin and across Southeast Asia have substantially increased N deposition in these regions in recent decades and may contribute to increased rates of carbon accumulation in secondary forests and other N‐limited ecosystems.

Seasonal variation in physicochemical properties of coastal waters of Kalpakkam, east coast of India with special emphasis on nutrients - K. K. Satpathy; A. K. Mohanty; U. Natesan; M. V. R. Prasad; S. K. Sarkar (Environmental Monitoring and Assessment, 2010)

Highly efficient shoot regeneration of Bacopa monnieri (L.) using a two-stage culture procedure and assessment of genetic integrity of micropropagated plants by RAPD - S. Antony Ceasar; S. Lenin Maxwell; K. Bhargav Prasad; M. Karthigan; Savarimuthu Ignacimuthu (Acta Physiologiae Plantarum, 2010)

Estimation of unconfined aquifer parameters by genetic algorithms - M. Rajesh; D. Kashyap; K. S. Hari Prasad (Hydrological Sciences Journal, 2010)

Synthesis and in vitro antiproliferative activity of diphenyl(sulphonylpiperidin-4-yl)methanol derivatives - S. B. Benaka Prasad; K. Vinaya; C. S. Ananda Kumar; Sanjay Swarup; K. S. Rangappa (Medicinal Chemistry Research, 2010)

Ground Water Control Techniques for Safe Exploitation of the Neyveli Lignite Deposit, Cuddalore District, Tamil Nadu, India - K. S. Anandan; S. N. Sahay; T. K. Ramabadran; S. Shiv Prasad (Mine Water and the Environment, 2010)

Ground Water Basin Management at the Neyveli Lignite Mines - V. Ravi Kumar; S. N. Sahay; N. Periasamy; S. Shiv Prasad; S. Karthikeyan (Mine Water and the Environment, 2010)

Nutritional evaluation of transgenic cottonseed in the ration of lactating dairy cows - Ranjan K. Mohanta; Kamal K. Singhal; Amrish K. Tyagi; Y. S. Rajput; Shiv Prasad (Tropical Animal Health and Production, 2010)

Delineation of Subtrappean Mesozoic Sediments in Deccan Syneclise, India, Using Travel-Time Inversion of Seismic Refraction and Wide-Angle Reflection Data - A. S. N. Murty; B. Rajendra Prasad; P. Koteswara Rao; S. Raju; T. Sateesh (Pure and Applied Geophysics, 2010)

Relative efficiency of diammonium phosphate and mussoorie rock phosphate on productivity and phosphorus balance in a rice–rapeseed–mungbean cropping system - S. N. Sharma; R. Prasad; Y. S. Shivay; M. K. Dwivedi; Sandeep Kumar; M. R. Davari; Moola Ram; Dinesh Kumar (Nutrient Cycling in Agroecosystems, 2010)

Tree row spacing affected agronomic and economic performance of Eucalyptus-based agroforestry in Andhra Pradesh, Southern India - J. V. N. S. Prasad; G. R. Korwar; K. V. Rao; U. K. Mandal; C. A. R. Rao; G. R. Rao; Y. S. Ramakrishna; B. Venkateswarlu; S. N. Rao; H. D. Kulkarni; M. R. Rao (Agroforestry Systems, 2010)

Isolation and characterization of Pseudomonas sp. KUMS3 from Asian sea bass (Lates calcarifer) with fin rot - S. Kumaran; B. Deivasigamani; K. M. Alagappan; M. Sakthivel; S. Guru Prasad (World Journal of Microbiology and Biotechnology, 2010)

Development of a New Comprehensive Ocean Atlas for Indian Ocean utilizing ARGO Data - B. Prasad Kumar; Rahul Barman; S. K. Dube; P. C. Pandey; M. Ravichandran; Shailesh Nayak (International Journal of Climatology, 2010)
The World Ocean Atlas (WOA), also termed ‘Levitus Climatology’, is a global ocean climatology containing monthly, seasonal and annual means of temperature (T) and salinity (S) fields at standard ocean depths. The monthly climatology for T and S is available for standard depths up to 1000 m. The database used in the preparation of this climatology (WOA) are historical records of Conductivity, Temperature and Depth (CTD) casts and other available marine observations collected in the past. The methodology used in preparation of this WOA is objective analysis which is essentially non‐synoptic and widely scattered in the space domain. We understand that ARGO data has so far not been blended with WOA, nor has its impact for improving WOA climatology been attempted. Presently, with the wealth of marine data from ARGO profilers in the Indian Ocean, we propose a new approach to reconstruct T and S fields optimally utilizing the ARGO data. Here we develop a new model using Delaunay Tessellation with QHull algorithm delivering three‐dimensional T and S fields from a non‐uniform scattered database up to a depth of 1000 m. For gaps in a data‐sparse region, we use all available quality‐checked Ocean Station Data (OSD) and Profiling Float Data (PFL) information on T and S, in addition to the existing ARGO data. The initiative here was to replace WOA data points with realistic information from ARGO and in situ data, thereby producing a new climatology atlas. We demonstrate the robustness of our approach, and the final climatology on T and S is better compared with the existing state‐of‐the‐art WOA. The advantage of the proposed methodology is the scope of improving the ocean atlas with the addition of more ARGO data in the near future. The clustered approach in modelling enables ocean parameter retrieval in geometrically disconnected regions with an option for hot restart. We believe that the new climatology will benefit the research community immensely. Copyright © 2009 Royal Meteorological Society

Assessing forest canopy closure in a geospatial medium to address management concerns for tropical islands—Southeast Asia - P. Rama Chandra Prasad; Nidhi Nagabhatla; C. S. Reddy; Stutee Gupta; K. S. Rajan; S. H. Raza; C. B. S. Dutt (Environmental Monitoring and Assessment, 2010)

Shoot multiplication kinetics and hyperhydric status of regenerated shoots of gladiolus in agar-solidified and matrix-supported liquid cultures - S. Dutta Gupta; V. S. S. Prasad (Plant Biotechnology Reports, 2010)

Impact of GPS radio occultation data assimilation on regional weather predictions - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Chuen-Tsyr Terng; Fang-Ching Chien; Pay-Liam Lin; Mien-Tze Kueh; Shu-Hua Chen; Ming-Jen Yang; Chieh-Ju Wang; Anisetty S. K. A. V. Prasad Rao (GPS Solutions, 2010)

Linear and Non-linear Double Diffusive Convection in a Fluid-Saturated Anisotropic Porous Layer with Cross-Diffusion Effects - S. N. Gaikwad; M. S. Malashetty; K. Rama Prasad (Transport in Porous Media, 2009)

Marker-free transgenic corn plant production through co-bombardment - N. Shiva Prakash; R. Bhojaraja; S. K. Shivbachan; G. G. Hari Priya; T. K. Nagraj; V. Prasad; V. Srikanth Babu; T. L. Jayaprakash; Santanu Dasgupta; T. Michael Spencer; Raghava S. Boddupalli (Plant Cell Reports, 2009)

Evidence of Late Palaeocene-Early Eocene equatorial rain forest refugia in southern Western Ghats, India - V. Prasad; A. Farooqui; S. K. M. Tripathi; R. Garg; B. Thakur (Journal of Biosciences, 2009)

Molecular mapping of rice blast resistance gene Pi-1(t) in the elite indica variety Samba mahsuri - M. Srinivas Prasad; B. Aruna Kanthi; S. M. Balachandran; M. Seshumadhav; K. Madhan Mohan; B. C. Viraktamath (World Journal of Microbiology and Biotechnology, 2009)

Nodulation of Sesbania species by Rhizobium ( Agrobacterium ) strain IRBG74 and other rhizobia - Stephen P. Cummings; Prasad Gyaneshwar; Pablo Vinuesa; Frank T. Farruggia; Mitchell Andrews; David Humphry; Geoffrey N. Elliott; Andrew Nelson; Caroline Orr; Deborah Pettitt; Gopit R. Shah; Scott R. Santos; et al. (Environmental Microbiology, 2009)
Summary Concatenated sequence analysis with 16S rRNA, rpoB and fusA genes identified a bacterial strain (IRBG74) isolated from root nodules of the aquatic legume Sesbania cannabina as a close relative of the plant pathogen Rhizobium radiobacter (syn. Agrobacterium tumefaciens ). However, DNA:DNA hybridization with R. radiobacter , R. rubi , R. vitis and R. huautlense gave only 44%, 5%, 8% and 8% similarity respectively, suggesting that IRBG74 is potentially a new species. Additionally, it contained no vir genes and lacked tumour‐forming ability, but harboured a sym ‐plasmid containing nifH and nodA genes similar to those in other Sesbania symbionts. Indeed, IRBG74 effectively nodulated S. cannabina and seven other Sesbania spp. that nodulate with Ensifer ( Sinorhizobium )/ Rhizobium strains with similar nodA genes to IRBG74, but not species that nodulate with Azorhizobium or Mesorhizobium . Light and electron microscopy revealed that IRBG74 infected Sesbania spp. via lateral root junctions under flooded conditions, but via root hairs under non‐flooded conditions. Thus, IRBG74 is the first confirmed legume‐nodulating symbiont from the Rhizobium ( Agrobacterium ) clade. Cross‐inoculation studies with various Sesbania symbionts showed that S. cannabina could form fully effective symbioses with strains in the genera Rhizobium and Ensifer , only ineffective ones with Azorhizobium strains, and either partially effective ( Mesorhizobium huakii ) or ineffective ( Mesorhizobium plurifarium ) symbioses with Mesorhizobium . These data are discussed in terms of the molecular phylogeny of Sesbania and its symbionts.

From global to local: Testing the potential of cross-scaling in global data sets - Nidhi Nagabhatla; R. Wickramasuriya; S. N. Prasad (Journal of the Indian Society of Remote Sensing, 2009)

Purification of a hyperactive nitrile hydratase from resting cells of Rhodococcus rhodochrous PA-34 - S. Prasad; J. Raj; T. C. Bhalla (Indian Journal of Microbiology, 2009)

Genome-wide QTL analysis for pre-harvest sprouting tolerance in bread wheat - Amita Mohan; Pawan Kulwal; Ravinder Singh; Vinay Kumar; Reyazul Rouf Mir; Jitendra Kumar; Manoj Prasad; H. S. Balyan; P. K. Gupta (Euphytica, 2009)

Changes in structural attributes of plant communities along disturbance gradients in a dry deciduous forest of Western Ghats, India - K. Anitha; Shijo Joseph; E. V. Ramasamy; S. Narendra Prasad (Environmental Monitoring and Assessment, 2009)

In vitro germination and micropropagation of Givotia rottleriformis Griff. - K. Samuel; D. Debashish; B. Madhumita; G. Padmaja; Siva Ram Prasad; V. Bhaskara Ramana Murthy; P. S. Rao (In Vitro Cellular & Developmental Biology - Plant, 2009)

Global irrigated area map (GIAM), derived from remote sensing, for the end of the last millennium - Prasad S. Thenkabail; Chandrashekhar M. Biradar; Praveen Noojipady; Venkateswarlu Dheeravath; Yuanjie Li; Manohar Velpuri; Muralikrishna Gumma; Obi Reddy P. Gangalakunta; Hugh Turral; Xueliang Cai; Jagath Vithanage; Mitchell A. Schull; et al. (International Journal of Remote Sensing, 2009)

Kinetics of Inhibition of Rabbit Intestine Alkaline Phosphatase by Heteroligand Peroxo Complexes of Vanadium(V) and Tungsten(VI) - Diganta Kalita; Siva Prasad Das; Nashreen S. Islam (Biological Trace Element Research, 2009)

Parameterization of sea surface drag under varying sea state and its dependence on wave age - R. Rajesh Kumar; B. Prasad Kumar; A. N. V. Satyanarayana; D. Bala Subrahamanyam; A. D. Rao; S. K. Dube (Natural Hazards, 2009)

Significance of nearshore wave parameters in identifying vulnerable zones during storm and normal conditions along Visakhapatnam coast, India - K. V. S. R. Prasad; S. V. V. Arun Kumar; Ch. Venkata Ramu; P. Sreenivas (Natural Hazards, 2009)

Effect of varied atmospheric stability on sea surface drag in shallow seas and its impact on wind-wave growth - R. Rajesh Kumar; B. Prasad Kumar; A. N. V. Satyanarayana; D. Bala Subrahamanyam; A. D. Rao; S. K. Dube (Natural Hazards, 2009)

Assessment of tsunami and anthropogenic impacts on the forest of the North Andaman Islands, India - P. Rama Chandra Prasad; C. Sudhakar Reddy; K. Sundara Rajan; S. Hazan Raza; C. Bala Subrahmanya Dutt (International Journal of Remote Sensing, 2009)

Use of remote sensing in characterization and management of Dhamni micro-watershed of Chandrapur district of Maharashtra - Elvis A. Shukla; Jagdish Prasad; M. S. S. Nagaraju; Rajeev Srivastava; D. L. Kauraw (Journal of the Indian Society of Remote Sensing, 2009)

Variations in CO, O3 and black carbon aerosol mass concentrations associated with planetary boundary layer (PBL) over tropical urban environment in India - K. V. S. Badarinath; Anu Rani Sharma; Shailesh Kumar Kharol; V. Krishna Prasad (Journal of Atmospheric Chemistry, 2009)

Differential expression of Fmr-1 mRNA and FMRP in female mice brain during aging - Kanchan Singh; S. Prasad (Molecular Biology Reports, 2008)

Performance stability of maize genotypes across diverse hill environments in Nepal - D. Sharma; R. C. Sharma; R. Dhakal; N. B. Dhami; D. B. Gurung; R. B. Katuwal; K. B. Koirala; R. C. Prasad; S. N. Sah; S. R. Upadhyay; T. P. Tiwari; G. Ortiz-Ferrara (Euphytica, 2008)

Spatial patterns in vegetation fires in the Indian region - Krishna Prasad Vadrevu; K. V. S. Badarinath; Eaturu Anuradha (Environmental Monitoring and Assessment, 2008)

Age- and sex-related analysis of methylation of 5′-upstream sequences of Fmr-1 gene in mouse brain and modulation by sex steroid hormones - Kanchan Singh; S. Prasad (Biogerontology, 2008)

Effects of precipitation, temperature and topographic parameters on evergreen vegetation greenery in the Western Ghats, India - V. Krishna Prasad; K. V. S. Badarinath; Anuradha Eaturu (International Journal of Climatology, 2008)
Bi‐weekly National Oceanic and Atmospheric Administration‐advanced very high‐resolution radiometer (NOAA‐AVHRR) satellite data covering a fourteen‐year time period (1990–2003) were used to examine spatial patterns in the normalized difference vegetation index (NDVI) and their relationships with environmental variables covering tropical evergreen forests of the Western Ghats, India. NDVI values and corresponding environmental variables were extracted from 23 different forested sites using the NOAA‐AVHRR global inventory monitoring and modelling studies (GIMMS) dataset. We specifically used the partial least square (PLS) multivariate regression technique that combines features from principal component analysis and multiple regression to link spatial patterns in NDVI with the environmental variables. PLS regression analysis suggested the two‐component model to be the best model, explaining nearly 71% of the variance in the NDVI datasets with relatively good R 2 value of 0.78 and a predicted R 2 value of 0.74. The most important positive predictors for NDVI included Riva's continentality index, precipitation indicators summed over different quarters, average precipitation and elevation. Also, the results from PLS regression clearly suggested that bio‐climatic indicators that relied only on precipitation parameters had much more positive influence than indicators that combined both temperature and precipitation together. These results highlight the climatic controls of vegetation vigor in evergreen forests and have implications for monitoring bio‐spheric activity, developing prognostic phenology models and deriving land cover maps in the Western Ghats region of India. Copyright © 2008 Royal Meteorological Society

Biotransformation of albendazole by Cunninghamella blakesleeana: effect of carbon and nitrogen source - G. S. Prasad; S. Girisham; S. M. Reddy; K. Srisailam (World Journal of Microbiology and Biotechnology, 2008)

Velocity Structure of the West-Bengal Sedimentary Basin, India along the Palashi-Kandi Profile Using a Travel-time Inversion of Wide-angle Seismic data and Gravity Modeling – An Update - A. S. N. Murty; Kalachand Sain; B. Rajendra Prasad (Pure and Applied Geophysics, 2008)

Variation in aerosol properties over Hyderabad, India during intense cyclonic conditions - K. V. S. Badarinath; Shailesh Kumar Kharol; V. Krishna Prasad; D. G. Kaskaoutis; H. D. Kambezidis (International Journal of Remote Sensing, 2008)

Biotransformation of albendazole by fungi - G. S. Prasad; S. Girisham; S. M. Reddy; K. Srisailam (World Journal of Microbiology and Biotechnology, 2008)

Effect of promoter driving selectable marker on corn transformation - N. Shiva Prakash; V. Prasad; Thillai P. Chidambram; Shoba Cherian; T. L. Jayaprakash; Santanu Dasgupta; Qi Wang; Michael T. Mann; T. Michael Spencer; Raghava S. Boddupalli (Transgenic Research, 2008)

Evaluation of Sesbania grandiflora for antiurolithiatic and antioxidant properties - Sujatha Doddola; Haritha Pasupulati; Bharathi Koganti; Koganti V. S. R. G. Prasad (Journal of Natural Medicines, 2008)

Influence of fly ash mixtures on early tree growth and physicochemical properties of soil in semi-arid tropical Alfisols - V. Ramesh; G. R. Korwar; Uttam Kumar Mandal; Jasti V. N. S. Prasad; Kishori Lal Sharma; Yezzu S. Ramakrishna; Kandula Venkanna (Agroforestry Systems, 2008)

Design of Optimum Response Surface Experiments for Electro-Coagulation of Distillery Spent Wash - R. Krishna Prasad; R. Ram Kumar; S. N. Srivastava (Water, Air, & Soil Pollution, 2008)

Parasitism and hyper parasitism on Pyrilla Perpusilla Walker in sugarcane ecosystem - D. C. Rajak; R. P. Singh; K. Prasad; U. Chandra; S. R. Saroj; H. Lal (Sugar Tech, 2008)

Landscape analysis in Fambong Lho wildlife sanctuary, East district, Sikkim, India using remote sensing and GIS techniques - S. Sudhakar; P. R. C. Prasad; M. L. Arrawatia; K. Sudha; Shilpa Babar; S. K. S. V. Rajeshwar Rao (Journal of the Indian Society of Remote Sensing, 2008)

Potential effects of climate change on birds of the Northeast - N. L. Rodenhouse; S. N. Matthews; K. P. McFarland; J. D. Lambert; L. R. Iverson; A. Prasad; T. S. Sillett; R. T. Holmes (Mitigation and Adaptation Strategies for Global Change, 2008)

Intercomparison of Air–Sea Interface Fluxes over the Yellow Sea and Korea Strait: Impact of Tsushima Warm Current - D. Bala Subrahamanyam; Radhika Ramachandran; S. Indira Rani; P. K. Kunhikrishnan; B. Prasad Kumar (Boundary-Layer Meteorology, 2008)

Influence of fly ash mixtures on early tree growth and physicochemical properties of soil in semi-arid tropical Alfisols - V. Ramesh; G. R. Korwar; Uttam Kumar Mandal; Jasti V. N. S. Prasad; Kishori Lal Sharma; S. Ramakrishna Yezzu; Venkanna Kandula (Agroforestry Systems, 2008)

Influence of natural and anthropogenic activities on UV Index variations – a study over tropical urban region using ground based observations and satellite data - K. V. S. Badarinath; Shailesh Kumar Kharol; V. Krishna Prasad; Anu Rani Sharma; E. U. B. Reddi; H. D. Kambezidis; D. G. Kaskaoutis (Journal of Atmospheric Chemistry, 2008)

Relative yield and zinc uptake by rice from zinc sulphate and zinc oxide coatings onto urea - Yashbir Singh Shivay; Dinesh Kumar; Rajendra Prasad; I. P. S. Ahlawat (Nutrient Cycling in Agroecosystems, 2008)

Effects of season-long high temperature growth conditions on sugar-to-starch metabolism in developing microspores of grain sorghum (Sorghum bicolor L. Moench) - Mukesh Jain; P. V. Vara Prasad; Kenneth J. Boote; Allen L. Hartwell; Prem S. Chourey (Planta, 2007)

Ionic liquids as a reaction medium for lipase-catalyzed methanolysis of sunflower oil - S. Sunitha; S. Kanjilal; P. S. Reddy; R. B. N. Prasad (Biotechnology Letters, 2007)

The Assimilation of GPS Radio Occultation Data and its Impact on Rainfall Prediction along the West Coast of India during Monsoon 2002 - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Anisetty S. K. A. V. Prasad Rao; Chien-Ju Wang (Pure and Applied Geophysics, 2007)

Synthesis and evaluation of 1-benzhydryl-sulfonyl-piperazine derivatives as inhibitors of MDA-MB-231 human breast cancer cell proliferation - C. S. Ananda Kumar; S. Nanjunda Swamy; N. R. Thimmegowda; S. B. Benaka Prasad; George W. Yip; K. S. Rangappa (Medicinal Chemistry Research, 2007)

Identification of Molecular Marker and Aggressiveness for Different Groups of Bipolaris sorokiniana Isolates Causing Spot Blotch Disease in Wheat (Triticum aestivum L.) - S. K. Jaiswal; Sweta; L. C. Prasad; S. Sharma; S. Kumar; R. Prasad; S. P. Pandey; R. Chand; A. K. Joshi (Current Microbiology, 2007)

Fragile x mental retardation (Fmr-1) gene expression is down regulated in brain of mice during aging - Kanchan Singh; Pankaj Gaur; S. Prasad (Molecular Biology Reports, 2007)

Genetic diversity in Hirsutella thompsonii isolates based on random amplified polymorphic DNA analysis - S. Aghajanzadeh; D. Theertha Prasad; B. Mallik (BioControl, 2007)

Spatial patterns of vegetation phenology metrics and related climatic controls of eight contrasting forest types in India – analysis from remote sensing datasets - V. Krishna Prasad; K. V. S. Badarinath; Anuradha Eaturu (Theoretical and Applied Climatology, 2007)

Heat shock transcription factors regulate heat induced cell death in a rat histiocytoma - Kolla V Prasad; Aftab Taiyab; D Jyothi; Usha K Srinivas; Amere S Sreedhar (Journal of Biosciences, 2007)

Residue Evaluation of Controlled-Release Formulations of Imidacloprid Against Rice Leaf Folder - B. Ram Prasad; Vidya S. Singh; Subhash Chander; Jitendra Kumar (Bulletin of Environmental Contamination and Toxicology, 2007)

Bench scale conversion of 3-cyanopyidine to nicotinamide using resting cells of Rhodococcus rhodochrous PA-34 - S. Prasad; J. Raj; T. C. Bhalla (Indian Journal of Microbiology, 2007)

Identification, characterization and utilization of EST-derived genic microsatellite markers for genome analyses of coffee and related species - Ramesh K. Aggarwal; Prasad S. Hendre; Rajeev K. Varshney; Prasanna R. Bhat; V. Krishnakumar; Lalji Singh (Theoretical and Applied Genetics, 2007)

Active, weak and break spells in the Indian summer monsoon - V. S. Prasad; T. Hayashi (Meteorology and Atmospheric Physics, 2007)

Sexual conflict in plants - N. G. Prasad; S. Bedhomme (Journal of Genetics, 2006)

In vitro shoot regeneration of gladiolus in semi-solid agar versus liquid cultures with support systems - V. S. S. Prasad; S. Dutta Gupta (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Hierarchical classification of allelic variation of gliadins in durum wheat - S. Sai Prasad; V. Rao; H. Pandey (Cereal Research Communications, 2006)

Lipase-mediated Transformation of Vegetable Oils into Biodiesel using Propan-2-ol as Acyl Acceptor - Mukesh Kumar Modi; J. R. C. Reddy; B. V. S. K. Rao; R. B. N. Prasad (Biotechnology Letters, 2006)

Airborne Dust Particle Counting Techniques - S. G. Sharma; B. D. Prasad (Environmental Monitoring and Assessment, 2006)

Expression genetics and haplotype analysis reveal cis regulation of serine carboxypeptidase I (Cxp1), a candidate gene for malting quality in barley (Hordeum vulgare L.) - E. Potokina; M. Prasad; L. Malysheva; M. S. Röder; A. Graner (Functional & Integrative Genomics, 2006)

Lunar ranging instrument for Chandrayaan-1 - J. A. Kamalakar; K. V. S. Bhaskar; A. S. Laxmi Prasad; R. Ranjith; K. A. Lohar; R Venketeswaran; T. K. Alex (Journal of Earth System Science, 2005)

Climatic controls of vegetation vigor in four contrasting forest types of India—evaluation from National Oceanic and Atmospheric Administration’s Advanced Very High Resolution Radiometer datasets (1990–2000) - V. Krishna Prasad; E. Anuradha; K. V. S. Badarinath (International Journal of Biometeorology, 2005)

Geomagnetic activity control on VHF scintillations over an Indian low latitude station, Waltair (17.7‡N, 83.3‡E, 20‡N dip) - D. S. V. V. D. Prasad; P. V. S. Rama Rao; G. Uma; S. Gopi Krishna; K. Venkateswarlu (Journal of Earth System Science, 2005)

Hydrogen peroxide modulates meiotic cell cycle and induces morphological features characteristic of apoptosis in rat oocytes cultured in vitro - S. K. Chaube; P. V. Prasad; S. C. Thakur; T. G. Shrivastav (Apoptosis, 2005)

Cytoprotective and antioxidant activity of Rhodiola imbricata against tert-butyl hydroperoxide induced oxidative injury in U-937 human macrophages - Kanupriya; D. Prasad; M. Sai Ram; R. Kumar; R. C. Sawhney; S. K. Sharma; G. Ilavazhagan; D. Kumar; P. K. Banerjee (Molecular and Cellular Biochemistry, 2005)

Dehydrogenase activity and VAM fungi in tree-rhizosphere of agroforestry systems in Indian arid zone - Rajendra Prasad; R. S. Mertia (Agroforestry Systems, 2005)

Development of cotton transgenics with antisense AV2 gene for resistance against cotton leaf curl virus (CLCuD) via Agrobacterium tumefaciens - Sanjaya; V. V. Satyavathi; V. Prasad; N. Kirthi; S. P. Maiya; H. S. Savithri; G. Lakshmi. Sita (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Enhanced production of tropane alkaloids in Scopolia parviflora by introducing the PMT (putrescine N-methyltransferase) gene - Ok-Sun Lee; Young-Min Kang; Hee-Young Jung; Ji-Yun Min; Seung-Mi Kang; Chandrakant S. Karigar; D. Theertha Prasad; Jung-Dong Bahk; Myung-Suk Choi (In Vitro Cellular & Developmental Biology - Plant, 2005)

Comparative Evaluation of SSR and ISSR Markers for Polymorphism in Landraces and Elite Varieties of Rice (Oryza sativa L) - A. S. Hari Prasad; C. N. Neeraja; N. Sarla; E. A. Siddiq (Journal of Plant Biochemistry and Biotechnology, 2005)

Promoter Trapping in Arabidopsis Using T-DNA Insertional Mutagenesis - Radhamony Resminath; Anand Mohan Prasad; Dhiraj R. Thakare; C. Sivanandan; S. R. Bhat; Srinivasan (Journal of Plant Biochemistry and Biotechnology, 2005)

Mortality Patterns in Dairy Animals under Organized Herd Management Conditions at Karnal India - S. Prasad; N. Ramachandran; S. Raju (Tropical Animal Health and Production, 2004)

News - Manager Singh; Atar Singh; Mahabeer Prasad; S. B. Singh (Sugar Tech, 2004)

Study of cloud liquid water path and total precipitable water from irs-p4/msmr and numerical weather prediction model output - S. Das; A. S. K. A. V. Prasad Rao; U. C. Mohanty; A. K. Mitra; D. Rajan (Journal of the Indian Society of Remote Sensing, 2004)

Sea State Hindcast with ECMWF Data Using a Spectral Wave Model for Typical Monsoon Months - B. Prasad Kumar; Ruchi Kalra; S. K. Dube; P. C. Sinha; A. D. Rao (Natural Hazards, 2004)

The Siva-1 putative amphipathic helical region (SAH) is sufficient to bind to BCL-XL and sensitize cells to UV radiation induced apoptosis - F. Chu; A. Borthakur; X. Sun; J. Barkinge; R. Gudi; S. Hawkins; K. V. S. Prasad (Apoptosis, 2004)

Trends in food production and nitrous oxide emissions from the agriculture sector in India: environmental implications - V. Krishna Prasad; Ben Stinner; Deb Stinner; John Cardina; Richard Moore; Prabhat K. Gupta; Harao Tsuruta; Kiyoto Tanabe; K. V. S. Badarinath; Casey Hoy (Regional Environmental Change, 2003)

Agrobacterium tumefaciens-mediated transformation of an Oncidium orchid - C.-H. Liau; S.-J. You; V. Prasad; H.-H. Hsiao; J.-C. Lu; N.-S. Yang; M.-T. Chan (Plant Cell Reports, 2003)

Slow desiccation leads to high-frequency shoot recovery from transformed somatic embryos of cotton (Gossypium hirsutum L. cv. Coker310FR) - B. Chaudhary; S. Kumar; K. V. S. K. Prasad; G. S. Oinam; P. K. Burma; D. Pental (Plant Cell Reports, 2003)

Impact of a consistent height reassignment method for INSAT derived cloud motion vectors - V. S. Prasad; K. J. Ramesh; A. K. Bohra; Sant Prasad (Meteorology and Atmospheric Physics, 2003)

Modelling the quantitative evaluation of soil nutrient supply, nutrient use efficiency, and fertilizer requirements of wheat in India - H. Pathak; P.K. Aggarwal; R. Roetter; N. Kalra; S.K. Bandyopadhaya; S. Prasad; H. Van Keulen (Nutrient Cycling in Agroecosystems, 2003)

Zinc in Cancer Prevention - Ananda S. Prasad; Omer Kucuk (Cancer and Metastasis Reviews, 2002)

Retrieval of sea surface velocities using sequential Ocean Colour Monitor (OCM) data - J. S. Prasad; A. S. Rajawat; Yaswant Pradhan; O. S. Chauhan; S. R. Nayak (Journal of Earth System Science, 2002)

Candidate gene polymorphisms among North Indians and their association with schizophrenia in a case-control study - Prachi Semwal; Suman Prasad; Panchami G. Varma; A. M. Bhagwat; S. N. Deshpande; B. K. Thelma (Journal of Genetics, 2002)

Emission of Nitrous Oxide from Rice-Wheat Systems of Indo-Gangetic Plains of India - H. Pathak; Arti Bhatia; Shiv Prasad; Shalini Singh; S. Kumar; M. C. Jain; U. Kumar (Environmental Monitoring and Assessment, 2002)

Use of SAMPL for a study of DNA polymorphism, genetic diversity and possible gene tagging in bread wheat - J. K. Roy; H. S. Balyan; M. Prasad; P. K. Gupta (Theoretical and Applied Genetics, 2002)

Amphibians and squamates from the Neogene Siwalik beds of Jammu and Kashmir, India - Jean-Claude Rage; Sudagar S. Gupta; Guntupalli V. R. Prasad (PalZ, 2001)

Comparing farmers and breeders rankings in varietal selection for low-input environments: A case study of rainfed rice in eastern India - B. Courtois; B. Bartholome; D. Chaudhary; G. McLaren; C.H. Misra; N.P. Mandal; S. Pandey; T. Paris; C. Piggin; K. Prasad; A.T. Roy; R.K. Sahu; et al. (Euphytica, 2001)

Aminopeptidase-N from the Helicoverpa armigera (Hubner) Brush Border Membrane Vesicles as a Receptor of Bacillus thuringiensis Cry1Ac δ-Endotoxin - Sanjay S. Ingle; Nidhi Trivedi; Rakesh Prasad; Jes Kuruvilla; Koteshwara Kukatla Rao; H.S. Chhatpar (Current Microbiology, 2001)

Toxin Production in Batch Cultures of Freshwater Cyanobacterium Microcystis aeruginosa - N. Gupta; A. S. B. Bhaskar; R. S. Dangi; G. B. K. S. Prasad; P. V. Lakshmana Rao (Bulletin of Environmental Contamination and Toxicology, 2001)

Irrigation Water Requirements and Supply Analysis in Dehradun Region—An Integrated Remote Sensing and GIS Approach - K. H. V. Durga Rao; C. S. Krishna Kumar; V. Hari Prasad (Journal of the Indian Society of Remote Sensing, 2001)

Integrated physical maps of 2DL, 6BS and 7DL carrying loci for grain protein content and pre-harvest sprouting tolerance in bread wheat - R. K. Varshney; M. Prasad; J. K. Roy; M. S. Röder; H. S. Balyan; P. K. Gupta (Cereal Research Communications, 2001)

Some characteristics of Limited-Area Model-Precipitation forecast of Indian monsoon and evaluation of associated flow features - S. K. Roy Bhowmik; K. Prasad (Meteorology and Atmospheric Physics, 2001)

Stratospheric zonal wind and temperature in relation to summer monsoon rainfall over India - S. D. Bansod; K. D. Prasad; S. V. Singh (Theoretical and Applied Climatology, 2000)

Persistence and Safety Evaluation of Alphamethrin on Mustard ( Brassica campestris Linn.) - R. Kumar; A. K. Dikshit; S. K. Prasad (Bulletin of Environmental Contamination and Toxicology, 2000)

Persistence and Safety Evaluation of Alphamethrin on Mustard (Brassica campestris Linn.) - R. Kumar; A. K. Dikshit; S. K. Prasad (Bulletin of Environmental Contamination and Toxicology, 2000)

Identification of eight chromosomes and a microsatellite marker on 1AS associated with QTL for grain weight in bread wheat - R. K. Varshney; M. Prasad; J. K. Roy; N. Kumar; Harjit-Singh; H. S. Dhaliwal; H.S. Balyan; P.K. Gupta (Theoretical and Applied Genetics, 2000)

Characterization of microsatellites and development of chromosome specific STMS markers in bread wheat - Rajeev K. Varshney; Alok Kumar; Harindra S. Balyan; Joy K. Roy; Manoj Prasad; Pushpendra K. Gupta (Plant Molecular Biology Reporter, 2000)

The use of microsatellites for detecting DNA polymorphism, genotype identification and genetic diversity in wheat - M. Prasad; R. K. Varshney; J. K. Roy; H. S. Balyan; P. K. Gupta (Theoretical and Applied Genetics, 2000)

A terrain evaluation using remote sensing and gis—case study of neyyar wild life sanctuary, Kerala - D. S. Suresh Babu; B. K. Jaya Prasad; V. S. Rajeev (Journal of the Indian Society of Remote Sensing, 1999)

Coating of Prilled Urea with Neem (Azadirachta Indica Juss) Oil for Efficient Nitrogen Use in Rice - R. Prasad; S. Singh; V. S. Saxena; C. Devkumar (The Science of Nature, 1999)

Modern pollen spectra from tropical South India and Sri Lanka: altitudinal distribution - R. Bonnefille; K. Anupama; D. Barboni; J. Pascal; S. Prasad; J. P. Sutra (Journal of Biogeography, 1999)
Summary We analysed the pollen content of 106 surface soil samples from evergreen and deciduous tropical forests distributed between 6° and 13° of latitude north in South India and Sri Lanka. The samples were collected along altitudinal gradients, ranging from 50 to 2420 m, in five regions that experience different rainfall regimes. Original pollen data from tropical vegetation subjected to seasonal monsoon rains are presented along altitude/temperature gradients. This paper includes a summarized description of the vegetation types mapped in the area. The pollen results are presented in the form of quantitative pollen diagrams and correspondence analyses. They show clear distinct pollen assemblages and markers for all types of vegetation in deciduous and evergreen vegetation. Forests are well identified by percentages of Arboreal Pollen greater than 50%, despite the fact that Dipterocarpaceae and Lauraceae are hardly recorded by pollen. The pollen distinction between low, medium and high elevation evergreen forests matches that established by ecologists. The botanical limits, respectively, placed at 900 m and 1500 m limits, correspond to the 20 °C and 15 °C‐values of mean temperature of the coldest month. They appear clearly identified in the modern pollen record. This justifies further use of pollen data in Biome modelling.

Vegetation discrimination using irs-p3 wifs temporal dataset - a case study from rampa forests, eastern ghats, a.p. - V. Krishna Prasad; Yogesh Kant; K. V. S. Badarinath (Journal of the Indian Society of Remote Sensing, 1999)

Studies on forest fires using dmsp ols data - V. Krishna Prasad; Yogesh Kant; K. V. S. Badarinath (Journal of the Indian Society of Remote Sensing, 1999)

A microsatellite marker associated with a QTL for grain protein content on chromosome arm 2DL of bread wheat - M. Prasad; R. K. Varshney; A. Kumar; H. S. Balyan; P. C. Sharma; K. J. Edwards; H-Singh; H. S. Dhaliwal; J. K. Roy; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Identification of a microsatellite on chromosomes 6B and a STS on 7D of bread wheat showing an association with preharvest sprouting tolerance - J. K. Roy; M. Prasad; R. K. Varshney; H. S. Balyan; T. K. Blake; H. S. Dhaliwal; H-Singh; K. J. Edwards; P. K. Gupta (Theoretical and Applied Genetics, 1999)

3-D HLEM Modeling of Tropical Weathering: A Trial from a Granitic Area of N-W Rajasthan, India - M. Poddar; G. Ashokbabu; S. B. Singh; P. P. Prasad (Pure and Applied Geophysics, 1999)

Isolation, genomic organization, and expression analysis of Men1, the murine homolog of the MEN1 gene - Siradanahalli C. Guru; Judy S. Crabtree; Kevin D. Brown; Karen J. Dunn; Pachiappan Manickam; Nijaguna B. Prasad; Danny Wangsa; A. Lee Burns; Allen M. Spiegel; Stephen J. Marx; William J. Pavan; Francis S. Collins; et al. (Mammalian Genome, 1999)

Grain mould resistance and associated characters of sorghum genotypes - S. Audilakshmi; J.W. Stenhouse; T.P. Reddy; M.V.R. Prasad (Euphytica, 1999)

Simulated Annealing 2-D Nonlinear Inversion of Geomagnetic Deep Sounding Data Near Ujjain-Guna, India - S. N. Prasad (Pure and Applied Geophysics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Teleconnections: Northern hemisphere lower stratospheric geopotential heights and Indian monsoon rainfall - R. H. Kripalani; A. Kulkarni; S. R. Inamdar; K. D. Prasad (Meteorology and Atmospheric Physics, 1999)

Zinc and immunity - Ananda S. Prasad (Molecular and Cellular Biochemistry, 1998)

A critical evaluation of copper metabolism in indian wilson’s disease children with special reference to their phenotypes and relatives - Rajendra Prasad; Gurjit Kaur; B. N. S. Walia (Biological Trace Element Research, 1998)

Pituitary-gonadal hormones during prolonged residency in Antarctica - R. C. Sawhney; A. S. Malhotra; Rajendra Prasad; Karan Pal; Rajesh Kumar; A. C. Bajaj (International Journal of Biometeorology, 1998)

Studies on biodiversity using semivariogram approach from IRS-IC LISS-III data - V Krishna Prasad; T Rajagopal; Yogesh Kant; Surya Srinivas; K (xxV) S Badarinath (Journal of the Indian Society of Remote Sensing, 1998)

Effect of elevated CO2 concentration on seedling growth rate and photosynthesis inHevea brasiliensis - A. S. Devakumar; M. S. Shesha Shayee; M. Udayakumar; T. G. Prasad (Journal of Biosciences, 1998)

Assessment of quality and impact of full resolution TOVS temperature profile data on the operational global data assimilation-forecast system of India - V. S. Prasad; K. J. Ramesh; A. K. Bohra; R. C. Bhatia (Meteorology and Atmospheric Physics, 1998)

Bancroftian filariasis in south east Madhya Pradesh: Pre-control epidemilogical observations - Vandana Dixit; Ashok V. Kurup; A K Gupta; O M Kataria; G B K S Prasad (Indian Journal of Clinical Biochemistry, 1997)

DNA binding protein of mycobacteria and human immune response - H. K. Prasad; S. Prabhakar; P. S. Annapurna; Shamsuzzaman; Surinder Kaur; N. K. Jain; A. B. Dey; Najmul Islam; Manoj Raje (Indian Journal of Clinical Biochemistry, 1997)

Subhorizontal Layering in the Lower Crust and its Tectonic Significance in the Narmada-Son-Region, India - P. R. Reddy; D. M. Mall; A. S. S. S. R. S. Prasad (Pure and Applied Geophysics, 1997)

Inhibition of human lymphocyte function by organic solvents - Ahmed S. Shoker; Mohamed A. Murabit; Fawsy F. Georges; Louis F. Qualtiere; Harry G. Deneer; Kailash Prasad (Molecular and Cellular Biochemistry, 1997)

Threatened fishes of the world: Amblyceps mangois Hamilton, 1822 (Amblycipitidae) - Maya S. Prasad; Amrendra N. Yadav; Balram Singh (Environmental Biology of Fishes, 1997)

Flowcytometric assessment of intracellular interferon -γ production in human CD4 + ve T-cells on mycobacterial antigen stimulation - S. Bhattacharyya; S. N. Das; A. B. Dey; K. Nagarkar; J. Lobo; S. K. Kapoor; H. K. Prasad (Journal of Biosciences, 1997)

A mid to late Holocene record of palaeoclimatic changes from Nal Sarovar: a palaeodesert margin lake in western India - SUSHMA PRASAD; SHEELA KUSUMGAR; S. K. GUPTA (Journal of Quaternary Science, 1997)

FORECASTING THE SPATIAL VARIABILITY OF THE INDIAN MONSOON RAINFALL USING CANONICAL CORRELATION - K. D. PRASAD; S. V. SINGH (International Journal of Climatology, 1996)

SEASONAL VARIATIONS OF THE RELATIONSHIP BETWEEN SOME ENSO PARAMETERS AND INDIAN RAINFALL - K. D. PRASAD; S. V. SINGH (International Journal of Climatology, 1996)

SEASONAL VARIATIONS OF THE RELATIONSHIP BETWEEN SOME ENSO PARAMETERS AND INDIAN RAINFALL - K. D. PRASAD; S. V. SINGH (International Journal of Climatology, 1996)

Efficacité des ennemis naturels deLantana camara à Guam : évaluation locale et saisonnière - R. Muniappan; G. R. W. Denton; J. W. Brown; T. S. Lali; U. Prasad; P. Singh (BioControl, 1996)

Large-Scale features of the indian summer monsoon rainfall and their association with some oceanic and atmospheric variables - K. D. Prasad; S. V. Singh (Advances in Atmospheric Sciences, 1988)

Monsoon rainfall and southern oscillation responses in the pressures over the Northern Indian Ocean - K. D. Prasad; S. V. Singh (Advances in Atmospheric Sciences, 1988)

Relationship between 500 hPa ridge axis positions over the indian and the west Pacific regions and the Indian summer monsoon rainfall - S. V. Singh; S. R. Inamdar; R. H. Kripalani; K. D. Prasad (Advances in Atmospheric Sciences, 1986)

Temperature response of trehalase from a mesophilic (Neurospora crassa) and a thermophilic (Thermomyces lanuginosus) fungus - A. R. S. Prasad; Ramesh Maheshwari (Archives of Microbiology, 1979)